Hadith #7090 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
The Prophet (ï·º) sent Muâadh to Yemen.
Grade: Sahih

Hadith #7091 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
When the Prophet (ï·º) sent Mu`adh to Yemen, he said to him, âYou are going to a nation from the people of the Scripture, so let the first thing to which you will invite them, be the Tauhid of Allah. If they learn that, tell them that Allah has enjoined on them, five prayers to be offered in one day and one night. And if they pray, tell them that Allah has enjoined on them Zakat of their properties and it is to be taken from the rich among them and given to the poor. And if they agree to that,
Grade: Sahih

Hadith #7092 - Sahih al-Bukhari - Muadh ibn Jabal (Sahih al-Bukhari)
The Prophet (ï·º) said, âO Mu`adh! Do you know what Allahâs Right upon His slaves is?â I said, âAllah and His Apostle know best.â The Prophet (ï·º) said, âTo worship Him (Allah) Alone and to join none in worship with Him (Allah). Do you know what their right upon Him is?â I replied, âAllah and His Apostle know best.â The Prophet (ï·º) said, âNot to punish them (if they do so).
Grade: Sahih

Hadith #7093 - Sahih al-Bukhari - Abu Sa'id al-Khudri (Sahih al-Bukhari)
A man heard another man reciting (in the prayers): âSay (O Muhammad): âHe is Allah, the One.â (112.1) And he recited it repeatedly. When it was morning, he went to the Prophet (ï·º) and informed him about that as if he considered that the recitation of that Sura by itself was not enough. Allahâs Messenger (ï·º) said, âBy Him in Whose Hand my life is, it is equal to one-third of the Qurâan.â
Grade: Sahih

Hadith #7094 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
The Prophet (ï·º) sent (an army unit) under the command of a man who used to lead his companions in the prayers and would finish his recitation with (the Sura 112): âSay (O Muhammad): âHe is Allah, the One.â â (112.1) When they returned (from the battle), they mentioned that to the Prophet. He said (to them), âAsk him why he does so.â They asked him and he said, âI do so because it mentions the qualities of the Beneficent and I love to recite it (in my prayer).â The Prophet; said
Grade: Sahih

Hadith #7095 - Sahih al-Bukhari - Jarir bin 'Abdullah al-Bajli (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âAllah will not be merciful to those who are not merciful to mankind.â
Grade: Sahih

Hadith #7096 - Sahih al-Bukhari - Usama bin 'Umayr al-Hadhali (Sahih al-Bukhari)
We were with the Prophet (ï·º) when suddenly there came to him a messenger from one of his daughters who was asking him to come and see her son who was dying. The Prophet (ï·º) said (to the messenger), âGo back and tell her that whatever Allah takes is His, and whatever He gives is His, and everything with Him has a limited fixed term (in this world). So order her to be patient and hope for Allahâs reward.â But she sent the messenger to the Prophet (ï·º) again, swearing that he should come
Grade: Sahih

Hadith #7097 - Sahih al-Bukhari - Abu Musa al-Asha'ari (Sahih al-Bukhari)
The Prophet (ï·º) said, âNone is more patient than Allah against the harmful and annoying words He hears (from the people): They ascribe children to Him, yet He bestows upon them health and provision .
Grade: Sahih

Hadith #7098 - Sahih al-Bukhari - ibn Umar (Sahih al-Bukhari)
The Prophet (ï·º) said, âThe keys of the unseen are five and none knows them but Allah: (1) None knows (the sex) what is in the womb, but Allah: (2) None knows what will happen tomorrow, but Allah; (3) None knows when it will rain, but Allah; (4) None knows where he will die, but Allah (knows that); (5) and none knows when the Hour will be established, but Allah.â
Grade: Sahih

Hadith #7099 - Sahih al-Bukhari - Masruq (Sahih al-Bukhari)
`Aisha said, âIf anyone tells you that Muhammad has seen his Lord, he is a liar, for Allah says: âNo vision can grasp Him.â (6.103) And if anyone tells you that Muhammad has seen the Unseen, he is a liar, for Allah says: âNone has the knowledge of the Unseen but Allah.â
Grade: Sahih

Hadith #7100 - Sahih al-Bukhari - Abdullah bin (Sahih al-Bukhari)
We used to pray behind the Prophet (ï·º) and used to say: âAs-Salamu âAl-Allah. The Prophet (ï·º) said, âAllah himself is As-Salam (Name of Allah), so you should say: âat-Tahiyatu lil-lahi was-sala-watu wattaiyibatu, as-salamu `alaika aiyyuha-n-nabiyyu wa rahmatu-l-lahi wa barakatuhu, as-salamu `alaina wa `ala `ibadi-l-lahi as-salihin. Ashhadu an la ilaha il-lallah, wa ash-hadu anna Muhammadan `abduhu wa rasuluhu.ââ
Grade: Sahih

Hadith #7101 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
The Prophet (ï·º) said, âOn the Day of Resurrection Allah will hold the whole earth and fold the heaven with His right hand and say, âI am the King: where are the kings of the earth?â â
Grade: Sahih

Hadith #7102 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
The Prophet (ï·º) used to say, âI seek refuge (with YOU) by Your âIzzat, None has the right to be worshipped but You Who does not die while the Jinns and the human beings die.â
Grade: Sahih

Hadith #7103 - Sahih al-Bukhari - Anas ibn Malik (Sahih al-Bukhari)
The Prophet (ï·º) said, â(The people will be thrown into Hell ( Fire) and it will keep on saying, âIs there any more?â till the Lord of the worlds puts His Foot over it, whereupon its different sides will come close to each other, and it will say, âQad! Qad! (enough! enough!) By Your âIzzat (Honor and Power) and YOUR KARAM (Generosity)!â Paradise will remain spacious enough to accommodate more people until Allah will create some more people and let them dwell in the superfluous space
Grade: Sahih

Hadith #7104 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
The Prophet (ï·º) used to invoke Allah at night, saying, âO Allah: All the Praises are for You: You are the Lord of the Heavens and the Earth. All the Praises are for You; You are the Maintainer of the Heaven and the Earth and whatever is in them. All the Praises are for You; You are the Light of the Heavens and the Earth. Your Word is the Truth, and Your Promise is the Truth, and the Meeting with You is the Truth, and Paradise is the Truth, and the (Hell) Fire is the Truth, and the Hour is th
Grade: Sahih

Hadith #7105 - Sahih al-Bukhari - Abu Musa al-Asha'ari (Sahih al-Bukhari)
We were with the Prophet (ï·º) on a journey, and whenever we ascended a high place, we used to say, âAllahu Akbar.â The Prophet (ï·º) said, âDonât trouble yourselves too much! You are not calling a deaf or an absent person, but you are calling One Who Hears, Sees, and is very near.â Then he came to me while I was saying in my heart, âLa hawla wala quwwatta illa billah (There is neither might nor power but with Allah).â He said, to me, âO `Abdullah bin Qais! Say, âLa hawla wala
Grade: Sahih

Hadith #7106 - Sahih al-Bukhari - Abdullah bin (Sahih al-Bukhari)
Abu Bakr As-Siddiq said to the Prophet (ï·º) âO Allahâs Messenger (ï·º)! Teach me an invocation with which I may invoke Allah in my prayers.â The Prophet (ï·º) said, âSay: O Allah! I have wronged my soul very much (oppressed myself), and none forgives the sins but You; so please bestow Your Forgiveness upon me. No doubt, You are the Oft-Forgiving, Most Merciful.â
Grade: Sahih

Hadith #7107 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
The Prophet (ï·º) said, âGabriel called me and said, âAllah has heard the statement of your people and what they replied to you.'â
Grade: Sahih

Hadith #7108 - Sahih al-Bukhari - Jabir ibn 'Abdullah (Sahih al-Bukhari)
As-Salami: Allahâs Messenger (ï·º) used to teach his companions to perform the prayer of Istikhara for each and every matter just as he used to teach them the Suras from the Qurâan He used to say, âIf anyone of you intends to do some thing, he should offer a two rak`at prayer other than the compulsory prayers, and after finishing it, he should say: O Allah! I consult You, for You have all knowledge, and appeal to You to support me with Your Power and ask for Your Bounty, for You are able t
Grade: Sahih

Hadith #7109 - Sahih al-Bukhari - Abdullah bin (Sahih al-Bukhari)
The Prophet (ï·º) frequently used to swear, âNo, by the One Who turns the hearts.â
Grade: Sahih

Hadith #7110 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âAllah has ninety-nine Names, one-hundred less one; and he who memorized them all by heart will enter Paradise.â To count something means to know it by heart.
Grade: Sahih

Hadith #7111 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
The Prophet (ï·º) said, âWhen anyone of you goes to bed, he should dust it off thrice with the edge of his garment, and say: Bismika Rabbi Wada`tu janbi, wa bika arfaâhu. In amsakta nafsi faghfir laha, wa in arsaltaha fahfazha bima tahfaz bihi âibadaka-s-salihin.â
Grade: Sahih

Hadith #7112 - Sahih al-Bukhari - Hudhaifa' (Sahih al-Bukhari)
When the Prophet (ï·º) went to bed, he used to say, âAllahumma bismika ahya wa amut.â And when he woke up in the mornings he used to say, âAl-hamdu li l-lahi al-ladhi ahyana baâda ma amatana wa ilaihi-nnushur.â
Grade: Sahih

Hadith #7113 - Sahih al-Bukhari - Abu Dharr al-Ghaffari (Sahih al-Bukhari)
When the Prophet (ï·º) went to bed at night, he used to say: âBismika namutu wa nahya.â And when he got up in the morning, he used to say, âAl hamdu li l-lahi al-ladhi ahyana baâda ma amatana, wa ilaihi-nnushur.â
Grade: Sahih

Hadith #7114 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âIf anyone of you, when intending to have a sexual relation (sleep) with his wife, says: Bismillah, Allahumma jannibna ashShaitan, wa Jannib ash-Shaitana ma razaqtana, Satan would never harm that child, should it be ordained that they will have one. (Because of that sleep).
Grade: Sahih

Hadith #7115 - Sahih al-Bukhari - Adi ibn Hatim al-Tayyi' (Sahih al-Bukhari)
I asked the Prophet, âI send off (for a game) my trained hunting dogs; (what is your verdict concerning the game they hunt?â He said, âIf you send off your trained hunting dogs and mention the Name of Allah, then, if they catch some game, eat (thereof). And if you hit the game with a miârad (a hunting tool) and it wounds it, you can eat (it).
Grade: Sahih

Hadith #7116 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
The people said to the Prophet (ï·º) , âO Allahâs Messenger (ï·º)! Here are people who have recently embraced Islam and they bring meat, and we do not know whether they had mentioned Allahâs Name while slaughtering the animals or not.â The Prophet (ï·º) said, âYou should mention Allahâs Name and eat.â
Grade: Sahih

Hadith #7117 - Sahih al-Bukhari - Anas ibn Malik (Sahih al-Bukhari)
The Prophet (ï·º) slaughtered two rams as sacrifice and mentioned Allahâs Name and said, âAllahu-Akbarâ while slaughtering).
Grade: Sahih

Hadith #7118 - Sahih al-Bukhari - Jundab bin 'Abdullah al-Bajli (Sahih al-Bukhari)
That he witnessed the Prophet (ï·º) on the Day of Nahr. The Prophet (ï·º) offered prayer and then delivered a sermon saying, âWhoever slaughtered his sacrifice before offering prayer, should slaughter another animal in place of the first; and whoever has not yet slaughtered any, should slaughter a sacrifice and mention Allahâs Name while doing so.â
Grade: Sahih

Hadith #7119 - Sahih al-Bukhari - ibn Umar (Sahih al-Bukhari)
The Prophet (ï·º) said, âDo not swear by your fathers; and whoever wants to swear should swear by Allah.â
Grade: Sahih

Hadith #7120 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
Allahâs Messenger (ï·º) sent ten persons to bring the enemyâs secrets and Khubaib Al-Ansari was one of them. âUbaidullah bin âIyad told me that the daughter of Al-Harith told him that when they gathered (to kill Khubaib Al Ansari) he asked for a razor to clean his pubic region, and when they had taken him outside the sanctuary of Mecca in order to kill him, he said in verse, âI donât care if I am killed as a Muslim, on any side (of my body) I may be killed in Allahâs Cause; for tha
Grade: Sahih

Hadith #7121 - Sahih al-Bukhari - Abdullah bin (Sahih al-Bukhari)
The Prophet (ï·º) said, âThere is none having a greater sense of Ghira than Allah, and for that reason He has forbidden shameful deeds and sins (illegal sexual intercourse etc.) And there is none who likes to be praised more than Allah does.â (See Hadith No. 147, Vol. 7)
Grade: Sahih

Hadith #7122 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
The Prophet (ï·º) said, âWhen Allah created the Creation, He wrote in His Bookâand He wrote (that) about Himself, and it is placed with Him on the ThroneââVerily My Mercy overcomes My Anger.'â
Grade: Sahih

Hadith #7123 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
The Prophet (ï·º) said, âAllah says: âI am just as My slave thinks I am, (i.e. I am able to do for him what he thinks I can do for him) and I am with him if He remembers Me. If he remembers Me in himself, I too, remember him in Myself; and if he remembers Me in a group of people, I remember him in a group that is better than they; and if he comes one span nearer to Me, I go one cubit nearer to him; and if he comes one cubit nearer to Me, I go a distance of two outstretched arms nearer to him
Grade: Sahih

Hadith #7124 - Sahih al-Bukhari - Jabir ibn 'Abdullah (Sahih al-Bukhari)
when this Verse:ââSay (O Muhammad!): He has Power to send torments on you from above,â (6.65) was revealed; The Prophet (ï·º) said, âI take refuge with Your Face.â Allah revealed:â â..or from underneath your feet.â (6.65) The Prophet (ï·º) then said, âI seek refuge with Your Face!â Then Allah revealed:âââ¦or confuse you in party-strife.â (6.65) Oh that, the Prophet (ï·º) said, âThis is easier.â
Grade: Sahih

Hadith #7125 - Sahih al-Bukhari - Abdullah bin (Sahih al-Bukhari)
Ad-Dajjal was mentioned in the presence of the Prophet. The Prophet (ï·º) said, âAllah is not hidden from you; He is not one-eyed,â and pointed with his hand towards his eye, adding, âWhile Al-Masih Ad- Dajjal is blind in the right eye and his eye looks like a protruding grape.â
Grade: Sahih

Hadith #7126 - Sahih al-Bukhari - Anas ibn Malik (Sahih al-Bukhari)
The Prophet (ï·º) said, âAllah did not send any prophet but that he warned his nation of the one-eyed liar (Ad-Dajjal). He is one-eyed while your Lord is not one-eyed, The word âKafirâ (unbeliever) is written between his two eyes.â
Grade: Sahih

Hadith #7127 - Sahih al-Bukhari - Abu Sa'id al-Khudri (Sahih al-Bukhari)
That during the battle with Bani Al-Mustaliq they (Muslims) captured some females and intended to have sexual relation with them without impregnating them. So they asked the Prophet (ï·º) about coitus interrupt us. The Prophet (ï·º) said, âIt is better that you should not do it, for Allah has written whom He is going to create till the Day of Resurrection.â Qazaâa said, âI heard Abu Sa`id saying that the Prophet (ï·º) said, âNo soul is ordained to be created but Allah will create it.â
Grade: Sahih

Hadith #7128 - Sahih al-Bukhari - Anas ibn Malik (Sahih al-Bukhari)
The Prophet (ï·º) said, âAllah will gather the believers on the Day of Resurrection in the same way (as they are gathered in this life), and they will say, âLet us ask someone to intercede for us with our Lord that He may relieve us from this place of ours.â Then they will go to Adam and say, âO Adam! Donât you see the people (peopleâs condition)? Allah created you with His Own Hands and ordered His angels to prostrate before you, and taught you the names of all the things. Please in
Grade: Sahih

Hadith #7129 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âAllahâs Hand is full, and (its fullness) is not affected by the continuous spending, day and night.â He also said, âDo you see what He has spent since He created the Heavens and the Earth? Yet all that has not decreased what is in His Hand.â He also said, âHis Throne is over the water and in His other Hand is the balance (of Justice) and He raises and lowers (whomever He will).â (See Hadith No. 206, Vol. 6)
Grade: Sahih

Hadith #7130 - Sahih al-Bukhari - ibn Umar (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âOn the Day of Resurrection, Allah will grasp the whole Earth by His Hand, and all the Heavens in His right, and then He will say, âI am the King.â Abu Huraira said, âAllahâs Messenger (ï·º) said,â Allah will grasp the Earthâ¦â â
Grade: Sahih

Hadith #7131 - Sahih al-Bukhari - Abdullah bin (Sahih al-Bukhari)
A Jew came to the Prophet (ï·º) and said, âO Muhammad! Allah will hold the heavens on a Finger, and the mountains on a Finger, and the trees on a Finger, and all the creation on a Finger, and then He will say, âI am the King.â â On that Allahâs Messenger (ï·º) smiled till his premolar teeth became visible, and then recited:â âNo just estimate have they made of Allah such as due to himâ¦.(39.67) `Abdullah added: Allahâs Apostle smiled (at the Jewâs statement) expressing his won
Grade: Sahih

Hadith #7132 - Sahih al-Bukhari - Abdullah bin (Sahih al-Bukhari)
A man from the people of the scripture came to the Prophet (ï·º) and said, âO Abal-Qasim! Allah will hold the Heavens upon a Finger, and the Earth on a Finger and the land on a Finger, and all the creation on a Finger, and will say, âI am the King! I am the King!â â I saw the Prophet (after hearing that), smiling till his premolar teeth became visible, and he then recited: â âNo just estimate have they made of Allah such as due to himâ¦ (39.67)
Grade: Sahih

Hadith #7133 - Sahih al-Bukhari - al-Mughira bin 'Abdullah Ø§ÙÙØºÙØ±Ø© Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø¹ÙÙÙ (Sahih al-Bukhari)
Sa`d bin âUbada said, âIf I saw a man with my wife, I would strike him (behead him) with the blade of my sword.â This news reached Allahâs Messenger (ï·º) who then said, âYou people are astonished at Sa`dâs Ghira. By Allah, I have more Ghira than he, and Allah has more Ghira than I, and because of Allahâs Ghira, He has made unlawful Shameful deeds and sins (illegal sexual intercourse etc.) done in open and in secret. And there is none who likes that the people should repent to Him
Grade: Sahih

Hadith #7134 - Sahih al-Bukhari - Sahl bin Sa'd bin Malik (Sahih al-Bukhari)
The Prophet (ï·º) said to a man, âHave you got anything of the Qurâan?â The man said, âYes, such-andsuch Sura, and such-and-such Sura,â naming the Suras.
Grade: Sahih

Hadith #7135 - Sahih al-Bukhari - Imran bin 'Uyaynah Ø¹ÙØ±Ø§Ù Ø¨Ù Ø¹ÙÙÙØ© (Sahih al-Bukhari)
While I was with the Prophet (ï·º) , some people from Bani Tamim came to him. The Prophet (ï·º) said, âO Bani Tamim! Accept the good news!â They said, âYou have given us the good news; now give us (something).â (After a while) some Yemenites entered, and he said to them, âO the people of Yemen! Accept the good news, as Bani Tamim have refused it. â They said, âWe accept it, for we have come to you to learn the Religion. So we ask you what the beginning of this universe was.â The
Grade: Sahih

Hadith #7136 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
The Prophet (ï·º) said, âThe Right (Hand) of Allah Is full, and (Its fullness) is not affected by the continuous spending night and day. Do you see what He has spent since He created the Heavens and the Earth? Yet all that has not decreased what is in His Right Hand. His Throne is over the water and in His other Hand is the Bounty or the Power to bring about death, and He raises some people and brings others down.â (See Hadith No. 508)
Grade: Sahih

Hadith #7137 - Sahih al-Bukhari - Anas ibn Malik (Sahih al-Bukhari)
Zaid bin Haritha came to the Prophet (ï·º) complaining about his wife. The Prophet (ï·º) kept on saying (to him), âBe afraid of Allah and keep your wife.â Aisha said, âIf Allahâs Messenger (ï·º) were to conceal anything (of the Qurâan he would have concealed this Verse.â Zainab used to boast before the wives of the Prophet (ï·º) and used to say, âYou were given in marriage by your families, while I was married (to the Prophet) by Allah from over seven Heavens.â And Thabit recited
Grade: Sahih

Hadith #7138 - Sahih al-Bukhari - Anas ibn Malik (Sahih al-Bukhari)
The Verse of Al-Hijab (veiling of women) was revealed in connection with Zainab bint Jahsh. (On the day of her marriage with him) the Prophet (ï·º) gave a wedding banquet with bread and meat; and she used to boast before other wives of the Prophet (ï·º) and used to say, âAllah married me (to the Prophet (ï·º) in the Heavens.â
Grade: Sahih

Hadith #7139 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
The Prophet (ï·º) said, âWhen Allah had finished His creation, He wrote over his Throne: âMy Mercy preceded My Anger.â
Grade: Sahih

Hadith #7140 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
The Prophet (ï·º) said, âWhoever believes in Allah and His Apostle offers prayers perfectly and fasts (the month of) Ramadan then it is incumbent upon Allah to admit him into Paradise, whether he emigrates for Allahâs cause or stays in the land where he was born.â They (the companions of the Prophet) said, âO Allahâs Messenger (ï·º)! Should we not inform the people of that?â He said, âThere are one-hundred degrees in Paradise which Allah has prepared for those who carry on Jihad in
Grade: Sahih

Hadith #7141 - Sahih al-Bukhari - Abu Dharr al-Ghaffari (Sahih al-Bukhari)
I entered the mosque while Allahâs Messenger (ï·º) was sitting there. When the sun had set, the Prophet (ï·º) said, âO Abu Dharr! Do you know where this (sun) goes?â I said, âAllah and His Apostle know best.â He said, âIt goes and asks permission to prostrate, and it is allowed, and (one day) it, as if being ordered to return whence it came, then it will rise from the west.â Then the Prophet (ï·º) recited, âThat: âAnd the sun runs on its fixed course (for a term decreed),â (3
Grade: Sahih

Hadith #7142 - Sahih al-Bukhari - Zaid bin Asim Mazni (Sahih al-Bukhari)
Abu Bakr sent for me, so I collected the Qurâan till I found the last part of Surat-at-Tauba with Abi Khuza`ima Al-Ansari and did not find it with anybody else. (The Verses are): â âVerily, there has come to you an Apostle (Muhammad) from amongst yourselves..(till the end of Surat Baraâa) (i.e., at- Tauba).â (9.128-129) Yunus also narrated as above.
Grade: Sahih

Hadith #7143 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
The Prophet (ï·º) used to say at the time of difficulty, âLa ilaha il-lallah Al-`Alimul-Halim. La-ilaha illallah Rabul- Arsh-al-Azim, La ilaha-il-lallah Rabus-Samawati Rab-ul-Ard; wa Rab-ul-Arsh Al- Karim.â (See Hadith No. 356 and 357, Vol. 8)
Grade: Sahih

Hadith #7144 - Sahih al-Bukhari - Abu Sa'id al-Khudri (Sahih al-Bukhari)
The Prophet (ï·º) said, âThe people will fall unconscious on the Day of Resurrection, then suddenly I will see Moses holding one of the pillars of the Throne.â Abu Huraira said: The Prophet (ï·º) said, âI will be the first person to be resurrected and will see Moses holding the Throne.â
Grade: Sahih

Hadith #7145 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, â(A group of) angels stay with you at night and (another group of) angels by daytime, and both groups gather at the time of the âAsr and Fajr prayers. Then those angels who have stayed with you overnight, ascend (to Heaven) and Allah asks them (about you) â- and He knows everything about you. âIn what state did you leave My slaves?â The angels reply, âWhen we left them, they were praying, and when we reached them they were praying.â â
Grade: Sahih

Hadith #7146 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âIf somebody gives in charity something equal to a date from his honestly earned money â-for nothing ascends to Allah except goodâ- then Allah will take it in His Right (Hand) and bring it up for its owner as anyone of you brings up a baby horse, till it becomes like a mountain.â Abu Huraira said: The Prophet. said, âNothing ascends to Allah except good.â
Grade: Sahih

Hadith #7147 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
Allahâs Messenger (ï·º) used to say at the time of difficulty, âNone has the right to be worshipped but Allah, the Majestic, the Most Forbearing. None has the right to be worshipped but Allah, the Lord of the Tremendous Throne. None has the right to be worshipped but Allah, the Lord of the Heavens and the Lord of the Honourable Throne. (See Hadith No. 357, Vol. 8)
Grade: Sahih

Hadith #7148 - Sahih al-Bukhari - Abu Sa'id al-Khudri (Sahih al-Bukhari)
When `Ali was in Yemen, he sent some gold in its ore to the Prophet. The Prophet (ï·º) distributed it among Al-Aqraâ bin H`Abis Al-Hanzali who belonged to Bani Mujashi, âUyaina bin Badr Al-Fazari, âAlqama bin âUlatha Al-`Amiri, who belonged to the Bani Kilab tribe and Zaid AI-Khail at-Taâi who belonged to Bani Nabhan. So the Quraish and the Ansar became angry and said, âHe gives to the chiefs of Najd and leaves us!â The Prophet (ï·º) said, âI just wanted to attract and unite thei
Grade: Sahih

Hadith #7149 - Sahih al-Bukhari - Abu Dharr al-Ghaffari (Sahih al-Bukhari)
I asked the Prophet (ï·º) regarding the Verse:ââAnd the sun runs on its fixed course for a term decreed for it.â (36.28) He said, âIts fixed course is underneath Allahâs Throne.â
Grade: Sahih

Hadith #7150 - Sahih al-Bukhari - Jarir bin 'Abdul Hameed al-Razi Ø¬Ø±ÙØ± Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØÙÙØ¯ Ø£Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø§ÙØ¶Ø¨Ù (Sahih al-Bukhari)
We were sitting with the Prophet (ï·º) and he looked at the moon on the night of the full-moon and said, âYou people will see your Lord as you see this full moon, and you will have no trouble in seeing Him, so if you can avoid missing (through sleep or business, etc.) a prayer before sunrise (Fajr) and a prayer before sunset (`Asr) you must do so.â (See Hadith No. 529, Vol. 1)
Grade: Sahih

Hadith #7151 - Sahih al-Bukhari - Jarir bin 'Abdullah al-Bajli (Sahih al-Bukhari)
The Prophet (ï·º) said, âYou will definitely see your Lord with your own eyes.â
Grade: Sahih

Hadith #7152 - Sahih al-Bukhari - Jarir bin 'Abdul Hameed al-Razi Ø¬Ø±ÙØ± Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØÙÙØ¯ Ø£Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø§ÙØ¶Ø¨Ù (Sahih al-Bukhari)
Allahâs Messenger (ï·º) came out to us on the night of the full moon and said, âYou will see your Lord on the Day of Resurrection as you see this (full moon) and you will have no difficulty in seeing Him.â
Grade: Sahih

Hadith #7153 - Sahih al-Bukhari - Ata ibn Yasar Ø¹Ø·Ø§Ø¡ Ø¨Ù ÙØ³Ø§Ø± Ø£Ø¨Ù ÙØÙØ¯ ÙÙÙÙ ÙÙÙÙÙØ© (Sahih al-Bukhari)
On the authority of Abu Huraira: The people said, âO Allahâs Messenger (ï·º)! Shall we see our Lord on the Day of Resurrection?â The Prophet (ï·º) said, âDo you have any difficulty in seeing the moon on a full moon night?â They said, âNo, O Allahâs Messenger (ï·º).â He said, âDo you have any difficulty in seeing the sun when there are no clouds?â They said, âNo, O Allahâs Messenger (ï·º).â He said, âSo you will see Him, like that. Allah will gather all the people on t
Grade: Sahih

Hadith #7154 - Sahih al-Bukhari - Abu Sa'id al-Khudri (Sahih al-Bukhari)
We said, âO Allahâs Messenger (ï·º)! Shall we see our Lord on the Day of Resurrection?â He said, âDo you have any difficulty in seeing the sun and the moon when the sky is clear?â We said, âNo.â He said, âSo you will have no difficulty in seeing your Lord on that Day as you have no difficulty in seeing the sun and the moon (in a clear sky).â The Prophet then said, âSomebody will then announce, âLet every nation follow what they used to worship.â So the companions of the c
Grade: Sahih

Hadith #7155 - Sahih al-Bukhari - Anas ibn Malik (Sahih al-Bukhari)
The Prophet (ï·º) said, âThe believers will be kept (waiting) on the Day of Resurrection so long that they will become worried and say, âLet us ask somebody to intercede far us with our Lord so that He may relieve us from our place. Then they will go to Adam and say, âYou are Adam, the father of the people. Allah created you with His Own Hand and made you reside in His Paradise and ordered His angels to prostrate before you, and taught you the names of all things will you intercede for us
Grade: Sahih

Hadith #7156 - Sahih al-Bukhari - Anas ibn Malik (Sahih al-Bukhari)
Allahâs Messenger (ï·º) sent for the Ansar and gathered them in a tent and said to them, âBe patient till you meet Allah and His Apostle, and I will be on the lake-Tank (Al-Kauthar).
Grade: Sahih

Hadith #7157 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
Whenever the Prophet (ï·º) offered his Tahajjud prayer, he would say, âO Allah, our Lord! All the praises are for You; You are the Keeper (Establisher or the One Who looks after) of the Heavens and the Earth. All the Praises are for You; You are the Light of the Heavens and the Earth and whatever is therein. You are the Truth, and Your saying is the Truth, and Your promise is the Truth, and the meeting with You is the Truth, and Paradise is the Truth, and the (Hell) Fire is the Truth. O Allah!
Grade: Sahih

Hadith #7158 - Sahih al-Bukhari - Adi ibn Hatim al-Tayyi' (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âThere will be none among you but his Lord will speak to him, and there will be no interpreter between them nor a screen to screen Him.â
Grade: Sahih

Hadith #7159 - Sahih al-Bukhari - Abdullah bin (Sahih al-Bukhari)
The Prophet (ï·º) said, â(There will be) two Paradises of silver and all the utensils and whatever is therein (will be of silver); and two Paradises of gold, and its utensils and whatever therein (will be of gold), and there will be nothing to prevent the people from seeing their Lord except the Cover of Majesty over His Face in the Paradise of Eden (eternal bliss).
Grade: Sahih

Hadith #7160 - Sahih al-Bukhari - Abdullah bin (Sahih al-Bukhari)
The Prophet (ï·º) said, âWhoever takes the property of a Muslim by taking a false oath, will meet Allah Who will be angry with him.â Then the Prophet (ï·º) recited the Verse:â âVerily those who purchase a small gain at the cost of Allahâs Covenant and their oaths, they shall have no portion in the Hereafter, neither will Allah speak to them, nor look at them.â (3.77)
Grade: Sahih

Hadith #7161 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
The Prophet (ï·º) said, â(There are) three (types of persons to whom) Allah will neither speak to them on the Day of Resurrections, nor look at them (They are):â(1) a man who takes a false oath that he has been offered for a commodity a price greater than what he has actually been offered; (2) and a man who takes a false oath after the `Asr (prayer) in order to grab the property of a Muslim through it; (3) and a man who forbids others to use the remaining superfluous water. To such a man All
Grade: Sahih

Hadith #7162 - Sahih al-Bukhari - Abu Bakra al-Thaqafi (Sahih al-Bukhari)
The Prophet (ï·º) said, âTime has come back to its original state which it had when Allah created the Heavens and the Earth, the year is twelve months, of which four are sacred; (and out of these four) three are in succession, namely, Dhul-Qaâda, Dhul-Hijja and Muharram, and (the fourth one) Rajab Mudar which is between Jumad (Ath-Tham) and Shaâban.â The Prophet (ï·º) then asked us, âWhich month is this?â We said, âAllah and His Apostle know (it) better.â He kept quiet so long th
Grade: Sahih

Hadith #7163 - Sahih al-Bukhari - Usama bin 'Umayr al-Hadhali (Sahih al-Bukhari)
A son of one of the daughters of the Prophet (ï·º) was dying, so she sent a person to call the Prophet. He sent (her a message), âWhat ever Allah takes is for Him, and whatever He gives is for Him, and everything has a limited fixed term (in this world) so she should be patient and hope for Allahâs reward.â She then sent for him again, swearing that he should come. Allahâs Messenger (ï·º) got up, and so did Mu`adh bin Jabal, Ubai bin Ka`b and âUbada bin As-Samit. When he entered (the h
Grade: Sahih

Hadith #7164 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
The Prophet (ï·º) said, âParadise and Hell (Fire) quarrelled in the presence of their Lord. Paradise said, âO Lord! What is wrong with me that only the poor and humble people enter me ?â Hell (Fire) said, I have been favored with the arrogant people.â So Allah said to Paradise, âYou are My Mercy,â and said to Hell, âYou are My Punishment which I inflict upon whom I wish, and I shall fill both of you.'â The Prophet added, âAs for Paradise, (it will be filled with good people) be
Grade: Sahih

Hadith #7165 - Sahih al-Bukhari - Anas ibn Malik (Sahih al-Bukhari)
The Prophet (ï·º) said, âSome people will be scorched by Hell (Fire) as a punishment for sins they have committed, and then Allah will admit them into Paradise by the grant of His Mercy. These people will be called, âAl-Jahannamiyyinâ (the people of Hell).
Grade: Sahih

Hadith #7166 - Sahih al-Bukhari - Abdullah bin (Sahih al-Bukhari)
A Jewish Rabbi came to Allahâs Messenger (ï·º) and said, âO Muhammad! Allah will put the Heavens on one finger and the earth on one finger, and the trees and the rivers on one finger, and the rest of the creation on one finger, and then will say, pointing out with His Hand, âI am the King.â âOn that Allahâs Apostle smiled and said, âNo just estimate have they made of Allah such as due to Him. (39.67)
Grade: Sahih

Hadith #7167 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
Once I stayed overnight at the house of (my aunt ) Maimuna while the Prophet (ï·º) was with her, to see how was the night prayer of Allah s Apostle Allahâs Messenger (ï·º) talked to his wife for a while and then slept. When it was the last third of the night (or part of it), the Prophet (ï·º) got up and looked towards the sky and recited the Verse:â âVerily! In the creation of the Heavens and the Earthâ¦.there are indeed signs for the men of understanding.â (3.190) Then He got up and pe
Grade: Sahih

Hadith #7168 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âWhen Allah created the creations, He wrote with Him on His Throne: âMy Mercy has preceded My Anger.â
Grade: Sahih

Hadith #7169 - Sahih al-Bukhari - Abdullah bin (Sahih al-Bukhari)
Allahâs Messenger (ï·º) the true and truly inspired, narrated to us, âThe creation of everyone of you starts with the process of collecting the material for his body within forty days and forty nights in the womb of his mother. Then he becomes a clot of thick blood for a similar period (40 days) and then he becomes like a piece of flesh for a similar period. Then an angel is sent to him (by Allah) and the angel is allowed (ordered) to write four things; his livelihood, his (date of) death, h
Grade: Sahih

Hadith #7170 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
The Prophet (ï·º) said, âO Gabriel, what prevents you. from visiting us more often than you do?â Then this Verse was revealed:ââAnd we angels descend not but by Command of your Lord. To Him belongs what is before us and what is behind us..â (19.64) So this was the answer to Muhammad.
Grade: Sahih

Hadith #7171 - Sahih al-Bukhari - Abdullah bin (Sahih al-Bukhari)
While I was walking with Allahâs Messenger (ï·º) in one of the fields of Medina and he was walking leaning on a stick, he passed a group of Jews. Some of them said to the others, âAsk him (the Prophet) about the spirit.â Others said, âDo not ask him.â But they asked him and he stood leaning on the stick and I was standing behind him and I thought that he was being divinely inspired. Then he said, âThey ask you concerning the spirit say: The spirit, its knowledge is with My Lord. And
Grade: Sahih

Hadith #7172 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âAllah guarantees to the person who carries out Jihad for His Cause and nothing compelled him to go out but the Jihad in His Cause, and belief in His Words, that He will either admit him into Paradise or return him with his reward or the booty he has earned to his residence from where he went out.â (See Hadith No. 555).
Grade: Sahih

Hadith #7173 - Sahih al-Bukhari - Abu Musa al-Asha'ari (Sahih al-Bukhari)
A man came to the Prophet (ï·º) and said, âA man fights for pride and haughtiness another fights for bravery, and another fights for showing off; which of these (cases) is in Allahâs Cause?â The Prophet (ï·º) said, âThe one who fights that Allahâs Word (Islam) should be superior, fights in Allahâs Cause.â (See Hadith No. 65, Vol. 4)
Grade: Sahih

Hadith #7174 - Sahih al-Bukhari - al-Mughira ibn Shu'ba (Sahih al-Bukhari)
I heard the Prophet (ï·º) saying, âSome people from my followers will continue to be victorious over others till Allahâs Order (The Hour) is established.â (See Hadith No. 414)
Grade: Sahih

Hadith #7175 - Sahih al-Bukhari - Mu'awiya bin Hadeej (Sahih al-Bukhari)
I heard the Prophet (ï·º) saying, âA group of my followers will keep on following Allahâs Laws strictly and they will not be harmed by those who will disbelieve them or stand against them till Allahâs Order (The Hour) will come while they will be in that state.â
Grade: Sahih

Hadith #7176 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
The Prophet (ï·º) stood before Musailama (the liar) who was sitting with his companions then, and said to him, âIf you ask me for this piece (of palm-leaf stalk), even then I would not give it to you. You cannot avoid what Allah has ordained for you, and if you turn away from Islam, Allah will surely ruin you! â
Grade: Sahih

Hadith #7177 - Sahih al-Bukhari - ibn Mas'ud (Sahih al-Bukhari)
While I was walking in company with the Prophet (ï·º) in one of the fields of Medina, the Prophet (ï·º) was reclining on a palm leave stalk which he carried with him. We passed by a group of Jews. Some of them said to the others, âAsk him about the spirit.â The others said, âDo not ask him, lest he would say something that you hate.â Some of them said, âWe will ask him.â So a man from among them stood up and said, âO Abal-Qasim! What is the spirit?â The Prophet (ï·º) kept quiet a
Grade: Sahih

Hadith #7178 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âAllah guarantees (the person who carries out Jihad in His Cause and nothing compelled him to go out but Jihad in His Cause and the belief in His Word) that He will either admit him into Paradise (Martyrdom) or return him with reward or booty he has earned to his residence from where he went out.â
Grade: Sahih

Hadith #7179 - Sahih al-Bukhari - Anas ibn Malik (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âWhenever anyone of you invoke Allah for something, he should be firm in his asking, and he should not say: âIf You wish, give meâ¦â for none can compel Allah to do something against His Will.â
Grade: Sahih

Hadith #7180 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
That one night Allahâs Messenger (ï·º) visited him and Fatima, the daughter of Allahâs Messenger (ï·º) and said to them, âWon ât you offer (night) prayer?.. `Ali added: I said, âO Allahâs Messenger (ï·º)! Our souls are in the Hand of Allah and when He Wishes to bring us to life, He does.â Then Allahâs Messenger (ï·º) went away when I said so and he did not give any reply. Then I heard him on leaving while he was striking his thighs, saying, âBut man is, more quarrelsome than an
Grade: Sahih

Hadith #7181 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âThe example of a believer is that of a fresh green plant the leaves of which move in whatever direction the wind forces them to move and when the wind becomes still, it stand straight. Such is the similitude of the believer: He is disturbed by calamities (but is like the fresh plant he regains his normal state soon). And the example of a disbeliever is that of a pine tree (which remains) hard and straight till Allah cuts it down when He will.â (See Hadith No.
Grade: Sahih

Hadith #7182 - Sahih al-Bukhari - ibn Umar (Sahih al-Bukhari)
I heard Allahâs Messenger (ï·º) while he was standing on the pulpit, saying, âThe remaining period of your stay (on the earth) in comparison to the nations before you, is like the period between the `Asr prayer and sunset. The people of the Torah were given the Torah and they acted upon it till midday, and then they were worn out and were given for their labor, one Qirat each. Then the people of the Gospel were given the Gospel and they acted upon it till the time of the `Asr prayer, and the
Grade: Sahih

Hadith #7183 - Sahih al-Bukhari - Ubada bin As-Samit (Sahih al-Bukhari)
I, along with a group of people, gave the pledge of allegiance to Allahâs Messenger (ï·º). He said, âI take your Pledge on the condition that you (1) will not join partners in worship with Allah, (2) will not steal, (3) will not commit illegal sexual intercourse, (4) will not kill your offspring, (5) will not slander, (6) and will not disobey me when I order you to do good. Whoever among you will abide by his pledge, his reward will be with Allah, and whoever commits any of those sins and re
Grade: Sahih

Hadith #7184 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
Allahâs Prophet Solomon who had sixty wives, once said, âTonight I will have sexual relation (sleep) with all my wives so that each of them will become pregnant and bring forth (a boy who will grow into) a cavalier and will fight in Allahâs Cause.â So he slept with his wives and none of them (conceived and) delivered (a child) except one who brought a half (body) boy (deformed). Allahâs Prophet said, âIf Solomon had said; âIf Allah Will,â then each of those women would have deliv
Grade: Sahih

Hadith #7185 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
Allahâs Messenger (ï·º) entered upon a sick bedouin in whom he went to visit and said to him, âDonât worry, Tahur (i.e., your illness will be a means of cleansing of your sins), if Allah Will.â The bedouin said, âTahur! No, but it is a fever that is burning in the body of an old man and it will make him visit his grave.â The Prophet (ï·º) said, âThen it is so.â
Grade: Sahih

Hadith #7186 - Sahih al-Bukhari - Abu Qatada ibn Rab'i (Sahih al-Bukhari)
When the people slept till so late that they did not offer the (morning) prayer, the Prophet (ï·º) said, âAllah captured your souls (made you sleep) when He willed, and returned them (to your bodies) when He willed.â So the people got up and went to answer the call of nature, performed ablution, till the sun had risen and it had become white, then the Prophet (ï·º) got up and offered the prayer.
Grade: Sahih

Hadith #7187 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
âA man from the Muslims and a man from the Jews quarrelled, and the Muslim said, âBy Him Who gave superiority to Muhammad over all the people!â The Jew said, âBy Him Who gave superiority to Moses over all the people!â On that the Muslim lifted his hand and slapped the Jew. The Jew went to Allahâs Messenger (ï·º) and informed him of all that had happened between him and the Muslim. The Prophet (ï·º) said, âDo not give me superiority over Moses, for the people will fall unconscious o
Grade: Sahih

Hadith #7188 - Sahih al-Bukhari - Anas ibn Malik (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âAd-Dajjal will come to Medina and find the angels guarding it. If Allah will, neither Ad-Dajjal nor plague will be able to come near it.â
Grade: Sahih

Hadith #7189 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âFor every Prophet there is one invocation which is definitely fulfilled by Allah, and I wish, if Allah will, to keep my that (special) invocation as to be the intercession for my followers on the Day of Resurrection.â
Grade: Sahih

Hadith #7190 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âWhile I was sleeping, I saw myself (in a dream) standing by a well. I drew from it as much water as Allah wished me to draw, and then Ibn Quhafa (Abu Bakr) took the bucket from me and drew one or two buckets, and there was weakness in his drawingâ-may Allah forgive him! Then `Umar took the bucket which turned into something like a big drum. I had never seen a powerful man among the people working as perfectly and vigorously as he did. (He drew so much water t
Grade: Sahih

Hadith #7191 - Sahih al-Bukhari - Abu Musa al-Asha'ari (Sahih al-Bukhari)
Whenever a beggar or a person in need of something came to the Prophet (ï·º) , he used to say (to his companions), âIntercede (for him) and you will be rewarded for that, and Allah will fulfill what He will through His Apostleâs tongue.â
Grade: Sahih

Hadith #7192 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
The Prophet (ï·º) said, âNone of you should say: âO Allah! Forgive me if You wish,â or âBestow Your Mercy on me if You wish,â or âProvide me with means of subsistence if You wish,â but he should be firm in his request, for Allah does what He will and nobody can force Him (to do anything).
Grade: Sahih

Hadith #7193 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
That he differed with Al-Hurr bin Qais bin Hisn Al-Fazari about the companion of Moses, (i.e., whether he was Kha,dir or not). Ubai bin Ka`b Al-Ansari passed by them and Ibn `Abbas called him saying, âMy friend (Hur) and I have differed about Mosesâ Companion whom Moses asked the way to meet. Did you hear Allahâs Messenger (ï·º) mentioning anything about him?â Ubai said, âYes, I heard Allahâs Apostle saying, âWhile Moses was sitting in the company of some Israelites a man came to h
Grade: Sahih

Hadith #7194 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âIf Allah wills, tomorrow we will encamp in Khaif Bani Kinana, the place where the pagans took the oath of Kufr (disbelief) against the Prophet. He meant Al-Muhassab. (See Hadith 1589)
Grade: Sahih

Hadith #7195 - Sahih al-Bukhari - ibn Umar (Sahih al-Bukhari)
The Prophet (ï·º) besieged the people of Taâif, but he did not conquer it. He said, âTomorrow, if Allah will, we will return home. On this the Muslims said, âThen we return without conquering it?â He said, âThen carry on fighting tomorrow.â The next day many of them were injured. The Prophet (ï·º) said, âIf Allah will, we will return home tomorrow.â It seemed that statement pleased them whereupon Allahâs Apostle smiled.
Grade: Sahih

Hadith #7196 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
The Prophet (ï·º) said, âWhen Allah ordains something on the Heaven the angels beat with their wings in obedience to His Statement which sounds like that of a chain dragged over a rock. His Statement: âUntil when the fear is banished from their hearts, the Angels say, âWhat was it that your Lord said?â âThey reply, â(He has said) the Truth. And He is the Most High, The Great. â (34.23)
Grade: Sahih

Hadith #7197 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âAllah never listens to anything as He listens to the Prophet (ï·º) reciting Qurâan in a pleasant sweet sounding voice.â A companion of Abu Huraira said, âHe means, reciting the Qurâan aloud.â
Grade: Sahih

Hadith #7198 - Sahih al-Bukhari - Abu Sa'id al-Khudri (Sahih al-Bukhari)
The Prophet (ï·º) said, âAllah will say (on the Day of Resurrection), âO Adam!â Adam will reply, âLabbaik wa Sa`daik! â Then a loud Voice will be heard (Saying) âAllah Commands you to take out the mission of the Hell Fire from your offspring.â â
Grade: Sahih

Hadith #7199 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
I never felt so jealous of any woman as I felt of Khadija, for Allah ordered him (the Prophet (ï·º) ) to give Khadija the glad tidings of a palace in Paradise (for her).
Grade: Sahih

Hadith #7200 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âIf Allah loves a person, He calls Gabriel, saying, âAllah loves so and so, O Gabriel love himâ So Gabriel would love him and then would make an announcement in the Heavens: âAllah has loved so and-so therefore you should love him also.â So all the dwellers of the Heavens would love him, and then he is granted the pleasure of the people on the earth.â (See Hadith No. 66, Vol. 8)
Grade: Sahih

Hadith #7201 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âThere are angels coming to you in succession at night, and others during the day, and they all gather at the time of `Asr and Fajr prayers. Then the angels who have stayed with you overnight ascend (to the heaven) and He (Allah) asks them though He perfectly knows their affairs. âIn what state have you left my slaves?â They say, âWhen we left them, they were praying and when we came to them they were praying.â â
Grade: Sahih

Hadith #7202 - Sahih al-Bukhari - Abu Dharr al-Ghaffari (Sahih al-Bukhari)
The Prophet (ï·º) said, Gabriel came to me and gave me the glad tidings that anyone who died without worshipping anything besides Allah, would enter Paradise. I asked (Gabriel), âEven if he committed theft, and even if he committed illegal sexual intercourse?â He said, â(Yes), even if he committed theft, and even if he Committed illegal sexual intercourse.â
Grade: Sahih

Hadith #7203 - Sahih al-Bukhari - al-Bara' bin Azib bin al-Harith (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âO so-and-so, whenever you go to your bed (for sleeping) say, âO Allah! I have surrendered myself over to you and have turned my face towards You, and leave all my affairs to You and depend on You and put my trust in You expecting Your reward and fearing Your punishment. There is neither fleeing from You nor refuge but with You. I believe in the Book (Qurâan) which You have revealed and in Your Prophet (Muhammad) whom You have sent.â If you then die on tha
Grade: Sahih

Hadith #7204 - Sahih al-Bukhari - Abdullah bin (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said on the Day of (the battle of) the Clans, âO Allah! The Revealer of the Holy Book, The Quick Taker of Accounts! Defeat the clans and shake them.â
Grade: Sahih

Hadith #7205 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
(regarding the Verse):â âNeither say your prayer aloud, nor say it in a low tone.â (17.110) This Verse was revealed while Allahâs Messenger (ï·º) was hiding himself in Mecca, and when he raised his voice while reciting the Qurâan, the pagans would hear him and abuse the Qurâan and its Revealer and to the one who brought it. So Allah said:â âNeither say your prayer aloud, nor say it in a low tone.â (17.110) That is, âDo not say your prayer so loudly that the pagans can hear yo
Grade: Sahih

Hadith #7206 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
The Prophet (ï·º) said, âAllah said: âThe son of Adam hurts Me by abusing Time, for I am Time; in My Hands are all things and I cause the revolution of night and day.â â (See Hadith No. 351, Vol. 6)
Grade: Sahih

Hadith #7207 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
The Prophet (ï·º) said, âAllah said: The Fast is for Me and I will give the reward for it, as he (the one who observes the fast) leaves his sexual desire, food and drink for My Sake. Fasting is a screen (from Hell) and there are two pleasures for a fasting person, one at the time of breaking his fast, and the other at the time when he will meet his Lord. And the smell of the mouth of a fasting person is better in Allahâs Sight than the smell of musk.â (See Hadith No. 128, Vol. 3).
Grade: Sahih

Hadith #7208 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
The Prophet (ï·º) said, âOnce while Job (Aiyub) was taking a bath in a naked state. Suddenly a great number of gold locusts started falling upon him and he started collecting them in his clothes. His Lord called him, âO Job! Didnât I make you rich enough to dispense with what you see now?â Job said, âYes, O Lord! But I cannot dispense with Your Blessings.â
Grade: Sahih

Hadith #7209 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âEvery night when it is the last third of the night, our Lord, the Superior, the Blessed, descends to the nearest heaven and says: Is there anyone to invoke Me that I may respond to his invocation? Is there anyone to ask Me so that I may grant him his request? Is there anyone asking My forgiveness so that I may forgive him?. â (See Hadith No. 246,Vol. 2)
Grade: Sahih

Hadith #7210 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âWe (Muslims) are the last (to come) but will be the foremost on the Day of Resurrection.â The narrators of this Hadith said: Allah said (to man), âSpend (in charity), for then I will compensate you (generously).â â
Grade: Sahih

Hadith #7211 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
The Prophet (ï·º) said that Gabriel said, âHere is Khadija coming to you with a dish of food or a tumbler containing something to drink. Convey to her a greeting from her Lord (Allah) and give her the glad tidings that she will have a palace in Paradise built of Qasab wherein there will be neither any noise nor any fatigue (trouble).â (See Hadith No. 168, Vol. 5)
Grade: Sahih

Hadith #7212 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
the Prophet (ï·º) said, âAllah said, âI have prepared for My righteous slaves (such excellent things) as no eye has ever seen, nor an ear has ever heard nor a human heart can ever think of.â â
Grade: Sahih

Hadith #7213 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
Whenever the Prophet (ï·º) offered the night (Tahajjud) prayer, he used to say, âO Allah! All the Praises are for You; You are the Light of the Heavens and the Earth. And all the Praises are for You; You are the Keeper of the Heavens and the Earth. All the Praises are for You; You are the Lord of the Heavens and the Earth and whatever is therein. You are the Truth, and Your Promise is the Truth, and Your Speech is the Truth, and meeting You is the Truth, and Paradise is the Truth and Hell (Fir
Grade: Sahih

Hadith #7214 - Sahih al-Bukhari - Urwa bin 'Abdullah Ø¹Ø±ÙØ© Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù ÙØ´ÙØ± (Sahih al-Bukhari)
Sa`id bin Al-Musaiyab, âAlqama bin Waqqas and âUbaidullah bin `Abdullah regarding the narrating of the forged statement against `Aisha, the wife of the Prophet, when the slanderers said what they said and Allah revealed her innocence. `Aisha said, âBut by Allah, I did not think that Allah, (to confirm my innocence), would reveal Divine Inspiration which would be recited, for I consider myself too unimportant to be talked about by Allah through Divine Inspiration revealed for recitation, bu
Grade: Sahih

Hadith #7215 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âAllah says, âIf My slave intends to do a bad deed then (O Angels) do not write it unless he does it; if he does it, then write it as it is, but if he refrains from doing it for My Sake, then write it as a good deed (in his account). (On the other hand) if he intends to do a good deed, but does not do it, then write a good deed (in his account), and if he does it, then write it for him (in his account) as ten good deeds up to seven-hundred times.â â
Grade: Sahih

Hadith #7216 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âAllah created the creation, and when He finished from His creation the Rahm (womb) got up, and Allah said (to it). âStop! What do you want? It said; âAt this place I seek refuge with You from all those who sever me (i.e. sever the ties of Kinship.)â Allah said: âWould you be pleased that I will keep good relation with the one who will keep good relation with you, and I will sever the relation with the one who will sever the relation with you. It said: â
Grade: Sahih

Hadith #7217 - Sahih al-Bukhari - Zaid bin Asim Mazni (Sahih al-Bukhari)
It rained (because of the Prophetâs invocation for rain) and the Prophet (ï·º) said, âAllah said, âSome of My slaves have become disbelievers in Me, and some others, believers in Me.'â
Grade: Sahih

Hadith #7218 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âAllah said, âIf My slaves loves the meeting with Me, I too love the meeting with him; and if he dislikes the meeting with Me, I too dislike the meeting with him.â â (See Hadith No. 514, Vol. 8)
Grade: Sahih

Hadith #7219 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âAllah said, âI am to my slave as he thinks of Me, (i.e. I am able to do for him what he thinks I can do for him). (See Hadith No. 502)
Grade: Sahih

Hadith #7220 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âA man who never did any good deed, said that if he died, his family should burn him and throw half the ashes of his burnt body in the earth and the other half in the sea, for by Allah, if Allah should get hold of him, He would inflict such punishment on him as He would not inflict on anybody among the people. But Allah ordered the sea to collect what was in it (of his ashes) and similarly ordered the earth to collect what was in it (of his ashes). Then Allah sa
Grade: Sahih

Hadith #7221 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
I heard the Prophet (ï·º) saying, âIf somebody commits a sin and then says, âO my Lord! I have sinned, please forgive me!â and his Lord says, âMy slave has known that he has a Lord who forgives sins and punishes for it, I therefore have forgiven my slave (his sins).â Then he remains without committing any sin for a while and then again commits another sin and says, âO my Lord, I have committed another sin, please forgive me,â and Allah says, âMy slave has known that he has a Lord
Grade: Sahih

Hadith #7222 - Sahih al-Bukhari - Abu Sa'id al-Khudri (Sahih al-Bukhari)
The Prophet (ï·º) mentioned a man from the people of the past or those who preceded you. The Prophet (ï·º) said a sentence meaning: Allah had given him wealth and children. When his death approached, he said to his sons, âWhat kind of father have I been to you?â They replied, âYou have been a good father.â He told them that he had not presented any good deed before Allah, and if Allah should get hold of him He would punish him.â âSo look!â he added, âWhen I die, burn me, and when
Grade: Sahih

Hadith #7223 - Sahih al-Bukhari - Anas ibn Malik (Sahih al-Bukhari)
I heard the Prophet (ï·º) saying, âOn the Day of Resurrection I will intercede and say, âO my Lord! Admit into Paradise (even) those who have faith equal to a mustard seed in their hearts.â Such people will enter Paradise, and then I will say, âO (Allah) admit into Paradise (even) those who have the least amount of faith in their hearts.â Anas then said: As if I were just now looking at the fingers of Allahâs Apostle.
Grade: Sahih

Hadith #7224 - Sahih al-Bukhari - Ma'bad bin Khalid al-Jadli ÙØ¹Ø¨Ø¯ Ø¨Ù Ø®Ø§ÙØ¯ Ø§ÙØ¬Ø¯ÙÙ (Sahih al-Bukhari)
We, i.e., some people from Basra gathered and went to Anas bin Malik, and we went in company with Thabit Al-Bunnani so that he might ask him about the Hadith of Intercession on our behalf. Behold, Anas was in his palace, and our arrival coincided with his Duha prayer. We asked permission to enter and he admitted us while he was sitting on his bed. We said to Thabit, âDo not ask him about anything else first but the Hadith of Intercession.â He said, âO Abu Hamza! There are your brethren fro
Grade: Sahih

Hadith #7225 - Sahih al-Bukhari - Abdullah bin (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âThe person who will be the last one to enter Paradise and the last to come out of Hell (Fire) will be a man who will come out crawling, and his Lord will say to him, âEnter Paradise.â He will reply, âO Lord, Paradise is full.â Allah will give him the same order thrice, and each time the man will give Him the same reply, i.e., âParadise is full.â Thereupon Allah will say (to him), âTen times of the world is for you.â â
Grade: Sahih

Hadith #7226 - Sahih al-Bukhari - Adi ibn Hatim al-Tayyi' (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âThere will be none among you but his Lord will talk to him, and there will be no interpreter between him and Allah. He will look to his right and see nothing but his deeds which he has sent forward, and will look to his left and see nothing but his deeds which he has sent forward, and will look in front of him and see nothing but the (Hell) Fire facing him. So save yourself from the (Hell) Fire even with half a date (given in charity).â Al-A`mash said: `Amr b
Grade: Sahih

Hadith #7227 - Sahih al-Bukhari - Abdullah bin (Sahih al-Bukhari)
A priest from the Jews came (to the Prophet) and said, âOn the Day of Resurrection, Allah will place all the heavens on one finger, and the Earth on one finger, and the waters and the land on one finger, and all the creation on one finger, and then He will shake them and say. âI am the King! I am the King!'â I saw the Prophet (ï·º) smiling till his premolar teeth became visible expressing his amazement and his belief in what he had said. Then the Prophet (ï·º) recited: âNo just estimate
Grade: Sahih

Hadith #7228 - Sahih al-Bukhari - Safwan bin 'Abdullah ØµÙÙØ§Ù Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù ØµÙÙØ§Ù Ø¨Ù Ø£ÙÙØ© (Sahih al-Bukhari)
A man asked Ibn `Umar, âWhat have you heard from Allahâs Messenger (ï·º) regarding An-Najwa?â He said, âEveryone of you will come close to His Lord Who will screen him from the people and say to him, âDid you do so-and-so?â He will reply, âYes.â Then Allah will say, âDid you do so-and-so?â He will reply, âYes.â So Allah will question him and make him confess, and then Allah will say, âI screened your sins in the world and forgive them for you today.â â
Grade: Sahih

Hadith #7229 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
The Prophet (ï·º) said, âAdam and Moses debated with each other and Moses said, âYou are Adam who turned out your offspring from Paradise.â Adam said, âYou are Moses whom Allah chose for His Message and for His direct talk, yet you blame me for a matter which had been ordained for me even before my creation?â Thus Adam overcame Moses.â
Grade: Sahih

Hadith #7230 - Sahih al-Bukhari - Anas ibn Malik (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âThe believers will be assembled on the Day of Resurrection and they will say, âLet us look for someone to intercede for us with our Lord so that He may relieve us from this place of ours.â So they will go to Adam and say, âYou are Adam, the father of mankind, and Allah created you with His Own Hands and ordered the Angels to prostrate before you, and He taught you the names of all things; so please intercede for us with our Lord so that He may relieve us.
Grade: Sahih

Hadith #7231 - Sahih al-Bukhari - Anas ibn Malik (Sahih al-Bukhari)
The night Allahâs Messenger (ï·º) was taken for a journey from the sacred mosque (of Mecca) Al-Ka`ba: Three persons came to him (in a dreamy while he was sleeping in the Sacred Mosque before the Divine Inspiration was revealed to Him. One of them said, âWhich of them is he?â The middle (second) angel said, âHe is the best of them.â The last (third) angle said, âTake the best of them.â Only that much happened on that night and he did not see them till they came on another night, i.e
Grade: Sahih

Hadith #7232 - Sahih al-Bukhari - Abu Sa'id al-Khudri (Sahih al-Bukhari)
The Prophet (ï·º) said, âAllah will say to the people of Paradise, âO the people of Paradise!â They will say, âLabbaik, O our Lord, and Sa`daik, and all the good is in Your Hands!â Allah will say, âAre you satisfied?â They will say, âWhy shouldnât we be satisfied, O our Lord as You have given us what You have not given to any of Your created beings?â He will say, âShall I not give you something better than that?â They will say, âO our Lord! What else could be better tha
Grade: Sahih

Hadith #7233 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
Once the Prophet (ï·º) was preaching while a bedouin was sitting there. The Prophet (ï·º) said, âA man from among the people of Paradise will request Allah to allow him to cultivate the land Allah will say to him, âHavenât you got whatever you desire?â He will reply, âyes, but I like to cultivate the land (Allah will permit him and) he will sow the seeds, and within seconds the plants will grow and ripen and (the yield) will be harvested and piled in heaps like mountains. On that Allah
Grade: Sahih

Hadith #7234 - Sahih al-Bukhari - Abdullah bin (Sahih al-Bukhari)
I asked Allahâs Messenger (ï·º) âWhat is the biggest sin in the sight of Allah?â He said, âTo set up rivals unto Allah though He alone created you.â I said, âIn fact, that is a tremendous sin,â and added, âWhat next?â He said, âTo kill your son being afraid that he may share your food with you.â I further asked, âWhat next?â He said, âTo commit illegal sexual intercourse with the wife of your neighbor.â
Grade: Sahih

Hadith #7235 - Sahih al-Bukhari - Abdullah bin (Sahih al-Bukhari)
Two person of Bani Thaqif and one from Quarish (or two persons from Quraish and one from Bani Thaqif) who had fat bellies but little wisdom, met near the Ka`ba. One of them said, âDid you see that Allah hears what we say? â The other said, âHe hears us if we speak aloud, but He does not hear if we speak in stealthy quietness (softly).â The third fellow said, âIf He hears when we speak aloud, then He surely hears us if we speak in stealthy quietness (softly).â So Allah revealed the Ve
Grade: Sahih

Hadith #7236 - Sahih al-Bukhari - `Ikrima bin Khalid (Sahih al-Bukhari)
Ibn `Abbas said, âHow can you ask the people of the Scriptures about their Books while you have Allahâs Book (the Qurâan) which is the most recent of the Books revealed by Allah, and you read it in its pure undistorted form?â
Grade: Sahih

Hadith #7237 - Sahih al-Bukhari - Ubaidullah bin 'Abdullah bin 'Umar Ø¹Ø¨ÙØ¯ Ø§ÙÙÙ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø¹ÙØ± Ø¨Ù Ø§ÙØ®Ø·Ø§Ø¨ (Sahih al-Bukhari)
`Abdullah bin `Abbas said, âO the group of Muslims! How can you ask the people of the Scriptures about anything while your Book which Allah has revealed to your Prophet contains the most recent news from Allah and is pure and not distorted? Allah has told you that the people of the Scriptures have changed some of Allahâs Books and distorted it and wrote something with their own hands and said, âThis is from Allah, so as to have a minor gain for it. Wonât the knowledge that has come to yo
Grade: Sahih

Hadith #7238 - Sahih al-Bukhari - Musa bin 'Abdullah ÙÙØ³Ù Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù ÙØ²ÙØ¯ (Sahih al-Bukhari)
Sa`id bin Jubair reported from Ibn `Abbas (regarding the explanation of the Verse: âDo not move your tongue concerning (the Qurâan) to make haste therewith) . He said, âThe Prophet (ï·º) used to undergo great difficulty in receiving the Divine Inspiration and used to move his lips.â Ibn `Abbas said (to Sa`id), âI move them (my lips) as Allahâs Messenger (ï·º) used to move his lips.â And Sa`id said (to me), âI move my lips as I saw Ibn `Abbas moving his lips,â and then he moved
Grade: Sahih

Hadith #7239 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
regarding the explanation of the Verse:â â(O Muhammad!) Neither say your prayer aloud, nor say it in a low tone.â (17.110) This Verse was revealed while Allahâs Messenger (ï·º) was hiding himself at Mecca. At that time, when he led his companions in prayer, he used to raise his voice while reciting the Qurâan; and if the pagans heard him, they would abuse the Qurâan, its Revealer, and the one who brought it. So Allah said to His Prophet: âNeither say your prayer aloud. i.e., your r
Grade: Sahih

Hadith #7240 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
The Verse:â â(O Muhammad!) Neither say your prayer aloud nor say it in a low tone.â (17.110) was revealed in connection with the invocations.
Grade: Sahih

Hadith #7241 - Sahih al-Bukhari - Abu Salama bin 'Abdur Rahman Ø£Ø¨Ù Ø³ÙÙØ© Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø¨Ù Ø¹ÙÙ (Sahih al-Bukhari)
Abu Huraira said, âAllahâs Messenger (ï·º) said, âWhoever does not recite Qurâan in a nice voice is not from us,â and others said extra,â (that means) to recite it aloud.â
Grade: Sahih

Hadith #7242 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âNot to wish to be the like of except the like of two men: a man whom Allah has given the Qurâan and he recites it during the hours of the night and the hours of the day, in which case one may say, âIf I were given the same as this man has been given, I would do the same as he is doing.â The other is a man whom Allah has given wealth and he spends it in the right way, in which case one may say, âIf I were given the same as he has been given, I would do t
Grade: Sahih

Hadith #7243 - Sahih al-Bukhari - Salim's father (Sahih al-Bukhari)
The Prophet (ï·º) said, âNot to wish to be the like of except the like of two (persons): a man whom Allah has given the knowledge of the Qurâan and he recites it during the hours of the night and the hours of the day; and a man whom Allah has given wealth and he spends it (in Allahâs Cause) during the hours of the night and during the hours of the day.â
Grade: Sahih

Hadith #7244 - Sahih al-Bukhari - al-Mughira bin 'Abdullah Ø§ÙÙØºÙØ±Ø© Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø¹ÙÙÙ (Sahih al-Bukhari)
Our Prophet has informed us our Lordâs Message that whoever of us is martyred, will go to Paradise.
Grade: Sahih

Hadith #7245 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
Whoever tells you that the Prophet (ï·º) concealed something of the Divine Inspiration, do not believe him, for Allah said: âO Apostle Muhammad! Proclaim (the Message) which has been sent down to you from your Lord, and if you do it not, then you have not conveyed His Message.â (5.67)
Grade: Sahih

Hadith #7246 - Sahih al-Bukhari - Abdullah bin (Sahih al-Bukhari)
A man said, âO Allahâs Messenger (ï·º)! Which sin is the biggest in Allahâs Sight?â The Prophet (ï·º) said, âTo set up rivals unto Allah though He Alone created you.â That man said, âWhat is next?â The Prophet (ï·º) said, âTo kill your son lest he should share your food with you.â The man said, âWhat is next?â The Prophet said, âTo commit illegal sexual intercourse with the wife of your neighbor.â Then Allah revealed in confirmation of that: âAnd those who invoke no
Grade: Sahih

Hadith #7247 - Sahih al-Bukhari - ibn Umar (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âYour stay (in this world) in comparison to the stay of the nations preceding you, is like the period between `Asr prayer and the sun set (in comparison to a whole day). The people of the Torah were given the Torah and they acted on it till midday and then they were unable to carry on. And they were given (a reward equal to) one Qirat each. Then the people of the Gospel were given the Gospel and they acted on it till `Asr Prayer and then they were unable to carr
Grade: Sahih

Hadith #7248 - Sahih al-Bukhari - ibn Mas'ud (Sahih al-Bukhari)
A man asked the Prophet (ï·º) âWhat deeds are the best?â The Prophet (ï·º) said: â(1) To perform the (daily compulsory) prayers at their (early) stated fixed times, (2) to be good and dutiful to oneâs own parents, (3) and to participate in Jihad in Allahâs Cause.â
Grade: Sahih

Hadith #7249 - Sahih al-Bukhari - al-Hasan al-Basri Ø§ÙØØ³Ù Ø§ÙØ¨ØµØ±Ù (Sahih al-Bukhari)
`Amr bin Taghlib said, âSome property was given to the Prophet (ï·º) and he gave it to some people and withheld it from some others. Then he came to know that they (the latter) were dissatisfied. So the Prophet said, âI give to one man and leave (do not give) another, and the one to whom I do not give is dearer to me than the one to whom I give. I give to some people because of the impatience and discontent present in their hearts, and leave other people because of the content and goodness A
Grade: Sahih

Hadith #7250 - Sahih al-Bukhari - Anas ibn Malik (Sahih al-Bukhari)
The Prophet (ï·º) said, âMy Lord says, âIf My slave comes nearer to me for a span, I go nearer to him for a cubit; and if he comes nearer to Me for a cubit, I go nearer to him for the span of outstretched arms; and if he comes to Me walking, I go to him running.â â
Grade: Sahih

Hadith #7251 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
Perhaps the Prophet (ï·º) mentioned the following (as Allahâs Saying): âIf My slave comes nearer to Me for a span, I go nearer to him for a cubit; and if he comes nearer to Me for a cubit; I go nearer to him for the span of outstretched arms. (See Hadith No. 502)
Grade: Sahih

Hadith #7252 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
The Prophet (ï·º) said that your Lord said, âEvery (sinful) deed can be expiated; and the fast is for Me, so I will give the reward for it; and the smell which comes out of the mouth of a fasting person, is better in Allahâs Sight than the smell of musk.â (See Hadith No. 584)
Grade: Sahih

Hadith #7253 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
The Prophet (ï·º) said that his Lord said: âIt does not befit a slave that he should say that he is better than Jonah (Yunus) bin Matta.
Grade: Sahih

Hadith #7254 - Sahih al-Bukhari - Shu'bah bin al-Hajjaj Ø´Ø¹Ø¨Ø© Ø¨Ù Ø§ÙØØ¬Ø§Ø¬ (Sahih al-Bukhari)
Muâawiya bin Qurra reported that `Abdullah bin Al-Maghaffal Al-Muzani said, âI saw Allahâs Messenger (ï·º) on the day of the Conquest of Mecca, riding his she-camel and reciting Surat-al-Fath (48) or part of Surat-al-Fath. He recited it in a vibrating and pleasant voice. Then Muâawiya recited as `Abdullah bin Mughaffal had done and said, âWere I not afraid that the people would crowd around me, I would surely recite in a vibrating pleasant voice as Ibn Mughaffal did, imitating the Prop
Grade: Sahih

Hadith #7255 - Sahih al-Bukhari - And Ibn 'Abbas (Sahih al-Bukhari)
Abu Sufyan bin Harb told me that Heraclius called for his translator and then asked for the letter of the Prophet (ï·º), and the former read it (thus): âIn the Name of Allah, the Most Gracious, the Merciful. (This letter is) from Muhammad bin âAbdullah, to Heraclius. ââ¦O people of the Scripture (Jews and Christians): Come to a word that is just between us and you that we worship none but Allahâ¦â (V.3:64)
Grade: Sahih

Hadith #7256 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
The people of the Scripture used to read the Torah in Hebrew and explain it to the Muslims in Arabic. Then Allahâs Messenger (ï·º) said, âDo not believe the people of the Scripture, and do not disbelieve them, but say, âWe believe in Allah and whatever has been revealedâ¦â (3.84)
Grade: Sahih

Hadith #7257 - Sahih al-Bukhari - ibn Umar (Sahih al-Bukhari)
A Jew and Jewess were brought to the Prophet (ï·º) on a charge of committing an illegal sexual intercourse. The Prophet (ï·º) asked the Jews, âWhat do you (usually) do with them?â They said, âWe blacken their faces and disgrace them.â He said, âBring here the Torah and recite it, if you are truthful.â They (fetched it and) came and asked a one-eyed man to recite. He went on reciting till he reached a portion on which he put his hand. The Prophet (ï·º) said, âLift up your hand!â H
Grade: Sahih

Hadith #7258 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
that he heard the Prophet (ï·º) saying, âAllah does not listen to anything as He listens to the recitation of the Qurâan by a Prophet who recites it in attractive audible sweet sounding voice.â
Grade: Sahih

Hadith #7259 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
(when the slanderers said what they said about her): I went to my bed knowing at that time that I was innocent and that Allah would reveal my innocence, but by Allah, I never thought that Allah would reveal in my favor a revelation which would be recited, for I considered myself too unimportant to be talked about by Allah in the Divine Revelation that was to be recited. So Allah revealed the ten Verses (of Surat-an-Nur). âThose who brought a false chargeâ¦â¦..â (24.11-20)
Grade: Sahih

Hadith #7260 - Sahih al-Bukhari - Al-Bara and 'Abdullah bin Abl 'Aufa (Sahih al-Bukhari)
I heard the Prophet (ï·º) reciting Surat at-Tin waz Zaitun (By the Fig and the Olive) in the `Ishaâ prayer and I have never heard anybody with a better voice or recitation than his.
Grade: Sahih

Hadith #7261 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
The Prophet (ï·º) was hiding himself in Mecca and used to recite the (Qurâan) in a loud voice. When the pagans heard him they would abuse the Qurâan and the one who brought it, so Allah said to His Prophet: âNeither say your prayer aloud, nor say it in a low tone.â (17.110)
Grade: Sahih

Hadith #7262 - Sahih al-Bukhari - Abdullah bin (Sahih al-Bukhari)
that Abu Sa`id Al-Khudri said to him, âI see that you like sheep and the desert, so when you are looking after your sheep or when you are in the desert and want to pronounce the Adhan, raise your voice, for no Jinn, human being or any other things hear the Mu`adh-dhinâs voice but will be a witness for him on the Day of Resurrection.â Abu Sa`id added, âI heard this from Allahâs Messenger (ï·º).â
Grade: Sahih

Hadith #7263 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
The Prophet (ï·º) used to recite the Qurâan with his head in my lap while I used to be in my periods (having menses).
Grade: Sahih

Hadith #7264 - Sahih al-Bukhari - Umar ibn al-Khattab (Sahih al-Bukhari)
I heard Hisham bin Hakim reciting Surat-al-Furqan during the lifetime of Allahâs Messenger (ï·º), I listened to his recitation and noticed that he was reciting in a way that Allahâs Messenger (ï·º) had not taught me. I was about to jump over him while He was still in prayer, but I waited patiently and when he finished his prayer, I put my sheet round his neck (and pulled him) and said, âWho has taught you this Sura which I have heard you reciting?â Hisham said, âAllahâs Messenger (ï·
Grade: Sahih

Hadith #7265 - Sahih al-Bukhari - Imran al-Barqy Ø¹ÙØ±Ø§Ù Ø§ÙØ¨Ø§Ø±ÙÙ (Sahih al-Bukhari)
I said, âO Allahâs Messenger (ï·º)! Why should a doer (people) try to do good deeds?â The Prophet (ï·º) said, âEverybody will find easy to do such deeds as will lead him to his destined place for which he has been created.â
Grade: Sahih

Hadith #7266 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
While the Prophet (ï·º) was in a funeral procession, he took a stick and started scraping the earth with it and said, âThere is none of you but has his place assigned either in Hell or in Paradise.â They (the people) said, âShall we not depend upon that (and give up doing any deeds)?â He said, â Carry on doing (good deeds) for everybody will find it easy to do such deeds as will lead him to his destined place for which he has been created .â (And then the Prophet (ï·º) recited the Ve
Grade: Sahih

Hadith #7267 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
I heard Allahâs Messenger (ï·º) saying, âBefore Allah created the creations, He wrote a Book (wherein He has written): My Mercy has preceded my Anger.â and that (Book) is written with Him over the Throne.â
Grade: Sahih

Hadith #7268 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
I heard Allahâs Messenger (ï·º) saying: âBefore Allah created the creations, He wrote a Book (wherein He has written): âMy Mercy has preceded my Anger.â And that is written with Him over the Throne.â (see Hadith 3194)
Grade: Sahih

Hadith #7269 - Sahih al-Bukhari - Zahdam al-Jarmi (Sahih al-Bukhari)
There were good relations and brotherhood between this tribe of Jurm and the Ash`ariyyin. Once, while we were sitting with Abu Musa Al-Ash`ari, there was brought to him a meal which contained chicken meat, and there was sitting beside him, a man from the tribe of Bani Taimul-lah who looked like one of the Mawali. Abu Musa invited the man to eat but the man said, âI have seen chicken eating some dirty things, and I have taken an oath not to eat chicken.â Abu Musa said to him, âCome along, l
Grade: Sahih

Hadith #7270 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
The delegates of `Abdul Qais came to Allahâs Messenger (ï·º) and said, âThe pagans of the tribe of Mudar intervene between you and us therefore we cannot come to you except in the Holy months. So please order us to do something good (Religious deeds) by which we may enter Paradise (by acting on them) and we may inform our people whom we have left behind to observe it.â The Prophet (ï·º) said, âI order you to do four things and forbid you from four things: I order you to believe in Allah.
Grade: Sahih

Hadith #7271 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âThe painter of these pictures will be punished on the Day of Resurrection, and it will be said to them, Make alive what you have created.â â
Grade: Sahih

Hadith #7272 - Sahih al-Bukhari - ibn Umar (Sahih al-Bukhari)
The Prophet (ï·º) said, âThe painters of these pictures will be punished on the Day of Resurrection, and it will be said to them, âMake alive what you have created.â
Grade: Sahih

Hadith #7273 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
I heard the Prophet (ï·º) saying, âAllah said, âWho are most unjust than those who try to create something like My creation? I challenge them to create even a smallest ant, a wheat grain or a barley grain.â â
Grade: Sahih

Hadith #7274 - Sahih al-Bukhari - Abu Musa al-Asha'ari (Sahih al-Bukhari)
The Prophet (ï·º) said, âThe example of a believer who recites the Qurâan is that of a citron (a citrus fruit) which is good in taste and good in smell. And the believer who does not recite the Qurâan is like a date which has a good taste but no smell. And the example of an impious person who recites the Qurâan is that of Ar-Rihana (an aromatic plant) which smells good but is bitter in taste. And the example of an impious person who does not recite the Qurâan is that of a colocynth whi
Grade: Sahih

Hadith #7275 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
Some people asked the Prophet (ï·º) regarding the soothsayers. He said, âThey are nothing.â They said, âO Allahâs Messenger (ï·º)! Some of their talks come true.â The Prophet (ï·º) said, âThat word which happens to be true is what a Jinn snatches away by stealth (from the Heaven) and pours it in the ears of his friend (the foreteller) with a sound like the cackling of a hen. The soothsayers then mix with that word, one hundred lies.â
Grade: Sahih

Hadith #7276 - Sahih al-Bukhari - Abu Sa'id al-Khudri (Sahih al-Bukhari)
The Prophet (ï·º) said, âThere will emerge from the East some people who will recite the Qurâan but it will not exceed their throats and who will go out of (renounce) the religion (Islam) as an arrow passes through the game, and they will never come back to it unless the arrow, comes back to the middle of the bow (by itself) (i.e., impossible). The people asked, âWhat will their signs be?â He said, âTheir sign will be the habit of shaving (of their beards and their heads). (Fath-ul-Bar
Grade: Sahih

Hadith #7277 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
The Prophet (ï·º) said, â(There are) two words which are dear to the Beneficent (Allah) and very light (easy) for the tongue (to say), but very heavy in weight in the balance. They are: âSubhan Allah wa-bi hamdihiâ and âSubhan Allah Al-`Azim.â (see Hadith 6682).
Grade: Sahih

Hadith #7371 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) sent Muâadh to Yemen. Ø¨ÙØ¹ÙØ«Ù ÙÙØ¹ÙØ§Ø°ÙØ§ Ø¥ÙÙÙÙ Ø§ÙÙÙÙÙÙÙÙâ.â
Grade:

Hadith #7372 - Sahih al-Bukhari (Sahih al-Bukhari)
When the Prophet (ï·º) sent Mu`adh to Yemen, he said to him, âYou are going to a nation from the people of the Scripture, so let the first thing to which you will invite them, be the Tauhid of Allah. If they learn that, tell them that Allah has enjoined on them, five prayers to be offered in one day and one night. And if they pray, tell them that Allah has enjoined on them Zakat of their properties and it is to be taken from the rich among them and given to the poor. And if they agree to that,
Grade:

Hadith #7373 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) said, âO Mu`adh! Do you know what Allahâs Right upon His slaves is?â I said, âAllah and His Apostle know best.â The Prophet (ï·º) said, âTo worship Him (Allah) Alone and to join none in worship with Him (Allah). Do you know what their right upon Him is?â I replied, âAllah and His Apostle know best.â The Prophet (ï·º) said, âNot to punish them (if they do so). Ø£ÙØªÙØ¯ÙØ±ÙÙ ÙÙØ§ ØÙÙÙÙ Ø§ÙÙÙÙÙÙ Ø¹ÙÙÙÙ Ø§ÙÙØ¹ÙØ¨ÙØ§Ø¯Ù ââââ.â
Grade:

Hadith #7374 - Sahih al-Bukhari (Sahih al-Bukhari)
A man heard another man reciting (in the prayers): âSay (O Muhammad): âHe is Allah, the One.â (112.1) And he recited it repeatedly. When it was morning, he went to the Prophet (ï·º) and informed him about that as if he considered that the recitation of that Sura by itself was not enough. Allahâs Messenger (ï·º) said, âBy Him in Whose Hand my life is, it is equal to one-third of the Qurâan.â Ø¥ÙÙÙÙÙÙØ§ ÙÙØªÙØ¹ÙØ¯ÙÙÙ Ø«ÙÙÙØ«Ù Ø§ÙÙÙÙØ±ÙØ¢ÙÙ ââ
Grade:

Hadith #7375 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) sent (an army unit) under the command of a man who used to lead his companions in the prayers and would finish his recitation with (the Sura 112): âSay (O Muhammad): âHe is Allah, the One.â â (112.1) When they returned (from the battle), they mentioned that to the Prophet. He said (to them), âAsk him why he does so.â They asked him and he said, âI do so because it mentions the qualities of the Beneficent and I love to recite it (in my prayer).â The Prophet; said
Grade:

Hadith #7376 - Sahih al-Bukhari (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âAllah will not be merciful to those who are not merciful to mankind.â ÙØ§Ù ÙÙØ±ÙØÙÙÙ Ø§ÙÙÙÙÙÙ ÙÙÙÙ ÙØ§Ù ÙÙØ±ÙØÙÙÙ Ø§ÙÙÙÙØ§Ø³Ù ââ
Grade:

Hadith #7377 - Sahih al-Bukhari (Sahih al-Bukhari)
We were with the Prophet (ï·º) when suddenly there came to him a messenger from one of his daughters who was asking him to come and see her son who was dying. The Prophet (ï·º) said (to the messenger), âGo back and tell her that whatever Allah takes is His, and whatever He gives is His, and everything with Him has a limited fixed term (in this world). So order her to be patient and hope for Allahâs reward.â But she sent the messenger to the Prophet (ï·º) again, swearing that he should come
Grade:

Hadith #7378 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) said, âNone is more patient than Allah against the harmful and annoying words He hears (from the people): They ascribe children to Him, yet He bestows upon them health and provision . ÙÙØ§ Ø£ÙØÙØ¯Ù Ø£ÙØµÙØ¨ÙØ±Ù Ø¹ÙÙÙÙ Ø£ÙØ°ÙÙ Ø³ÙÙÙØ¹ÙÙÙ ÙÙÙÙ Ø§ÙÙÙÙÙÙØ ÙÙØ¯ÙÙØ¹ÙÙÙÙ ÙÙÙÙ Ø§ÙÙÙÙÙÙØ¯ÙØ Ø«ÙÙÙÙ ÙÙØ¹ÙØ§ÙÙÙÙÙÙÙ ÙÙÙÙØ±ÙØ²ÙÙÙÙÙÙÙ ââ
Grade:

Hadith #7379 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) said, âThe keys of the unseen are five and none knows them but Allah: (1) None knows (the sex) what is in the womb, but Allah: (2) None knows what will happen tomorrow, but Allah; (3) None knows when it will rain, but Allah; (4) None knows where he will die, but Allah (knows that); (5) and none knows when the Hour will be established, but Allah.â ÙÙÙÙØ§ØªÙÙØÙ Ø§ÙÙØºÙÙÙØ¨Ù Ø®ÙÙÙØ³Ù ÙØ§Ù ÙÙØ¹ÙÙÙÙÙÙÙØ§ Ø¥ÙÙØ§ÙÙ Ø§ÙÙÙÙÙÙØ ÙØ§Ù ÙÙØ¹ÙÙ
Grade:

Hadith #7380 - Sahih al-Bukhari (Sahih al-Bukhari)
`Aisha said, âIf anyone tells you that Muhammad has seen his Lord, he is a liar, for Allah says: âNo vision can grasp Him.â (6.103) And if anyone tells you that Muhammad has seen the Unseen, he is a liar, for Allah says: âNone has the knowledge of the Unseen but Allah.â ÙÙÙÙ ØÙØ¯ÙÙØ«ÙÙÙ Ø£ÙÙÙÙ ÙÙØÙÙÙÙØ¯ÙØ§ ØµÙÙ Ø§ÙÙÙ Ø¹ÙÙÙ ÙØ³ÙÙ Ø±ÙØ£ÙÙ Ø±ÙØ¨ÙÙÙÙ ÙÙÙÙØ¯Ù ÙÙØ°ÙØ¨Ù ÙÙÙÙÙÙ ÙÙÙÙÙÙÙ ââ{âÙØ§Ù ØªÙØ¯ÙØ±ÙÙÙÙÙ Ø§ÙØ£Ù
Grade:

Hadith #7381 - Sahih al-Bukhari (Sahih al-Bukhari)
We used to pray behind the Prophet (ï·º) and used to say: âAs-Salamu âAl-Allah. The Prophet (ï·º) said, âAllah himself is As-Salam (Name of Allah), so you should say: âat-Tahiyatu lil-lahi was-sala-watu wattaiyibatu, as-salamu `alaika aiyyuha-n-nabiyyu wa rahmatu-l-lahi wa barakatuhu, as-salamu `alaina wa `ala `ibadi-l-lahi as-salihin. Ashhadu an la ilaha il-lallah, wa ash-hadu anna Muhammadan `abduhu wa rasuluhu.ââ Ø¥ÙÙÙÙ Ø§ÙÙÙÙÙÙ ÙÙÙÙ Ø§ÙØ³ÙÙÙØ§ÙÙÙ ÙÙÙÙÙÙ
Grade:

Hadith #7382 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) said, âOn the Day of Resurrection Allah will hold the whole earth and fold the heaven with His right hand and say, âI am the King: where are the kings of the earth?â â ÙÙÙÙØ¨ÙØ¶Ù Ø§ÙÙÙÙÙÙ Ø§ÙØ£ÙØ±ÙØ¶Ù ÙÙÙÙÙÙ Ø§ÙÙÙÙÙÙØ§ÙÙØ©ÙØ ÙÙÙÙØ·ÙÙÙÙ Ø§ÙØ³ÙÙÙÙØ§Ø¡Ù Ø¨ÙÙÙÙÙÙÙÙÙÙ Ø«ÙÙÙÙ ÙÙÙÙÙÙÙ Ø£ÙÙÙØ§ Ø§ÙÙÙÙÙÙÙÙ Ø£ÙÙÙÙÙ ÙÙÙÙÙÙÙ Ø§ÙØ£ÙØ±ÙØ¶Ù ââ
Grade:

Hadith #7383 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) used to say, âI seek refuge (with YOU) by Your âIzzat, None has the right to be worshipped but You Who does not die while the Jinns and the human beings die.â Ø£ÙØ¹ÙÙØ°Ù Ø¨ÙØ¹ÙØ²ÙÙØªÙÙÙ Ø§ÙÙÙØ°ÙÙ ÙØ§Ù Ø¥ÙÙÙÙÙ Ø¥ÙÙØ§ÙÙ Ø£ÙÙÙØªÙØ Ø§ÙÙÙØ°ÙÙ ÙØ§Ù ÙÙÙÙÙØªÙ ÙÙØ§ÙÙØ¬ÙÙÙÙ ÙÙØ§ÙØ¥ÙÙÙØ³Ù ÙÙÙÙÙØªÙÙÙÙ ââ
Grade:

Hadith #7384 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) said, â(The people will be thrown into Hell ( Fire) and it will keep on saying, âIs there any more?â till the Lord of the worlds puts His Foot over it, whereupon its different sides will come close to each other, and it will say, âQad! Qad! (enough! enough!) By Your âIzzat (Honor and Power) and YOUR KARAM (Generosity)!â Paradise will remain spacious enough to accommodate more people until Allah will create some more people and let them dwell in the superfluous space
Grade:

Hadith #7385 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) used to invoke Allah at night, saying, âO Allah: All the Praises are for You: You are the Lord of the Heavens and the Earth. All the Praises are for You; You are the Maintainer of the Heaven and the Earth and whatever is in them. All the Praises are for You; You are the Light of the Heavens and the Earth. Your Word is the Truth, and Your Promise is the Truth, and the Meeting with You is the Truth, and Paradise is the Truth, and the (Hell) Fire is the Truth, and the Hour is th
Grade:

Hadith #7386 - Sahih al-Bukhari (Sahih al-Bukhari)
We were with the Prophet (ï·º) on a journey, and whenever we ascended a high place, we used to say, âAllahu Akbar.â The Prophet (ï·º) said, âDonât trouble yourselves too much! You are not calling a deaf or an absent person, but you are calling One Who Hears, Sees, and is very near.â Then he came to me while I was saying in my heart, âLa hawla wala quwwatta illa billah (There is neither might nor power but with Allah).â He said, to me, âO `Abdullah bin Qais! Say, âLa hawla wala
Grade:

Hadith #7387 - Sahih al-Bukhari (Sahih al-Bukhari)
Abu Bakr As-Siddiq said to the Prophet (ï·º) âO Allahâs Messenger (ï·º)! Teach me an invocation with which I may invoke Allah in my prayers.â The Prophet (ï·º) said, âSay: O Allah! I have wronged my soul very much (oppressed myself), and none forgives the sins but You; so please bestow Your Forgiveness upon me. No doubt, You are the Oft-Forgiving, Most Merciful.â ÙÙÙÙ Ø§ÙÙÙÙÙÙÙÙÙ Ø¥ÙÙÙÙÙ Ø¸ÙÙÙÙÙØªÙ ÙÙÙÙØ³ÙÙ Ø¸ÙÙÙÙÙØ§ ÙÙØ«ÙÙØ±ÙØ§Ø ÙÙÙØ§Ù ÙÙ
Grade:

Hadith #7389 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) said, âGabriel called me and said, âAllah has heard the statement of your people and what they replied to you.'â Ø¥ÙÙÙÙ Ø¬ÙØ¨ÙØ±ÙÙÙÙ Ø¹ÙÙÙÙÙÙÙ Ø§ÙØ³ÙÙÙØ§ÙÙÙ ÙÙØ§Ø¯ÙØ§ÙÙÙ ÙÙØ§ÙÙ Ø¥ÙÙÙÙ Ø§ÙÙÙÙÙÙ ÙÙØ¯Ù Ø³ÙÙÙØ¹Ù ÙÙÙÙÙÙ ÙÙÙÙÙÙÙÙ ÙÙÙÙØ§ Ø±ÙØ¯ÙÙÙØ§ Ø¹ÙÙÙÙÙÙÙ ââ
Grade:

Hadith #7390 - Sahih al-Bukhari (Sahih al-Bukhari)
As-Salami: Allahâs Messenger (ï·º) used to teach his companions to perform the prayer of Istikhara for each and every matter just as he used to teach them the Suras from the Qurâan He used to say, âIf anyone of you intends to do some thing, he should offer a two rak`at prayer other than the compulsory prayers, and after finishing it, he should say: O Allah! I consult You, for You have all knowledge, and appeal to You to support me with Your Power and ask for Your Bounty, for You are able t
Grade:

Hadith #7391 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) frequently used to swear, âNo, by the One Who turns the hearts.â ÙÙØÙÙÙÙÙ âââ ÙØ§Ù ÙÙÙÙÙÙÙÙÙØ¨Ù Ø§ÙÙÙÙÙÙÙØ¨Ù ââ
Grade:

Hadith #7392 - Sahih al-Bukhari (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âAllah has ninety-nine Names, one-hundred less one; and he who memorized them all by heart will enter Paradise.â To count something means to know it by heart. Ø¥ÙÙÙÙ ÙÙÙÙÙÙÙ ØªÙØ³ÙØ¹ÙØ©Ù ÙÙØªÙØ³ÙØ¹ÙÙÙÙ Ø§Ø³ÙÙÙØ§ ÙÙØ§Ø¦ÙØ©Ù Ø¥ÙÙØ§ÙÙ ÙÙØ§ØÙØ¯ÙØ§Ø ÙÙÙÙ Ø£ÙØÙØµÙØ§ÙÙØ§ Ø¯ÙØ®ÙÙÙ Ø§ÙÙØ¬ÙÙÙÙØ©Ù ââ
Grade:

Hadith #7393 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) said, âWhen anyone of you goes to bed, he should dust it off thrice with the edge of his garment, and say: Bismika Rabbi Wada`tu janbi, wa bika arfaâhu. In amsakta nafsi faghfir laha, wa in arsaltaha fahfazha bima tahfaz bihi âibadaka-s-salihin.â Ø¥ÙØ°ÙØ§ Ø¬ÙØ§Ø¡Ù Ø£ÙØÙØ¯ÙÙÙÙÙ ÙÙØ±ÙØ§Ø´ÙÙÙ ÙÙÙÙÙÙÙÙÙÙØ¶ÙÙÙ Ø¨ÙØµÙÙÙÙÙØ©Ù Ø«ÙÙÙØ¨ÙÙÙ Ø«ÙÙØ§ÙØ«Ù ÙÙØ±ÙÙØ§ØªÙØ ÙÙÙÙÙÙÙÙÙÙ Ø¨ÙØ§Ø³ÙÙÙÙÙ Ø±ÙØ¨ÙÙ ÙÙØ¶ÙØ¹ÙØ
Grade:

Hadith #7394 - Sahih al-Bukhari (Sahih al-Bukhari)
When the Prophet (ï·º) went to bed, he used to say, âAllahumma bismika ahya wa amut.â And when he woke up in the mornings he used to say, âAl-hamdu li l-lahi al-ladhi ahyana baâda ma amatana wa ilaihi-nnushur.â Ø§ÙÙÙÙÙÙÙÙÙ Ø¨ÙØ§Ø³ÙÙÙÙÙ Ø£ÙØÙÙÙØ§ ÙÙØ£ÙÙÙÙØªÙ ââââ.â ÙÙØ¥ÙØ°ÙØ§ Ø£ÙØµÙØ¨ÙØÙ ÙÙØ§ÙÙ âââ Ø§ÙÙØÙÙÙØ¯Ù ÙÙÙÙÙÙÙ Ø§ÙÙÙØ°ÙÙ Ø£ÙØÙÙÙØ§ÙÙØ§ Ø¨ÙØ¹ÙØ¯Ù ÙÙØ§ Ø£ÙÙÙØ§ØªÙÙÙØ§ ÙÙØ¥ÙÙÙÙÙÙÙ Ø§Ù
Grade:

Hadith #7395 - Sahih al-Bukhari (Sahih al-Bukhari)
When the Prophet (ï·º) went to bed at night, he used to say: âBismika namutu wa nahya.â And when he got up in the morning, he used to say, âAl hamdu li l-lahi al-ladhi ahyana baâda ma amatana, wa ilaihi-nnushur.â Ø¥ÙØ°ÙØ§ Ø£ÙØ®ÙØ°Ù ÙÙØ¶ÙØ¬ÙØ¹ÙÙÙ ÙÙÙÙ Ø§ÙÙÙÙÙÙÙÙ ÙÙØ§ÙÙ âââ Ø¨ÙØ§Ø³ÙÙÙÙÙ ÙÙÙÙÙØªÙ ÙÙÙÙØÙÙÙØ§Ø ÙÙØ¥ÙØ°ÙØ§ Ø§Ø³ÙØªÙÙÙÙÙØ¸Ù ÙÙØ§ÙÙ Ø§ÙÙØÙÙÙØ¯Ù ÙÙÙÙÙÙÙ Ø§ÙÙÙØ°ÙÙ Ø£ÙØÙÙÙØ§ÙÙØ§ Ø¨ÙØ¹ÙØ
Grade:

Hadith #7396 - Sahih al-Bukhari (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âIf anyone of you, when intending to have a sexual relation (sleep) with his wife, says: Bismillah, Allahumma jannibna ashShaitan, wa Jannib ash-Shaitana ma razaqtana, Satan would never harm that child, should it be ordained that they will have one. (Because of that sleep). ÙÙÙÙ Ø£ÙÙÙÙ Ø£ÙØÙØ¯ÙÙÙÙÙ Ø¥ÙØ°ÙØ§ Ø£ÙØ±ÙØ§Ø¯Ù Ø£ÙÙÙ ÙÙØ£ÙØªÙÙÙ Ø£ÙÙÙÙÙÙÙ ÙÙÙÙØ§ÙÙ Ø¨ÙØ§Ø³ÙÙÙ Ø§ÙÙÙÙÙÙØ Ø§ÙÙÙÙÙÙÙÙÙ Ø¬ÙÙÙÙØ¨Ù
Grade:

Hadith #7397 - Sahih al-Bukhari (Sahih al-Bukhari)
I asked the Prophet, âI send off (for a game) my trained hunting dogs; (what is your verdict concerning the game they hunt?â He said, âIf you send off your trained hunting dogs and mention the Name of Allah, then, if they catch some game, eat (thereof). And if you hit the game with a miârad (a hunting tool) and it wounds it, you can eat (it). Ø¥ÙØ°ÙØ§ Ø£ÙØ±ÙØ³ÙÙÙØªÙ ÙÙÙØ§ÙØ¨ÙÙÙ Ø§ÙÙÙÙØ¹ÙÙÙÙÙÙØ©Ù ÙÙØ°ÙÙÙØ±ÙØªÙ Ø§Ø³ÙÙÙ Ø§ÙÙÙÙÙÙ ÙÙØ£ÙÙÙØ³ÙÙÙ
Grade:

Hadith #7398 - Sahih al-Bukhari (Sahih al-Bukhari)
The people said to the Prophet (ï·º) , âO Allahâs Messenger (ï·º)! Here are people who have recently embraced Islam and they bring meat, and we do not know whether they had mentioned Allahâs Name while slaughtering the animals or not.â The Prophet (ï·º) said, âYou should mention Allahâs Name and eat.â Ø§Ø°ÙÙÙØ±ÙÙØ§ Ø£ÙÙÙØªÙÙÙ Ø§Ø³ÙÙÙ Ø§ÙÙÙÙÙÙ ÙÙÙÙÙÙÙØ§ ââ
Grade:

Hadith #7399 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) slaughtered two rams as sacrifice and mentioned Allahâs Name and said, âAllahu-Akbarâ while slaughtering). Ø¶ÙØÙÙÙ Ø§ÙÙÙÙØ¨ÙÙÙÙ ØµÙÙ Ø§ÙÙÙ Ø¹ÙÙÙ ÙØ³ÙÙ Ø¨ÙÙÙØ¨ÙØ´ÙÙÙÙÙØ ÙÙØ³ÙÙÙÙÙ ÙÙÙÙÙÙØ¨ÙÙØ±Ùâ.â
Grade:

Hadith #7400 - Sahih al-Bukhari (Sahih al-Bukhari)
That he witnessed the Prophet (ï·º) on the Day of Nahr. The Prophet (ï·º) offered prayer and then delivered a sermon saying, âWhoever slaughtered his sacrifice before offering prayer, should slaughter another animal in place of the first; and whoever has not yet slaughtered any, should slaughter a sacrifice and mention Allahâs Name while doing so.â ÙÙÙÙ Ø°ÙØ¨ÙØÙ ÙÙØ¨ÙÙÙ Ø£ÙÙÙ ÙÙØµÙÙÙÙÙÙ ÙÙÙÙÙÙØ°ÙØ¨ÙØÙ ÙÙÙÙØ§ÙÙÙÙØ§ Ø£ÙØ®ÙØ±ÙÙØ ÙÙÙÙÙÙ ÙÙ
Grade:

Hadith #7401 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) said, âDo not swear by your fathers; and whoever wants to swear should swear by Allah.â ÙØ§Ù ØªÙØÙÙÙÙÙÙØ§ Ø¨ÙØ¢Ø¨ÙØ§Ø¦ÙÙÙÙÙØ ÙÙÙÙÙÙ ÙÙØ§ÙÙ ØÙØ§ÙÙÙÙØ§ ÙÙÙÙÙÙØÙÙÙÙÙ Ø¨ÙØ§ÙÙÙÙÙÙ ââ
Grade:

Hadith #7402 - Sahih al-Bukhari (Sahih al-Bukhari)
Allahâs Messenger (ï·º) sent ten persons to bring the enemyâs secrets and Khubaib Al-Ansari was one of them. âUbaidullah bin âIyad told me that the daughter of Al-Harith told him that when they gathered (to kill Khubaib Al Ansari) he asked for a razor to clean his pubic region, and when they had taken him outside the sanctuary of Mecca in order to kill him, he said in verse, âI donât care if I am killed as a Muslim, on any side (of my body) I may be killed in Allahâs Cause; for tha
Grade:

Hadith #7403 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) said, âThere is none having a greater sense of Ghira than Allah, and for that reason He has forbidden shameful deeds and sins (illegal sexual intercourse etc.) And there is none who likes to be praised more than Allah does.â (See Hadith No. 147, Vol. 7) ÙÙØ§ ÙÙÙÙ Ø£ÙØÙØ¯Ù Ø£ÙØºÙÙÙØ±Ù ÙÙÙÙ Ø§ÙÙÙÙÙÙØ ÙÙÙÙ Ø£ÙØ¬ÙÙÙ Ø°ÙÙÙÙÙ ØÙØ±ÙÙÙÙ Ø§ÙÙÙÙÙÙØ§ØÙØ´ÙØ ÙÙÙÙØ§ Ø£ÙØÙØ¯Ù Ø£ÙØÙØ¨ÙÙ Ø¥ÙÙÙÙÙÙÙ Ø§ÙÙÙÙØ¯ÙØÙ
Grade:

Hadith #7404 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) said, âWhen Allah created the Creation, He wrote in His Bookâand He wrote (that) about Himself, and it is placed with Him on the ThroneââVerily My Mercy overcomes My Anger.'â ÙÙÙÙÙØ§ Ø®ÙÙÙÙÙ Ø§ÙÙÙÙÙÙ Ø§ÙÙØ®ÙÙÙÙÙ ÙÙØªÙØ¨Ù ÙÙÙ ÙÙØªÙØ§Ø¨ÙÙÙ Ù ÙÙÙÙ ÙÙÙÙØªÙØ¨Ù Ø¹ÙÙÙÙ ÙÙÙÙØ³ÙÙÙØ ÙÙÙÙÙÙ ÙÙØ¶ÙØ¹Ù Ø¹ÙÙÙØ¯ÙÙÙ Ø¹ÙÙÙÙ Ø§ÙÙØ¹ÙØ±ÙØ´Ù Ù Ø¥ÙÙÙÙ Ø±ÙØÙÙÙØªÙÙ ØªÙØºÙÙÙØ¨Ù ØºÙØ¶ÙØ¨ÙÙ â
Grade:

Hadith #7405 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) said, âAllah says: âI am just as My slave thinks I am, (i.e. I am able to do for him what he thinks I can do for him) and I am with him if He remembers Me. If he remembers Me in himself, I too, remember him in Myself; and if he remembers Me in a group of people, I remember him in a group that is better than they; and if he comes one span nearer to Me, I go one cubit nearer to him; and if he comes one cubit nearer to Me, I go a distance of two outstretched arms nearer to him
Grade:

Hadith #7406 - Sahih al-Bukhari (Sahih al-Bukhari)
when this Verse:ââSay (O Muhammad!): He has Power to send torments on you from above,â (6.65) was revealed; The Prophet (ï·º) said, âI take refuge with Your Face.â Allah revealed:â â..or from underneath your feet.â (6.65) The Prophet (ï·º) then said, âI seek refuge with Your Face!â Then Allah revealed:âââ¦or confuse you in party-strife.â (6.65) Oh that, the Prophet (ï·º) said, âThis is easier.â Ø£ÙØ¹ÙÙØ°Ù Ø¨ÙÙÙØ¬ÙÙÙÙÙ ââââ.â ÙÙÙÙØ§ÙÙ â
Grade:

Hadith #7407 - Sahih al-Bukhari (Sahih al-Bukhari)
Ad-Dajjal was mentioned in the presence of the Prophet. The Prophet (ï·º) said, âAllah is not hidden from you; He is not one-eyed,â and pointed with his hand towards his eye, adding, âWhile Al-Masih Ad- Dajjal is blind in the right eye and his eye looks like a protruding grape.â Ø¥ÙÙÙÙ Ø§ÙÙÙÙÙÙ ÙØ§Ù ÙÙØ®ÙÙÙÙ Ø¹ÙÙÙÙÙÙÙÙÙØ Ø¥ÙÙÙÙ Ø§ÙÙÙÙÙÙ ÙÙÙÙØ³Ù Ø¨ÙØ£ÙØ¹ÙÙÙØ±Ù Ù ÙÙØ£ÙØ´ÙØ§Ø±Ù Ø¨ÙÙÙØ¯ÙÙÙ Ø¥ÙÙÙÙ Ø¹ÙÙÙÙÙÙÙ Ù ÙÙØ¥ÙÙÙ
Grade:

Hadith #7408 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) said, âAllah did not send any prophet but that he warned his nation of the one-eyed liar (Ad-Dajjal). He is one-eyed while your Lord is not one-eyed, The word âKafirâ (unbeliever) is written between his two eyes.â ÙÙØ§ Ø¨ÙØ¹ÙØ«Ù Ø§ÙÙÙÙÙÙ ÙÙÙÙ ÙÙØ¨ÙÙÙÙ Ø¥ÙÙØ§ÙÙ Ø£ÙÙÙØ°ÙØ±Ù ÙÙÙÙÙÙÙÙ Ø§ÙØ£ÙØ¹ÙÙÙØ±Ù Ø§ÙÙÙÙØ°ÙÙØ§Ø¨ÙØ Ø¥ÙÙÙÙÙÙ Ø£ÙØ¹ÙÙÙØ±ÙØ ÙÙØ¥ÙÙÙÙ Ø±ÙØ¨ÙÙÙÙÙÙ ÙÙÙÙØ³Ù Ø¨ÙØ£ÙØ¹ÙÙÙØ±ÙØ ÙÙ
Grade:

Hadith #7409 - Sahih al-Bukhari (Sahih al-Bukhari)
That during the battle with Bani Al-Mustaliq they (Muslims) captured some females and intended to have sexual relation with them without impregnating them. So they asked the Prophet (ï·º) about coitus interrupt us. The Prophet (ï·º) said, âIt is better that you should not do it, for Allah has written whom He is going to create till the Day of Resurrection.â Qazaâa said, âI heard Abu Sa`id saying that the Prophet (ï·º) said, âNo soul is ordained to be created but Allah will create it.â
Grade:

Hadith #7410 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) said, âAllah will gather the believers on the Day of Resurrection in the same way (as they are gathered in this life), and they will say, âLet us ask someone to intercede for us with our Lord that He may relieve us from this place of ours.â Then they will go to Adam and say, âO Adam! Donât you see the people (peopleâs condition)? Allah created you with His Own Hands and ordered His angels to prostrate before you, and taught you the names of all the things. Please in
Grade:

Hadith #7411 - Sahih al-Bukhari (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âAllahâs Hand is full, and (its fullness) is not affected by the continuous spending, day and night.â He also said, âDo you see what He has spent since He created the Heavens and the Earth? Yet all that has not decreased what is in His Hand.â He also said, âHis Throne is over the water and in His other Hand is the balance (of Justice) and He raises and lowers (whomever He will).â (See Hadith No. 206, Vol. 6) ÙÙØ¯Ù Ø§ÙÙÙÙÙÙ ÙÙÙØ£ÙÙ ÙØ§Ù
Grade:

Hadith #7412 - Sahih al-Bukhari (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âOn the Day of Resurrection, Allah will grasp the whole Earth by His Hand, and all the Heavens in His right, and then He will say, âI am the King.â Abu Huraira said, âAllahâs Messenger (ï·º) said,â Allah will grasp the Earthâ¦â â Ø¥ÙÙÙÙ Ø§ÙÙÙÙÙÙ ÙÙÙÙØ¨ÙØ¶Ù ÙÙÙÙÙÙ Ø§ÙÙÙÙÙÙØ§ÙÙØ©Ù Ø§ÙØ£ÙØ±ÙØ¶Ù ÙÙØªÙÙÙÙÙÙ Ø§ÙØ³ÙÙÙÙÙÙØ§ØªÙ Ø¨ÙÙÙÙÙÙÙÙÙÙ Ø«ÙÙÙÙ ÙÙÙÙÙÙÙ Ø£ÙÙÙØ§ Ø§ÙÙÙÙÙÙÙÙ
Grade:

Hadith #7414 - Sahih al-Bukhari (Sahih al-Bukhari)
A Jew came to the Prophet (ï·º) and said, âO Muhammad! Allah will hold the heavens on a Finger, and the mountains on a Finger, and the trees on a Finger, and all the creation on a Finger, and then He will say, âI am the King.â â On that Allahâs Messenger (ï·º) smiled till his premolar teeth became visible, and then recited:â âNo just estimate have they made of Allah such as due to himâ¦.(39.67) `Abdullah added: Allahâs Apostle smiled (at the Jewâs statement) expressing his won
Grade:

Hadith #7415 - Sahih al-Bukhari (Sahih al-Bukhari)
A man from the people of the scripture came to the Prophet (ï·º) and said, âO Abal-Qasim! Allah will hold the Heavens upon a Finger, and the Earth on a Finger and the land on a Finger, and all the creation on a Finger, and will say, âI am the King! I am the King!â â I saw the Prophet (after hearing that), smiling till his premolar teeth became visible, and he then recited: â âNo just estimate have they made of Allah such as due to himâ¦ (39.67) Ø¶ÙØÙÙÙ ØÙØªÙÙÙ Ø¨ÙØ¯ÙØªÙ
Grade:

Hadith #7416 - Sahih al-Bukhari (Sahih al-Bukhari)
Sa`d bin âUbada said, âIf I saw a man with my wife, I would strike him (behead him) with the blade of my sword.â This news reached Allahâs Messenger (ï·º) who then said, âYou people are astonished at Sa`dâs Ghira. By Allah, I have more Ghira than he, and Allah has more Ghira than I, and because of Allahâs Ghira, He has made unlawful Shameful deeds and sins (illegal sexual intercourse etc.) done in open and in secret. And there is none who likes that the people should repent to Him
Grade:

Hadith #7417 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) said to a man, âHave you got anything of the Qurâan?â The man said, âYes, such-andsuch Sura, and such-and-such Sura,â naming the Suras. Ø£ÙÙÙØ¹ÙÙÙ ÙÙÙÙ Ø§ÙÙÙÙØ±ÙØ¢ÙÙ Ø´ÙÙÙØ¡Ù ââââ.â ÙÙØ§ÙÙ ÙÙØ¹ÙÙÙ Ø³ÙÙØ±ÙØ©Ù ÙÙØ°ÙØ§ ÙÙØ³ÙÙØ±ÙØ©Ù ÙÙØ°ÙØ§â.â ÙÙØ³ÙÙÙØ±Ù Ø³ÙÙÙÙØ§ÙÙØ§â.â
Grade:

Hadith #7418 - Sahih al-Bukhari (Sahih al-Bukhari)
While I was with the Prophet (ï·º) , some people from Bani Tamim came to him. The Prophet (ï·º) said, âO Bani Tamim! Accept the good news!â They said, âYou have given us the good news; now give us (something).â (After a while) some Yemenites entered, and he said to them, âO the people of Yemen! Accept the good news, as Bani Tamim have refused it. â They said, âWe accept it, for we have come to you to learn the Religion. So we ask you what the beginning of this universe was.â The
Grade:

Hadith #7419 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) said, âThe Right (Hand) of Allah Is full, and (Its fullness) is not affected by the continuous spending night and day. Do you see what He has spent since He created the Heavens and the Earth? Yet all that has not decreased what is in His Right Hand. His Throne is over the water and in His other Hand is the Bounty or the Power to bring about death, and He raises some people and brings others down.â (See Hadith No. 508) Ø¥ÙÙÙÙ ÙÙÙÙÙÙÙ Ø§ÙÙÙÙÙÙ ÙÙÙØ£ÙÙ Ù
Grade:

Hadith #7420 - Sahih al-Bukhari (Sahih al-Bukhari)
Zaid bin Haritha came to the Prophet (ï·º) complaining about his wife. The Prophet (ï·º) kept on saying (to him), âBe afraid of Allah and keep your wife.â Aisha said, âIf Allahâs Messenger (ï·º) were to conceal anything (of the Qurâan he would have concealed this Verse.â Zainab used to boast before the wives of the Prophet (ï·º) and used to say, âYou were given in marriage by your families, while I was married (to the Prophet) by Allah from over seven Heavens.â And Thabit recited
Grade:

Hadith #7421 - Sahih al-Bukhari (Sahih al-Bukhari)
The Verse of Al-Hijab (veiling of women) was revealed in connection with Zainab bint Jahsh. (On the day of her marriage with him) the Prophet (ï·º) gave a wedding banquet with bread and meat; and she used to boast before other wives of the Prophet (ï·º) and used to say, âAllah married me (to the Prophet (ï·º) in the Heavens.â Ø¥ÙÙÙÙ Ø§ÙÙÙÙÙÙ Ø£ÙÙÙÙÙØÙÙÙÙ ÙÙÙ Ø§ÙØ³ÙÙÙÙØ§Ø¡Ùâ.â
Grade:

Hadith #7422 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) said, âWhen Allah had finished His creation, He wrote over his Throne: âMy Mercy preceded My Anger.â Ø¥ÙÙÙÙ Ø§ÙÙÙÙÙÙ ÙÙÙÙÙØ§ ÙÙØ¶ÙÙ Ø§ÙÙØ®ÙÙÙÙÙ ÙÙØªÙØ¨Ù Ø¹ÙÙÙØ¯ÙÙÙ ÙÙÙÙÙÙ Ø¹ÙØ±ÙØ´ÙÙÙ Ø¥ÙÙÙÙ Ø±ÙØÙÙÙØªÙÙ Ø³ÙØ¨ÙÙÙØªÙ ØºÙØ¶ÙØ¨ÙÙ ââ
Grade:

Hadith #7423 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) said, âWhoever believes in Allah and His Apostle offers prayers perfectly and fasts (the month of) Ramadan then it is incumbent upon Allah to admit him into Paradise, whether he emigrates for Allahâs cause or stays in the land where he was born.â They (the companions of the Prophet) said, âO Allahâs Messenger (ï·º)! Should we not inform the people of that?â He said, âThere are one-hundred degrees in Paradise which Allah has prepared for those who carry on Jihad in
Grade:

Hadith #7424 - Sahih al-Bukhari (Sahih al-Bukhari)
I entered the mosque while Allahâs Messenger (ï·º) was sitting there. When the sun had set, the Prophet (ï·º) said, âO Abu Dharr! Do you know where this (sun) goes?â I said, âAllah and His Apostle know best.â He said, âIt goes and asks permission to prostrate, and it is allowed, and (one day) it, as if being ordered to return whence it came, then it will rise from the west.â Then the Prophet (ï·º) recited, âThat: âAnd the sun runs on its fixed course (for a term decreed),â (3
Grade:

Hadith #7425 - Sahih al-Bukhari (Sahih al-Bukhari)
Abu Bakr sent for me, so I collected the Qurâan till I found the last part of Surat-at-Tauba with Abi Khuza`ima Al-Ansari and did not find it with anybody else. (The Verses are): â âVerily, there has come to you an Apostle (Muhammad) from amongst yourselves..(till the end of Surat Baraâa) (i.e., at- Tauba).â (9.128-129) Yunus also narrated as above. Ø£ÙØ±ÙØ³ÙÙÙ Ø¥ÙÙÙÙÙÙ Ø£ÙØ¨ÙÙ Ø¨ÙÙÙØ±Ù ÙÙØªÙØªÙØ¨ÙÙØ¹ÙØªÙ Ø§ÙÙÙÙØ±ÙØ¢ÙÙ ØÙØªÙÙÙ ÙÙØ¬ÙØ¯ÙØªÙ Ø¢Ø®
Grade:

Hadith #7426 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) used to say at the time of difficulty, âLa ilaha il-lallah Al-`Alimul-Halim. La-ilaha illallah Rabul- Arsh-al-Azim, La ilaha-il-lallah Rabus-Samawati Rab-ul-Ard; wa Rab-ul-Arsh Al- Karim.â (See Hadith No. 356 and 357, Vol. 8) ÙØ§Ù Ø¥ÙÙÙÙÙ Ø¥ÙÙØ§ÙÙ Ø§ÙÙÙÙÙÙ Ø§ÙÙØ¹ÙÙÙÙÙÙ Ø§ÙÙØÙÙÙÙÙÙ ÙØ§Ù Ø¥ÙÙÙÙÙ Ø¥ÙÙØ§ÙÙ Ø§ÙÙÙÙÙÙ Ø±ÙØ¨ÙÙ Ø§ÙÙØ¹ÙØ±ÙØ´Ù Ø§ÙÙØ¹ÙØ¸ÙÙÙÙ ÙØ§Ù Ø¥ÙÙÙÙÙ Ø¥ÙÙØ§ÙÙ Ø§ÙÙÙÙÙÙ Ø±ÙØ¨ÙÙ Ø§Ù
Grade:

Hadith #7427 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) said, âThe people will fall unconscious on the Day of Resurrection, then suddenly I will see Moses holding one of the pillars of the Throne.â Abu Huraira said: The Prophet (ï·º) said, âI will be the first person to be resurrected and will see Moses holding the Throne.â â Ø§ÙÙÙÙØ§Ø³Ù ÙÙØµÙØ¹ÙÙÙÙÙÙ ÙÙÙÙÙÙ Ø§ÙÙÙÙÙÙØ§ÙÙØ©Ù ÙÙØ¥ÙØ°ÙØ§ Ø£ÙÙÙØ§ Ø¨ÙÙÙÙØ³ÙÙ Ø¢Ø®ÙØ°Ù Ø¨ÙÙÙØ§Ø¦ÙÙÙØ©Ù ÙÙÙÙ ÙÙÙÙØ§Ø¦ÙÙÙ Ø§ÙÙØ¹ÙØ±ÙØ´Ù
Grade:

Hadith #7429 - Sahih al-Bukhari (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, â(A group of) angels stay with you at night and (another group of) angels by daytime, and both groups gather at the time of the âAsr and Fajr prayers. Then those angels who have stayed with you overnight, ascend (to Heaven) and Allah asks them (about you) â- and He knows everything about you. âIn what state did you leave My slaves?â The angels reply, âWhen we left them, they were praying, and when we reached them they were praying.â â ÙÙØªÙØ¹ÙØ
Grade:

Hadith #7430 - Sahih al-Bukhari (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âIf somebody gives in charity something equal to a date from his honestly earned money â-for nothing ascends to Allah except goodâ- then Allah will take it in His Right (Hand) and bring it up for its owner as anyone of you brings up a baby horse, till it becomes like a mountain.â Abu Huraira said: The Prophet. said, âNothing ascends to Allah except good.â ÙÙÙÙØ§ÙÙ Ø®ÙØ§ÙÙØ¯Ù Ø¨ÙÙÙ ÙÙØ®ÙÙÙØ¯Ù ØÙØ¯ÙÙØ«ÙÙÙØ§ Ø³ÙÙÙÙÙÙÙØ§ÙÙ
Grade:

Hadith #7431 - Sahih al-Bukhari (Sahih al-Bukhari)
Allahâs Messenger (ï·º) used to say at the time of difficulty, âNone has the right to be worshipped but Allah, the Majestic, the Most Forbearing. None has the right to be worshipped but Allah, the Lord of the Tremendous Throne. None has the right to be worshipped but Allah, the Lord of the Heavens and the Lord of the Honourable Throne. (See Hadith No. 357, Vol. 8) ÙØ§Ù Ø¥ÙÙÙÙÙ Ø¥ÙÙØ§ÙÙ Ø§ÙÙÙÙÙÙ Ø§ÙÙØ¹ÙØ¸ÙÙÙÙ Ø§ÙÙØÙÙÙÙÙÙØ ÙØ§Ù Ø¥ÙÙÙÙÙ Ø¥ÙÙØ§ÙÙ Ø§Ù
Grade:

Hadith #7432 - Sahih al-Bukhari (Sahih al-Bukhari)
When `Ali was in Yemen, he sent some gold in its ore to the Prophet. The Prophet (ï·º) distributed it among Al-Aqraâ bin H`Abis Al-Hanzali who belonged to Bani Mujashi, âUyaina bin Badr Al-Fazari, âAlqama bin âUlatha Al-`Amiri, who belonged to the Bani Kilab tribe and Zaid AI-Khail at-Taâi who belonged to Bani Nabhan. So the Quraish and the Ansar became angry and said, âHe gives to the chiefs of Najd and leaves us!â The Prophet (ï·º) said, âI just wanted to attract and unite thei
Grade:

Hadith #7433 - Sahih al-Bukhari (Sahih al-Bukhari)
I asked the Prophet (ï·º) regarding the Verse:ââAnd the sun runs on its fixed course for a term decreed for it.â (36.28) He said, âIts fixed course is underneath Allahâs Throne.â ÙÙØ³ÙØªÙÙÙØ±ÙÙÙÙØ§ ØªÙØÙØªÙ Ø§ÙÙØ¹ÙØ±ÙØ´Ù ââ
Grade:

Hadith #7434 - Sahih al-Bukhari (Sahih al-Bukhari)
We were sitting with the Prophet (ï·º) and he looked at the moon on the night of the full-moon and said, âYou people will see your Lord as you see this full moon, and you will have no trouble in seeing Him, so if you can avoid missing (through sleep or business, etc.) a prayer before sunrise (Fajr) and a prayer before sunset (`Asr) you must do so.â (See Hadith No. 529, Vol. 1) Ø¥ÙÙÙÙÙÙÙÙ Ø³ÙØªÙØ±ÙÙÙÙÙ Ø±ÙØ¨ÙÙÙÙÙÙ ÙÙÙÙØ§ ØªÙØ±ÙÙÙÙÙ ÙÙØ°ÙØ§ Ø§ÙÙÙÙÙÙØ±Ù
Grade:

Hadith #7435 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) said, âYou will definitely see your Lord with your own eyes.â Ø¥ÙÙÙÙÙÙÙÙ Ø³ÙØªÙØ±ÙÙÙÙÙ Ø±ÙØ¨ÙÙÙÙÙÙ Ø¹ÙÙÙØ§ÙÙØ§ ââ
Grade:

Hadith #7436 - Sahih al-Bukhari (Sahih al-Bukhari)
Allahâs Messenger (ï·º) came out to us on the night of the full moon and said, âYou will see your Lord on the Day of Resurrection as you see this (full moon) and you will have no difficulty in seeing Him.â Ø¥ÙÙÙÙÙÙÙÙ Ø³ÙØªÙØ±ÙÙÙÙÙ Ø±ÙØ¨ÙÙÙÙÙÙ ÙÙÙÙÙÙ Ø§ÙÙÙÙÙÙØ§ÙÙØ©Ù ÙÙÙÙØ§ ØªÙØ±ÙÙÙÙÙ ÙÙØ°ÙØ§Ø ÙØ§Ù ØªÙØ¶ÙØ§ÙÙÙÙÙÙ ÙÙÙ Ø±ÙØ¤ÙÙÙØªÙÙÙ ââ
Grade:

Hadith #7437 - Sahih al-Bukhari (Sahih al-Bukhari)
On the authority of Abu Huraira: The people said, âO Allahâs Messenger (ï·º)! Shall we see our Lord on the Day of Resurrection?â The Prophet (ï·º) said, âDo you have any difficulty in seeing the moon on a full moon night?â They said, âNo, O Allahâs Messenger (ï·º).â He said, âDo you have any difficulty in seeing the sun when there are no clouds?â They said, âNo, O Allahâs Messenger (ï·º).â He said, âSo you will see Him, like that. Allah will gather all the people on t
Grade:

Hadith #7439 - Sahih al-Bukhari (Sahih al-Bukhari)
We said, âO Allahâs Messenger (ï·º)! Shall we see our Lord on the Day of Resurrection?â He said, âDo you have any difficulty in seeing the sun and the moon when the sky is clear?â We said, âNo.â He said, âSo you will have no difficulty in seeing your Lord on that Day as you have no difficulty in seeing the sun and the moon (in a clear sky).â The Prophet then said, âSomebody will then announce, âLet every nation follow what they used to worship.â So the companions of the c
Grade:

Hadith #7440 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) said, âThe believers will be kept (waiting) on the Day of Resurrection so long that they will become worried and say, âLet us ask somebody to intercede far us with our Lord so that He may relieve us from our place. Then they will go to Adam and say, âYou are Adam, the father of the people. Allah created you with His Own Hand and made you reside in His Paradise and ordered His angels to prostrate before you, and taught you the names of all things will you intercede for us
Grade:

Hadith #7441 - Sahih al-Bukhari (Sahih al-Bukhari)
Allahâs Messenger (ï·º) sent for the Ansar and gathered them in a tent and said to them, âBe patient till you meet Allah and His Apostle, and I will be on the lake-Tank (Al-Kauthar). Ø§ØµÙØ¨ÙØ±ÙÙØ§ ØÙØªÙÙÙ ØªÙÙÙÙÙÙÙØ§ Ø§ÙÙÙÙÙÙ ÙÙØ±ÙØ³ÙÙÙÙÙÙØ ÙÙØ¥ÙÙÙÙÙ Ø¹ÙÙÙÙ Ø§ÙÙØÙÙÙØ¶Ù ââ
Grade:

Hadith #7442 - Sahih al-Bukhari (Sahih al-Bukhari)
Whenever the Prophet (ï·º) offered his Tahajjud prayer, he would say, âO Allah, our Lord! All the praises are for You; You are the Keeper (Establisher or the One Who looks after) of the Heavens and the Earth. All the Praises are for You; You are the Light of the Heavens and the Earth and whatever is therein. You are the Truth, and Your saying is the Truth, and Your promise is the Truth, and the meeting with You is the Truth, and Paradise is the Truth, and the (Hell) Fire is the Truth. O Allah!
Grade:

Hadith #7443 - Sahih al-Bukhari (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âThere will be none among you but his Lord will speak to him, and there will be no interpreter between them nor a screen to screen Him.â ÙÙØ§ ÙÙÙÙÙÙÙÙ ÙÙÙÙ Ø£ÙØÙØ¯Ù Ø¥ÙÙØ§ÙÙ Ø³ÙÙÙÙÙÙÙÙÙÙÙÙ Ø±ÙØ¨ÙÙÙÙØ ÙÙÙÙØ³Ù Ø¨ÙÙÙÙÙÙÙ ÙÙØ¨ÙÙÙÙÙÙÙ ØªÙØ±ÙØ¬ÙÙÙØ§ÙÙ ÙÙÙØ§Ù ØÙØ¬ÙØ§Ø¨Ù ÙÙØÙØ¬ÙØ¨ÙÙÙ ââ
Grade:

Hadith #7444 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) said, â(There will be) two Paradises of silver and all the utensils and whatever is therein (will be of silver); and two Paradises of gold, and its utensils and whatever therein (will be of gold), and there will be nothing to prevent the people from seeing their Lord except the Cover of Majesty over His Face in the Paradise of Eden (eternal bliss). Ø¬ÙÙÙÙØªÙØ§ÙÙ ÙÙÙÙ ÙÙØ¶ÙÙØ©Ù Ø¢ÙÙÙÙØªÙÙÙÙÙØ§ ÙÙÙÙØ§ ÙÙÙÙÙÙÙØ§Ø ÙÙØ¬ÙÙÙÙØªÙØ§ÙÙ ÙÙ
Grade:

Hadith #7445 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) said, âWhoever takes the property of a Muslim by taking a false oath, will meet Allah Who will be angry with him.â Then the Prophet (ï·º) recited the Verse:â âVerily those who purchase a small gain at the cost of Allahâs Covenant and their oaths, they shall have no portion in the Hereafter, neither will Allah speak to them, nor look at them.â (3.77) ÙÙÙÙ Ø§ÙÙØªÙØ·ÙØ¹Ù ÙÙØ§ÙÙ Ø§ÙÙØ±ÙØ¦Ù ÙÙØ³ÙÙÙÙÙ Ø¨ÙÙÙÙÙÙÙÙ ÙÙØ§Ø°ÙØ¨ÙØ©ÙØ ÙÙÙÙ
Grade:

Hadith #7446 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) said, â(There are) three (types of persons to whom) Allah will neither speak to them on the Day of Resurrections, nor look at them (They are):â(1) a man who takes a false oath that he has been offered for a commodity a price greater than what he has actually been offered; (2) and a man who takes a false oath after the `Asr (prayer) in order to grab the property of a Muslim through it; (3) and a man who forbids others to use the remaining superfluous water. To such a man All
Grade:

Hadith #7447 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) said, âTime has come back to its original state which it had when Allah created the Heavens and the Earth, the year is twelve months, of which four are sacred; (and out of these four) three are in succession, namely, Dhul-Qaâda, Dhul-Hijja and Muharram, and (the fourth one) Rajab Mudar which is between Jumad (Ath-Tham) and Shaâban.â The Prophet (ï·º) then asked us, âWhich month is this?â We said, âAllah and His Apostle know (it) better.â He kept quiet so long th
Grade:

Hadith #7448 - Sahih al-Bukhari (Sahih al-Bukhari)
A son of one of the daughters of the Prophet (ï·º) was dying, so she sent a person to call the Prophet. He sent (her a message), âWhat ever Allah takes is for Him, and whatever He gives is for Him, and everything has a limited fixed term (in this world) so she should be patient and hope for Allahâs reward.â She then sent for him again, swearing that he should come. Allahâs Messenger (ï·º) got up, and so did Mu`adh bin Jabal, Ubai bin Ka`b and âUbada bin As-Samit. When he entered (the h
Grade:

Hadith #7449 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) said, âParadise and Hell (Fire) quarrelled in the presence of their Lord. Paradise said, âO Lord! What is wrong with me that only the poor and humble people enter me ?â Hell (Fire) said, I have been favored with the arrogant people.â So Allah said to Paradise, âYou are My Mercy,â and said to Hell, âYou are My Punishment which I inflict upon whom I wish, and I shall fill both of you.'â The Prophet added, âAs for Paradise, (it will be filled with good people) be
Grade:

Hadith #7450 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) said, âSome people will be scorched by Hell (Fire) as a punishment for sins they have committed, and then Allah will admit them into Paradise by the grant of His Mercy. These people will be called, âAl-Jahannamiyyinâ (the people of Hell). ÙÙÙÙØµÙÙØ¨ÙÙÙÙ Ø£ÙÙÙÙÙØ§ÙÙØ§ Ø³ÙÙÙØ¹Ù ÙÙÙÙ Ø§ÙÙÙÙØ§Ø±Ù Ø¨ÙØ°ÙÙÙÙØ¨Ù Ø£ÙØµÙØ§Ø¨ÙÙÙÙØ§ Ø¹ÙÙÙÙØ¨ÙØ©ÙØ Ø«ÙÙÙÙ ÙÙØ¯ÙØ®ÙÙÙÙÙÙÙ Ø§ÙÙÙÙÙÙ Ø§ÙÙØ¬ÙÙÙÙØ©Ù Ø¨ÙÙÙØ¶ÙÙÙ
Grade:

Hadith #7451 - Sahih al-Bukhari (Sahih al-Bukhari)
A Jewish Rabbi came to Allahâs Messenger (ï·º) and said, âO Muhammad! Allah will put the Heavens on one finger and the earth on one finger, and the trees and the rivers on one finger, and the rest of the creation on one finger, and then will say, pointing out with His Hand, âI am the King.â âOn that Allahâs Apostle smiled and said, âNo just estimate have they made of Allah such as due to Him. (39.67) ÙÙØ¶ÙØÙÙÙ Ø±ÙØ³ÙÙÙÙ Ø§ÙÙÙÙÙÙ ØµÙÙ Ø§ÙÙÙ Ø¹ÙÙÙ ÙØ³ÙÙ Ù
Grade:

Hadith #7452 - Sahih al-Bukhari (Sahih al-Bukhari)
Once I stayed overnight at the house of (my aunt ) Maimuna while the Prophet (ï·º) was with her, to see how was the night prayer of Allah s Apostle Allahâs Messenger (ï·º) talked to his wife for a while and then slept. When it was the last third of the night (or part of it), the Prophet (ï·º) got up and looked towards the sky and recited the Verse:â âVerily! In the creation of the Heavens and the Earthâ¦.there are indeed signs for the men of understanding.â (3.190) Then He got up and pe
Grade:

Hadith #7453 - Sahih al-Bukhari (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âWhen Allah created the creations, He wrote with Him on His Throne: âMy Mercy has preceded My Anger.â ÙÙÙÙÙØ§ ÙÙØ¶ÙÙ Ø§ÙÙÙÙÙÙ Ø§ÙÙØ®ÙÙÙÙÙ ÙÙØªÙØ¨Ù Ø¹ÙÙÙØ¯ÙÙÙ ÙÙÙÙÙÙ Ø¹ÙØ±ÙØ´ÙÙÙØ Ø¥ÙÙÙÙ Ø±ÙØÙÙÙØªÙÙ Ø³ÙØ¨ÙÙÙØªÙ ØºÙØ¶ÙØ¨ÙÙ ââ
Grade:

Hadith #7454 - Sahih al-Bukhari (Sahih al-Bukhari)
Allahâs Messenger (ï·º) the true and truly inspired, narrated to us, âThe creation of everyone of you starts with the process of collecting the material for his body within forty days and forty nights in the womb of his mother. Then he becomes a clot of thick blood for a similar period (40 days) and then he becomes like a piece of flesh for a similar period. Then an angel is sent to him (by Allah) and the angel is allowed (ordered) to write four things; his livelihood, his (date of) death, h
Grade:

Hadith #7455 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) said, âO Gabriel, what prevents you. from visiting us more often than you do?â Then this Verse was revealed:ââAnd we angels descend not but by Command of your Lord. To Him belongs what is before us and what is behind us..â (19.64) So this was the answer to Muhammad. ÙÙØ§ ÙÙÙÙÙÙØ¹ÙÙÙ Ø£ÙÙÙ ØªÙØ²ÙÙØ±ÙÙÙØ§ Ø£ÙÙÙØ«ÙØ±Ù ÙÙÙÙÙØ§ ØªÙØ²ÙÙØ±ÙÙÙØ§ ââââ.â ÙÙÙÙØ²ÙÙÙØªÙ ââ{âÙÙÙÙØ§ ÙÙØªÙÙÙØ²ÙÙÙÙ Ø¥ÙÙØ§ÙÙ Ø
Grade:

Hadith #7456 - Sahih al-Bukhari (Sahih al-Bukhari)
While I was walking with Allahâs Messenger (ï·º) in one of the fields of Medina and he was walking leaning on a stick, he passed a group of Jews. Some of them said to the others, âAsk him (the Prophet) about the spirit.â Others said, âDo not ask him.â But they asked him and he stood leaning on the stick and I was standing behind him and I thought that he was being divinely inspired. Then he said, âThey ask you concerning the spirit say: The spirit, its knowledge is with My Lord. And
Grade:

Hadith #7457 - Sahih al-Bukhari (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âAllah guarantees to the person who carries out Jihad for His Cause and nothing compelled him to go out but the Jihad in His Cause, and belief in His Words, that He will either admit him into Paradise or return him with his reward or the booty he has earned to his residence from where he went out.â (See Hadith No. 555). ØªÙÙÙÙÙÙÙÙ Ø§ÙÙÙÙÙÙ ÙÙÙÙÙÙ Ø¬ÙØ§ÙÙØ¯Ù ÙÙÙ Ø³ÙØ¨ÙÙÙÙÙÙØ ÙØ§Ù ÙÙØ®ÙØ±ÙØ¬ÙÙÙ Ø¥ÙÙØ§ÙÙ Ø§ÙÙØ¬ÙÙ
Grade:

Hadith #7458 - Sahih al-Bukhari (Sahih al-Bukhari)
A man came to the Prophet (ï·º) and said, âA man fights for pride and haughtiness another fights for bravery, and another fights for showing off; which of these (cases) is in Allahâs Cause?â The Prophet (ï·º) said, âThe one who fights that Allahâs Word (Islam) should be superior, fights in Allahâs Cause.â (See Hadith No. 65, Vol. 4) ÙÙÙÙ ÙÙØ§ØªÙÙÙ ÙÙØªÙÙÙÙÙÙ ÙÙÙÙÙÙØ©Ù Ø§ÙÙÙÙÙÙ ÙÙÙÙ Ø§ÙÙØ¹ÙÙÙÙÙØ§Ø ÙÙÙÙÙÙ ÙÙÙ Ø³ÙØ¨ÙÙÙÙ Ø§ÙÙÙÙ
Grade:

Hadith #7459 - Sahih al-Bukhari (Sahih al-Bukhari)
I heard the Prophet (ï·º) saying, âSome people from my followers will continue to be victorious over others till Allahâs Order (The Hour) is established.â (See Hadith No. 414) ÙØ§Ù ÙÙØ²ÙØ§ÙÙ ÙÙÙÙ Ø£ÙÙÙÙØªÙÙ ÙÙÙÙÙÙ Ø¸ÙØ§ÙÙØ±ÙÙÙÙ Ø¹ÙÙÙÙ Ø§ÙÙÙÙØ§Ø³ÙØ ØÙØªÙÙÙ ÙÙØ£ÙØªÙÙÙÙÙÙÙ Ø£ÙÙÙØ±Ù Ø§ÙÙÙÙÙÙ ââ
Grade:

Hadith #7460 - Sahih al-Bukhari (Sahih al-Bukhari)
I heard the Prophet (ï·º) saying, âA group of my followers will keep on following Allahâs Laws strictly and they will not be harmed by those who will disbelieve them or stand against them till Allahâs Order (The Hour) will come while they will be in that state.â ÙØ§Ù ÙÙØ²ÙØ§ÙÙ ÙÙÙÙ Ø£ÙÙÙÙØªÙÙ Ø£ÙÙÙÙØ©Ù ÙÙØ§Ø¦ÙÙÙØ©Ù Ø¨ÙØ£ÙÙÙØ±Ù Ø§ÙÙÙÙÙÙØ ÙÙØ§ ÙÙØ¶ÙØ±ÙÙÙÙÙÙ ÙÙÙÙ ÙÙØ°ÙÙØ¨ÙÙÙÙÙØ ÙÙÙØ§Ù ÙÙÙÙ Ø®ÙØ§ÙÙÙÙÙÙÙÙØ ØÙ
Grade:

Hadith #7461 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) stood before Musailama (the liar) who was sitting with his companions then, and said to him, âIf you ask me for this piece (of palm-leaf stalk), even then I would not give it to you. You cannot avoid what Allah has ordained for you, and if you turn away from Islam, Allah will surely ruin you! â ÙÙÙÙ Ø³ÙØ£ÙÙÙØªÙÙÙÙ ÙÙØ°ÙÙÙ Ø§ÙÙÙÙØ·ÙØ¹ÙØ©Ù ÙÙØ§ Ø£ÙØ¹ÙØ·ÙÙÙØªÙÙÙÙÙØ§Ø ÙÙÙÙÙÙ ØªÙØ¹ÙØ¯ÙÙÙ Ø£ÙÙÙØ±Ù Ø§ÙÙÙÙÙÙ ÙÙÙÙÙØ ÙÙ
Grade:

Hadith #7462 - Sahih al-Bukhari (Sahih al-Bukhari)
While I was walking in company with the Prophet (ï·º) in one of the fields of Medina, the Prophet (ï·º) was reclining on a palm leave stalk which he carried with him. We passed by a group of Jews. Some of them said to the others, âAsk him about the spirit.â The others said, âDo not ask him, lest he would say something that you hate.â Some of them said, âWe will ask him.â So a man from among them stood up and said, âO Abal-Qasim! What is the spirit?â The Prophet (ï·º) kept quiet a
Grade:

Hadith #7463 - Sahih al-Bukhari (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âAllah guarantees (the person who carries out Jihad in His Cause and nothing compelled him to go out but Jihad in His Cause and the belief in His Word) that He will either admit him into Paradise (Martyrdom) or return him with reward or booty he has earned to his residence from where he went out.â ØªÙÙÙÙÙÙÙÙ Ø§ÙÙÙÙÙÙ ÙÙÙÙÙÙ Ø¬ÙØ§ÙÙØ¯Ù ÙÙÙ Ø³ÙØ¨ÙÙÙÙÙÙØ ÙØ§Ù ÙÙØ®ÙØ±ÙØ¬ÙÙÙ ÙÙÙÙ Ø¨ÙÙÙØªÙÙÙ Ø¥ÙÙØ§ÙÙ Ø§ÙÙØ¬
Grade:

Hadith #7464 - Sahih al-Bukhari (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âWhenever anyone of you invoke Allah for something, he should be firm in his asking, and he should not say: âIf You wish, give meâ¦â for none can compel Allah to do something against His Will.â Ø¥ÙØ°ÙØ§ Ø¯ÙØ¹ÙÙÙØªÙÙÙ Ø§ÙÙÙÙÙÙ ÙÙØ§Ø¹ÙØ²ÙÙÙÙØ§ ÙÙÙ Ø§ÙØ¯ÙÙØ¹ÙØ§Ø¡ÙØ ÙÙÙØ§Ù ÙÙÙÙÙÙÙÙÙÙ Ø£ÙØÙØ¯ÙÙÙÙÙ Ø¥ÙÙÙ Ø´ÙØ¦ÙØªÙ ÙÙØ£ÙØ¹ÙØ·ÙÙÙÙØ ÙÙØ¥ÙÙÙÙ Ø§ÙÙÙÙÙÙ ÙØ§Ù ÙÙØ³ÙØªÙÙÙØ±ÙÙÙ ÙÙ
Grade:

Hadith #7465 - Sahih al-Bukhari (Sahih al-Bukhari)
That one night Allahâs Messenger (ï·º) visited him and Fatima, the daughter of Allahâs Messenger (ï·º) and said to them, âWon ât you offer (night) prayer?.. `Ali added: I said, âO Allahâs Messenger (ï·º)! Our souls are in the Hand of Allah and when He Wishes to bring us to life, He does.â Then Allahâs Messenger (ï·º) went away when I said so and he did not give any reply. Then I heard him on leaving while he was striking his thighs, saying, âBut man is, more quarrelsome than an
Grade:

Hadith #7466 - Sahih al-Bukhari (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âThe example of a believer is that of a fresh green plant the leaves of which move in whatever direction the wind forces them to move and when the wind becomes still, it stand straight. Such is the similitude of the believer: He is disturbed by calamities (but is like the fresh plant he regains his normal state soon). And the example of a disbeliever is that of a pine tree (which remains) hard and straight till Allah cuts it down when He will.â (See Hadith No.
Grade:

Hadith #7467 - Sahih al-Bukhari (Sahih al-Bukhari)
I heard Allahâs Messenger (ï·º) while he was standing on the pulpit, saying, âThe remaining period of your stay (on the earth) in comparison to the nations before you, is like the period between the `Asr prayer and sunset. The people of the Torah were given the Torah and they acted upon it till midday, and then they were worn out and were given for their labor, one Qirat each. Then the people of the Gospel were given the Gospel and they acted upon it till the time of the `Asr prayer, and the
Grade:

Hadith #7468 - Sahih al-Bukhari (Sahih al-Bukhari)
I, along with a group of people, gave the pledge of allegiance to Allahâs Messenger (ï·º). He said, âI take your Pledge on the condition that you (1) will not join partners in worship with Allah, (2) will not steal, (3) will not commit illegal sexual intercourse, (4) will not kill your offspring, (5) will not slander, (6) and will not disobey me when I order you to do good. Whoever among you will abide by his pledge, his reward will be with Allah, and whoever commits any of those sins and re
Grade:

Hadith #7469 - Sahih al-Bukhari (Sahih al-Bukhari)
Allahâs Prophet Solomon who had sixty wives, once said, âTonight I will have sexual relation (sleep) with all my wives so that each of them will become pregnant and bring forth (a boy who will grow into) a cavalier and will fight in Allahâs Cause.â So he slept with his wives and none of them (conceived and) delivered (a child) except one who brought a half (body) boy (deformed). Allahâs Prophet said, âIf Solomon had said; âIf Allah Will,â then each of those women would have deliv
Grade:

Hadith #7470 - Sahih al-Bukhari (Sahih al-Bukhari)
Allahâs Messenger (ï·º) entered upon a sick bedouin in whom he went to visit and said to him, âDonât worry, Tahur (i.e., your illness will be a means of cleansing of your sins), if Allah Will.â The bedouin said, âTahur! No, but it is a fever that is burning in the body of an old man and it will make him visit his grave.â The Prophet (ï·º) said, âThen it is so.â ÙØ§Ù Ø¨ÙØ£ÙØ³Ù Ø¹ÙÙÙÙÙÙÙ Ø·ÙÙÙÙØ±ÙØ Ø¥ÙÙÙ Ø´ÙØ§Ø¡Ù Ø§ÙÙÙÙÙÙ ââââ.â ÙÙØ§ÙÙ ÙÙ
Grade:

Hadith #7471 - Sahih al-Bukhari (Sahih al-Bukhari)
When the people slept till so late that they did not offer the (morning) prayer, the Prophet (ï·º) said, âAllah captured your souls (made you sleep) when He willed, and returned them (to your bodies) when He willed.â So the people got up and went to answer the call of nature, performed ablution, till the sun had risen and it had become white, then the Prophet (ï·º) got up and offered the prayer. Ø¥ÙÙÙÙ Ø§ÙÙÙÙÙÙ ÙÙØ¨ÙØ¶Ù Ø£ÙØ±ÙÙÙØ§ØÙÙÙÙÙ ØÙÙÙÙ Ø´ÙØ§Ø¡ÙØ ÙÙØ±Ù
Grade:

Hadith #7472 - Sahih al-Bukhari (Sahih al-Bukhari)
âA man from the Muslims and a man from the Jews quarrelled, and the Muslim said, âBy Him Who gave superiority to Muhammad over all the people!â The Jew said, âBy Him Who gave superiority to Moses over all the people!â On that the Muslim lifted his hand and slapped the Jew. The Jew went to Allahâs Messenger (ï·º) and informed him of all that had happened between him and the Muslim. The Prophet (ï·º) said, âDo not give me superiority over Moses, for the people will fall unconscious o
Grade:

Hadith #7473 - Sahih al-Bukhari (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âAd-Dajjal will come to Medina and find the angels guarding it. If Allah will, neither Ad-Dajjal nor plague will be able to come near it.â â Ø§ÙÙÙÙØ¯ÙÙÙÙØ©Ù ÙÙØ£ÙØªÙÙÙÙØ§ Ø§ÙØ¯ÙÙØ¬ÙÙØ§ÙÙ ÙÙÙÙØ¬ÙØ¯Ù Ø§ÙÙÙÙÙØ§ÙØ¦ÙÙÙØ©Ù ÙÙØÙØ±ÙØ³ÙÙÙÙÙÙØ§ ÙÙÙØ§Ù ÙÙÙÙØ±ÙØ¨ÙÙÙØ§ Ø§ÙØ¯ÙÙØ¬ÙÙØ§ÙÙ ÙÙÙØ§Ù Ø§ÙØ·ÙÙØ§Ø¹ÙÙÙÙ Ø¥ÙÙÙ Ø´ÙØ§Ø¡Ù Ø§ÙÙÙÙÙÙ ââ
Grade:

Hadith #7474 - Sahih al-Bukhari (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âFor every Prophet there is one invocation which is definitely fulfilled by Allah, and I wish, if Allah will, to keep my that (special) invocation as to be the intercession for my followers on the Day of Resurrection.â ÙÙÙÙÙÙÙ ÙÙØ¨ÙÙÙÙ Ø¯ÙØ¹ÙÙÙØ©ÙØ ÙÙØ£ÙØ±ÙÙØ¯Ù Ø¥ÙÙÙ Ø´ÙØ§Ø¡Ù Ø§ÙÙÙÙÙÙ Ø£ÙÙÙ Ø£ÙØ®ÙØªÙØ¨ÙÙÙ Ø¯ÙØ¹ÙÙÙØªÙÙ Ø´ÙÙÙØ§Ø¹ÙØ©Ù ÙØ£ÙÙÙÙØªÙÙ ÙÙÙÙÙÙ Ø§ÙÙÙÙÙÙØ§ÙÙØ©Ù ââ
Grade:

Hadith #7475 - Sahih al-Bukhari (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âWhile I was sleeping, I saw myself (in a dream) standing by a well. I drew from it as much water as Allah wished me to draw, and then Ibn Quhafa (Abu Bakr) took the bucket from me and drew one or two buckets, and there was weakness in his drawingâ-may Allah forgive him! Then `Umar took the bucket which turned into something like a big drum. I had never seen a powerful man among the people working as perfectly and vigorously as he did. (He drew so much water t
Grade:

Hadith #7476 - Sahih al-Bukhari (Sahih al-Bukhari)
Whenever a beggar or a person in need of something came to the Prophet (ï·º) , he used to say (to his companions), âIntercede (for him) and you will be rewarded for that, and Allah will fulfill what He will through His Apostleâs tongue.â Ø¥ÙØ°ÙØ§ Ø£ÙØªÙØ§ÙÙ Ø§ÙØ³ÙÙØ§Ø¦ÙÙÙ Ù ÙÙØ±ÙØ¨ÙÙÙÙØ§ ÙÙØ§ÙÙ Ø¬ÙØ§Ø¡ÙÙÙ Ø§ÙØ³ÙÙØ§Ø¦ÙÙÙ Ù Ø£ÙÙÙ ØµÙØ§ØÙØ¨Ù Ø§ÙÙØÙØ§Ø¬ÙØ©Ù ÙÙØ§ÙÙ âââ Ø§Ø´ÙÙÙØ¹ÙÙØ§ ÙÙÙÙØªÙØ¤ÙØ¬ÙØ±ÙÙØ§Ø ÙÙÙÙÙÙØ¶ÙÙ
Grade:

Hadith #7477 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) said, âNone of you should say: âO Allah! Forgive me if You wish,â or âBestow Your Mercy on me if You wish,â or âProvide me with means of subsistence if You wish,â but he should be firm in his request, for Allah does what He will and nobody can force Him (to do anything). ÙØ§Ù ÙÙÙÙÙÙ Ø£ÙØÙØ¯ÙÙÙÙÙ Ø§ÙÙÙÙÙÙÙÙÙ Ø§ØºÙÙÙØ±Ù ÙÙÙ Ø¥ÙÙÙ Ø´ÙØ¦ÙØªÙØ Ø§Ø±ÙØÙÙÙÙÙÙ Ø¥ÙÙÙ Ø´ÙØ¦ÙØªÙØ Ø§Ø±ÙØ²ÙÙÙÙÙÙ Ø¥ÙÙÙ Ø´ÙØ¦ÙØªÙØ
Grade:

Hadith #7478 - Sahih al-Bukhari (Sahih al-Bukhari)
That he differed with Al-Hurr bin Qais bin Hisn Al-Fazari about the companion of Moses, (i.e., whether he was Kha,dir or not). Ubai bin Ka`b Al-Ansari passed by them and Ibn `Abbas called him saying, âMy friend (Hur) and I have differed about Mosesâ Companion whom Moses asked the way to meet. Did you hear Allahâs Messenger (ï·º) mentioning anything about him?â Ubai said, âYes, I heard Allahâs Apostle saying, âWhile Moses was sitting in the company of some Israelites a man came to h
Grade:

Hadith #7479 - Sahih al-Bukhari (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âIf Allah wills, tomorrow we will encamp in Khaif Bani Kinana, the place where the pagans took the oath of Kufr (disbelief) against the Prophet. He meant Al-Muhassab. (See Hadith 1589) ÙÙÙÙØ²ÙÙÙ ØºÙØ¯ÙØ§ Ø¥ÙÙÙ Ø´ÙØ§Ø¡Ù Ø§ÙÙÙÙÙÙ Ø¨ÙØ®ÙÙÙÙÙ Ø¨ÙÙÙÙ ÙÙÙÙØ§ÙÙØ©Ù ØÙÙÙØ«Ù ØªÙÙÙØ§Ø³ÙÙÙÙØ§ Ø¹ÙÙÙÙ Ø§ÙÙÙÙÙÙØ±Ù ââââ.â ÙÙØ±ÙÙØ¯Ù Ø§ÙÙÙÙØÙØµÙÙØ¨Ùâ.â
Grade:

Hadith #7480 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) besieged the people of Taâif, but he did not conquer it. He said, âTomorrow, if Allah will, we will return home. On this the Muslims said, âThen we return without conquering it?â He said, âThen carry on fighting tomorrow.â The next day many of them were injured. The Prophet (ï·º) said, âIf Allah will, we will return home tomorrow.â It seemed that statement pleased them whereupon Allahâs Apostle smiled. Ø¥ÙÙÙÙØ§ ÙÙØ§ÙÙÙÙÙÙÙ Ø¥ÙÙÙ Ø´ÙØ§Ø¡Ù Ø§Ù
Grade:

Hadith #7481 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) said, âWhen Allah ordains something on the Heaven the angels beat with their wings in obedience to His Statement which sounds like that of a chain dragged over a rock. His Statement: âUntil when the fear is banished from their hearts, the Angels say, âWhat was it that your Lord said?â âThey reply, â(He has said) the Truth. And He is the Most High, The Great. â (34.23) Ø¥ÙØ°ÙØ§ ÙÙØ¶ÙÙ Ø§ÙÙÙÙÙÙ Ø§ÙØ£ÙÙÙØ±Ù ÙÙÙ Ø§ÙØ³ÙÙÙÙØ§Ø¡Ù Ø¶ÙØ±ÙØ¨ÙØªÙ
Grade:

Hadith #7482 - Sahih al-Bukhari (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âAllah never listens to anything as He listens to the Prophet (ï·º) reciting Qurâan in a pleasant sweet sounding voice.â A companion of Abu Huraira said, âHe means, reciting the Qurâan aloud.â ÙÙØ§ Ø£ÙØ°ÙÙÙ Ø§ÙÙÙÙÙÙ ÙÙØ´ÙÙÙØ¡Ù ÙÙØ§ Ø£ÙØ°ÙÙÙ ÙÙÙÙÙÙØ¨ÙÙÙÙ ØµÙÙ Ø§ÙÙÙ Ø¹ÙÙÙ ÙØ³ÙÙ ÙÙØªÙØºÙÙÙÙÙ Ø¨ÙØ§ÙÙÙÙØ±ÙØ¢ÙÙ ââ
Grade:

Hadith #7483 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) said, âAllah will say (on the Day of Resurrection), âO Adam!â Adam will reply, âLabbaik wa Sa`daik! â Then a loud Voice will be heard (Saying) âAllah Commands you to take out the mission of the Hell Fire from your offspring.â â ÙÙÙÙÙÙÙ Ø§ÙÙÙÙÙÙ ÙÙØ§ Ø¢Ø¯ÙÙÙâ.â ÙÙÙÙÙÙÙÙÙ ÙÙØ¨ÙÙÙÙÙÙ ÙÙØ³ÙØ¹ÙØ¯ÙÙÙÙÙâ.â ÙÙÙÙÙÙØ§Ø¯ÙÙ Ø¨ÙØµÙÙÙØªÙ Ø¥ÙÙÙÙ Ø§ÙÙÙÙÙÙ ÙÙØ£ÙÙÙØ±ÙÙÙ Ø£ÙÙÙ ØªÙØ®ÙØ±ÙØ¬Ù Ù
Grade:

Hadith #7484 - Sahih al-Bukhari (Sahih al-Bukhari)
I never felt so jealous of any woman as I felt of Khadija, for Allah ordered him (the Prophet (ï·º) ) to give Khadija the glad tidings of a palace in Paradise (for her). ÙÙØ§ ØºÙØ±ÙØªÙ Ø¹ÙÙÙÙ Ø§ÙÙØ±ÙØ£ÙØ©Ù ÙÙØ§ ØºÙØ±ÙØªÙ Ø¹ÙÙÙÙ Ø®ÙØ¯ÙÙØ¬ÙØ©ÙØ ÙÙÙÙÙÙØ¯Ù Ø£ÙÙÙØ±ÙÙÙ Ø±ÙØ¨ÙÙÙÙ Ø£ÙÙÙ ÙÙØ¨ÙØ´ÙÙØ±ÙÙÙØ§ Ø¨ÙØ¨ÙÙÙØªÙ ÙÙÙ Ø§ÙÙØ¬ÙÙÙÙØ©Ùâ.â
Grade:

Hadith #7485 - Sahih al-Bukhari (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âIf Allah loves a person, He calls Gabriel, saying, âAllah loves so and so, O Gabriel love himâ So Gabriel would love him and then would make an announcement in the Heavens: âAllah has loved so and-so therefore you should love him also.â So all the dwellers of the Heavens would love him, and then he is granted the pleasure of the people on the earth.â (See Hadith No. 66, Vol. 8) Ø¥ÙÙÙÙ Ø§ÙÙÙÙÙÙ ØªÙØ¨ÙØ§Ø±ÙÙÙ ÙÙØªÙØ¹ÙØ§ÙÙÙ Ø¥ÙØ°Ù
Grade:

Hadith #7486 - Sahih al-Bukhari (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âThere are angels coming to you in succession at night, and others during the day, and they all gather at the time of `Asr and Fajr prayers. Then the angels who have stayed with you overnight ascend (to the heaven) and He (Allah) asks them though He perfectly knows their affairs. âIn what state have you left my slaves?â They say, âWhen we left them, they were praying and when we came to them they were praying.â â ÙÙØªÙØ¹ÙØ§ÙÙØ¨ÙÙÙÙ ÙÙÙÙÙ
Grade:

Hadith #7487 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) said, Gabriel came to me and gave me the glad tidings that anyone who died without worshipping anything besides Allah, would enter Paradise. I asked (Gabriel), âEven if he committed theft, and even if he committed illegal sexual intercourse?â He said, â(Yes), even if he committed theft, and even if he Committed illegal sexual intercourse.â Ø£ÙØªÙØ§ÙÙÙ Ø¬ÙØ¨ÙØ±ÙÙÙÙ ÙÙØ¨ÙØ´ÙÙØ±ÙÙÙÙ Ø£ÙÙÙÙÙÙ ÙÙÙÙ ÙÙØ§ØªÙ ÙØ§Ù ÙÙØ´ÙØ±ÙÙÙ Ø¨ÙØ§ÙÙÙ
Grade:

Hadith #7488 - Sahih al-Bukhari (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âO so-and-so, whenever you go to your bed (for sleeping) say, âO Allah! I have surrendered myself over to you and have turned my face towards You, and leave all my affairs to You and depend on You and put my trust in You expecting Your reward and fearing Your punishment. There is neither fleeing from You nor refuge but with You. I believe in the Book (Qurâan) which You have revealed and in Your Prophet (Muhammad) whom You have sent.â If you then die on tha
Grade:

Hadith #7489 - Sahih al-Bukhari (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said on the Day of (the battle of) the Clans, âO Allah! The Revealer of the Holy Book, The Quick Taker of Accounts! Defeat the clans and shake them.â Ø§ÙÙÙÙÙÙÙÙÙ ÙÙÙÙØ²ÙÙÙ Ø§ÙÙÙÙØªÙØ§Ø¨ÙØ Ø³ÙØ±ÙÙØ¹Ù Ø§ÙÙØÙØ³ÙØ§Ø¨ÙØ Ø§ÙÙØ²ÙÙÙ Ø§ÙØ£ÙØÙØ²ÙØ§Ø¨Ù ÙÙØ²ÙÙÙØ²ÙÙÙ Ø¨ÙÙÙÙÙ ââ
Grade:

Hadith #7490 - Sahih al-Bukhari (Sahih al-Bukhari)
(regarding the Verse):â âNeither say your prayer aloud, nor say it in a low tone.â (17.110) This Verse was revealed while Allahâs Messenger (ï·º) was hiding himself in Mecca, and when he raised his voice while reciting the Qurâan, the pagans would hear him and abuse the Qurâan and its Revealer and to the one who brought it. So Allah said:â âNeither say your prayer aloud, nor say it in a low tone.â (17.110) That is, âDo not say your prayer so loudly that the pagans can hear yo
Grade:

Hadith #7491 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) said, âAllah said: âThe son of Adam hurts Me by abusing Time, for I am Time; in My Hands are all things and I cause the revolution of night and day.â â (See Hadith No. 351, Vol. 6) ÙÙØ¤ÙØ°ÙÙÙÙÙ Ø§Ø¨ÙÙÙ Ø¢Ø¯ÙÙÙØ ÙÙØ³ÙØ¨ÙÙ Ø§ÙØ¯ÙÙÙÙØ±Ù ÙÙØ£ÙÙÙØ§ Ø§ÙØ¯ÙÙÙÙØ±ÙØ Ø¨ÙÙÙØ¯ÙÙ Ø§ÙØ£ÙÙÙØ±ÙØ Ø£ÙÙÙÙÙÙØ¨Ù Ø§ÙÙÙÙÙÙÙÙ ÙÙØ§ÙÙÙÙÙÙØ§Ø±Ù ââ
Grade:

Hadith #7492 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) said, âAllah said: The Fast is for Me and I will give the reward for it, as he (the one who observes the fast) leaves his sexual desire, food and drink for My Sake. Fasting is a screen (from Hell) and there are two pleasures for a fasting person, one at the time of breaking his fast, and the other at the time when he will meet his Lord. And the smell of the mouth of a fasting person is better in Allahâs Sight than the smell of musk.â (See Hadith No. 128, Vol. 3). Ø§ÙØµÙ
Grade:

Hadith #7493 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) said, âOnce while Job (Aiyub) was taking a bath in a naked state. Suddenly a great number of gold locusts started falling upon him and he started collecting them in his clothes. His Lord called him, âO Job! Didnât I make you rich enough to dispense with what you see now?â Job said, âYes, O Lord! But I cannot dispense with Your Blessings.â Ø¨ÙÙÙÙÙÙÙØ§ Ø£ÙÙÙÙÙØ¨Ù ÙÙØºÙØªÙØ³ÙÙÙ Ø¹ÙØ±ÙÙÙØ§ÙÙØ§ Ø®ÙØ±ÙÙ Ø¹ÙÙÙÙÙÙÙ Ø±ÙØ¬ÙÙÙ Ø¬ÙØ±ÙØ§
Grade:

Hadith #7494 - Sahih al-Bukhari (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âEvery night when it is the last third of the night, our Lord, the Superior, the Blessed, descends to the nearest heaven and says: Is there anyone to invoke Me that I may respond to his invocation? Is there anyone to ask Me so that I may grant him his request? Is there anyone asking My forgiveness so that I may forgive him?. â (See Hadith No. 246,Vol. 2) ÙÙØªÙÙÙØ²ÙÙÙÙ Ø±ÙØ¨ÙÙÙÙØ§ ØªÙØ¨ÙØ§Ø±ÙÙÙ ÙÙØªÙØ¹ÙØ§ÙÙÙ ÙÙÙÙÙ ÙÙÙÙÙÙØ©Ù
Grade:

Hadith #7495 - Sahih al-Bukhari (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âWe (Muslims) are the last (to come) but will be the foremost on the Day of Resurrection.â The narrators of this Hadith said: Allah said (to man), âSpend (in charity), for then I will compensate you (generously).â â ÙÙØÙÙÙ Ø§ÙØ¢Ø®ÙØ±ÙÙÙÙ Ø§ÙØ³ÙÙØ§Ø¨ÙÙÙÙÙÙ ÙÙÙÙÙÙ Ø§ÙÙÙÙÙÙØ§ÙÙØ©Ù ââ
Grade:

Hadith #7497 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) said that Gabriel said, âHere is Khadija coming to you with a dish of food or a tumbler containing something to drink. Convey to her a greeting from her Lord (Allah) and give her the glad tidings that she will have a palace in Paradise built of Qasab wherein there will be neither any noise nor any fatigue (trouble).â (See Hadith No. 168, Vol. 5) ÙÙØ°ÙÙÙ Ø®ÙØ¯ÙÙØ¬ÙØ©Ù Ø£ÙØªÙØªÙÙÙ Ø¨ÙØ¥ÙÙÙØ§Ø¡Ù ÙÙÙÙÙ Ø·ÙØ¹ÙØ§ÙÙ Ø£ÙÙÙ Ø¥ÙÙÙØ§Ø¡Ù ÙÙÙÙÙ Ø
Grade:

Hadith #7498 - Sahih al-Bukhari (Sahih al-Bukhari)
the Prophet (ï·º) said, âAllah said, âI have prepared for My righteous slaves (such excellent things) as no eye has ever seen, nor an ear has ever heard nor a human heart can ever think of.â â Ø£ÙØ¹ÙØ¯ÙØ¯ÙØªÙ ÙÙØ¹ÙØ¨ÙØ§Ø¯ÙÙ Ø§ÙØµÙÙØ§ÙÙØÙÙÙÙ ÙÙØ§ ÙØ§Ù Ø¹ÙÙÙÙÙ Ø±ÙØ£ÙØªÙØ ÙÙÙØ§Ù Ø£ÙØ°ÙÙÙ Ø³ÙÙÙØ¹ÙØªÙØ ÙÙÙØ§Ù Ø®ÙØ·ÙØ±Ù Ø¹ÙÙÙÙ ÙÙÙÙØ¨Ù Ø¨ÙØ´ÙØ±Ù ââ
Grade:

Hadith #7499 - Sahih al-Bukhari (Sahih al-Bukhari)
Whenever the Prophet (ï·º) offered the night (Tahajjud) prayer, he used to say, âO Allah! All the Praises are for You; You are the Light of the Heavens and the Earth. And all the Praises are for You; You are the Keeper of the Heavens and the Earth. All the Praises are for You; You are the Lord of the Heavens and the Earth and whatever is therein. You are the Truth, and Your Promise is the Truth, and Your Speech is the Truth, and meeting You is the Truth, and Paradise is the Truth and Hell (Fir
Grade:

Hadith #7500 - Sahih al-Bukhari (Sahih al-Bukhari)
Sa`id bin Al-Musaiyab, âAlqama bin Waqqas and âUbaidullah bin `Abdullah regarding the narrating of the forged statement against `Aisha, the wife of the Prophet, when the slanderers said what they said and Allah revealed her innocence. `Aisha said, âBut by Allah, I did not think that Allah, (to confirm my innocence), would reveal Divine Inspiration which would be recited, for I consider myself too unimportant to be talked about by Allah through Divine Inspiration revealed for recitation, bu
Grade:

Hadith #7501 - Sahih al-Bukhari (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âAllah says, âIf My slave intends to do a bad deed then (O Angels) do not write it unless he does it; if he does it, then write it as it is, but if he refrains from doing it for My Sake, then write it as a good deed (in his account). (On the other hand) if he intends to do a good deed, but does not do it, then write a good deed (in his account), and if he does it, then write it for him (in his account) as ten good deeds up to seven-hundred times.â â Ø¥ÙØ°
Grade:

Hadith #7502 - Sahih al-Bukhari (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âAllah created the creation, and when He finished from His creation the Rahm (womb) got up, and Allah said (to it). âStop! What do you want? It said; âAt this place I seek refuge with You from all those who sever me (i.e. sever the ties of Kinship.)â Allah said: âWould you be pleased that I will keep good relation with the one who will keep good relation with you, and I will sever the relation with the one who will sever the relation with you. It said: â
Grade:

Hadith #7503 - Sahih al-Bukhari (Sahih al-Bukhari)
It rained (because of the Prophetâs invocation for rain) and the Prophet (ï·º) said, âAllah said, âSome of My slaves have become disbelievers in Me, and some others, believers in Me.'â Ø£ÙØµÙØ¨ÙØÙ ÙÙÙÙ Ø¹ÙØ¨ÙØ§Ø¯ÙÙ ÙÙØ§ÙÙØ±Ù Ø¨ÙÙ ÙÙÙÙØ¤ÙÙÙÙÙ Ø¨ÙÙ ââ
Grade:

Hadith #7504 - Sahih al-Bukhari (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âAllah said, âIf My slaves loves the meeting with Me, I too love the meeting with him; and if he dislikes the meeting with Me, I too dislike the meeting with him.â â (See Hadith No. 514, Vol. 8) Ø¥ÙØ°ÙØ§ Ø£ÙØÙØ¨ÙÙ Ø¹ÙØ¨ÙØ¯ÙÙ ÙÙÙÙØ§Ø¦ÙÙ Ø£ÙØÙØ¨ÙØ¨ÙØªÙ ÙÙÙÙØ§Ø¡ÙÙÙØ ÙÙØ¥ÙØ°ÙØ§ ÙÙØ±ÙÙÙ ÙÙÙÙØ§Ø¦ÙÙ ÙÙØ±ÙÙÙØªÙ ÙÙÙÙØ§Ø¡ÙÙÙ ââ
Grade:

Hadith #7505 - Sahih al-Bukhari (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âAllah said, âI am to my slave as he thinks of Me, (i.e. I am able to do for him what he thinks I can do for him). (See Hadith No. 502) Ø£ÙÙÙØ§ Ø¹ÙÙÙØ¯Ù Ø¸ÙÙÙÙ Ø¹ÙØ¨ÙØ¯ÙÙ Ø¨ÙÙ ââ
Grade:

Hadith #7506 - Sahih al-Bukhari (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âA man who never did any good deed, said that if he died, his family should burn him and throw half the ashes of his burnt body in the earth and the other half in the sea, for by Allah, if Allah should get hold of him, He would inflict such punishment on him as He would not inflict on anybody among the people. But Allah ordered the sea to collect what was in it (of his ashes) and similarly ordered the earth to collect what was in it (of his ashes). Then Allah sa
Grade:

Hadith #7507 - Sahih al-Bukhari (Sahih al-Bukhari)
I heard the Prophet (ï·º) saying, âIf somebody commits a sin and then says, âO my Lord! I have sinned, please forgive me!â and his Lord says, âMy slave has known that he has a Lord who forgives sins and punishes for it, I therefore have forgiven my slave (his sins).â Then he remains without committing any sin for a while and then again commits another sin and says, âO my Lord, I have committed another sin, please forgive me,â and Allah says, âMy slave has known that he has a Lord
Grade:

Hadith #7508 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) mentioned a man from the people of the past or those who preceded you. The Prophet (ï·º) said a sentence meaning: Allah had given him wealth and children. When his death approached, he said to his sons, âWhat kind of father have I been to you?â They replied, âYou have been a good father.â He told them that he had not presented any good deed before Allah, and if Allah should get hold of him He would punish him.â âSo look!â he added, âWhen I die, burn me, and when
Grade:

Hadith #7509 - Sahih al-Bukhari (Sahih al-Bukhari)
I heard the Prophet (ï·º) saying, âOn the Day of Resurrection I will intercede and say, âO my Lord! Admit into Paradise (even) those who have faith equal to a mustard seed in their hearts.â Such people will enter Paradise, and then I will say, âO (Allah) admit into Paradise (even) those who have the least amount of faith in their hearts.â Anas then said: As if I were just now looking at the fingers of Allahâs Apostle. Ø¥ÙØ°ÙØ§ ÙÙØ§ÙÙ ÙÙÙÙÙÙ Ø§ÙÙÙÙÙÙØ§ÙÙØ©Ù Ø´ÙÙ
Grade:

Hadith #7510 - Sahih al-Bukhari (Sahih al-Bukhari)
We, i.e., some people from Basra gathered and went to Anas bin Malik, and we went in company with Thabit Al-Bunnani so that he might ask him about the Hadith of Intercession on our behalf. Behold, Anas was in his palace, and our arrival coincided with his Duha prayer. We asked permission to enter and he admitted us while he was sitting on his bed. We said to Thabit, âDo not ask him about anything else first but the Hadith of Intercession.â He said, âO Abu Hamza! There are your brethren fro
Grade:

Hadith #7511 - Sahih al-Bukhari (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âThe person who will be the last one to enter Paradise and the last to come out of Hell (Fire) will be a man who will come out crawling, and his Lord will say to him, âEnter Paradise.â He will reply, âO Lord, Paradise is full.â Allah will give him the same order thrice, and each time the man will give Him the same reply, i.e., âParadise is full.â Thereupon Allah will say (to him), âTen times of the world is for you.â â Ø¥ÙÙÙÙ Ø¢Ø®ÙØ±Ù Ø£Ù
Grade:

Hadith #7512 - Sahih al-Bukhari (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âThere will be none among you but his Lord will talk to him, and there will be no interpreter between him and Allah. He will look to his right and see nothing but his deeds which he has sent forward, and will look to his left and see nothing but his deeds which he has sent forward, and will look in front of him and see nothing but the (Hell) Fire facing him. So save yourself from the (Hell) Fire even with half a date (given in charity).â Al-A`mash said: `Amr b
Grade:

Hadith #7513 - Sahih al-Bukhari (Sahih al-Bukhari)
A priest from the Jews came (to the Prophet) and said, âOn the Day of Resurrection, Allah will place all the heavens on one finger, and the Earth on one finger, and the waters and the land on one finger, and all the creation on one finger, and then He will shake them and say. âI am the King! I am the King!'â I saw the Prophet (ï·º) smiling till his premolar teeth became visible expressing his amazement and his belief in what he had said. Then the Prophet (ï·º) recited: âNo just estimate
Grade:

Hadith #7514 - Sahih al-Bukhari (Sahih al-Bukhari)
A man asked Ibn `Umar, âWhat have you heard from Allahâs Messenger (ï·º) regarding An-Najwa?â He said, âEveryone of you will come close to His Lord Who will screen him from the people and say to him, âDid you do so-and-so?â He will reply, âYes.â Then Allah will say, âDid you do so-and-so?â He will reply, âYes.â So Allah will question him and make him confess, and then Allah will say, âI screened your sins in the world and forgive them for you today.â â Ø¥ÙÙÙÙÙ
Grade:

Hadith #7515 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) said, âAdam and Moses debated with each other and Moses said, âYou are Adam who turned out your offspring from Paradise.â Adam said, âYou are Moses whom Allah chose for His Message and for His direct talk, yet you blame me for a matter which had been ordained for me even before my creation?â Thus Adam overcame Moses.â Ø§ØÙØªÙØ¬ÙÙ Ø¢Ø¯ÙÙÙ ÙÙÙÙÙØ³ÙÙØ ÙÙÙÙØ§ÙÙ ÙÙÙØ³ÙÙ Ø£ÙÙÙØªÙ Ø¢Ø¯ÙÙÙ Ø§ÙÙÙØ°ÙÙ Ø£ÙØ®ÙØ±ÙØ¬ÙØªÙ Ø°ÙØ±ÙÙÙÙÙ
Grade:

Hadith #7516 - Sahih al-Bukhari (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âThe believers will be assembled on the Day of Resurrection and they will say, âLet us look for someone to intercede for us with our Lord so that He may relieve us from this place of ours.â So they will go to Adam and say, âYou are Adam, the father of mankind, and Allah created you with His Own Hands and ordered the Angels to prostrate before you, and He taught you the names of all things; so please intercede for us with our Lord so that He may relieve us.
Grade:

Hadith #7517 - Sahih al-Bukhari (Sahih al-Bukhari)
The night Allahâs Messenger (ï·º) was taken for a journey from the sacred mosque (of Mecca) Al-Ka`ba: Three persons came to him (in a dreamy while he was sleeping in the Sacred Mosque before the Divine Inspiration was revealed to Him. One of them said, âWhich of them is he?â The middle (second) angel said, âHe is the best of them.â The last (third) angle said, âTake the best of them.â Only that much happened on that night and he did not see them till they came on another night, i.e
Grade:

Hadith #7518 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) said, âAllah will say to the people of Paradise, âO the people of Paradise!â They will say, âLabbaik, O our Lord, and Sa`daik, and all the good is in Your Hands!â Allah will say, âAre you satisfied?â They will say, âWhy shouldnât we be satisfied, O our Lord as You have given us what You have not given to any of Your created beings?â He will say, âShall I not give you something better than that?â They will say, âO our Lord! What else could be better tha
Grade:

Hadith #7519 - Sahih al-Bukhari (Sahih al-Bukhari)
Once the Prophet (ï·º) was preaching while a bedouin was sitting there. The Prophet (ï·º) said, âA man from among the people of Paradise will request Allah to allow him to cultivate the land Allah will say to him, âHavenât you got whatever you desire?â He will reply, âyes, but I like to cultivate the land (Allah will permit him and) he will sow the seeds, and within seconds the plants will grow and ripen and (the yield) will be harvested and piled in heaps like mountains. On that Allah
Grade:

Hadith #7520 - Sahih al-Bukhari (Sahih al-Bukhari)
I asked Allahâs Messenger (ï·º) âWhat is the biggest sin in the sight of Allah?â He said, âTo set up rivals unto Allah though He alone created you.â I said, âIn fact, that is a tremendous sin,â and added, âWhat next?â He said, âTo kill your son being afraid that he may share your food with you.â I further asked, âWhat next?â He said, âTo commit illegal sexual intercourse with the wife of your neighbor.â Ø£ÙÙÙ ØªÙØ¬ÙØ¹ÙÙÙ ÙÙÙÙÙÙÙ ÙÙØ¯ÙÙØ§ ÙÙÙÙÙ
Grade:

Hadith #7521 - Sahih al-Bukhari (Sahih al-Bukhari)
Two person of Bani Thaqif and one from Quarish (or two persons from Quraish and one from Bani Thaqif) who had fat bellies but little wisdom, met near the Ka`ba. One of them said, âDid you see that Allah hears what we say? â The other said, âHe hears us if we speak aloud, but He does not hear if we speak in stealthy quietness (softly).â The third fellow said, âIf He hears when we speak aloud, then He surely hears us if we speak in stealthy quietness (softly).â So Allah revealed the Ve
Grade:

Hadith #7522 - Sahih al-Bukhari (Sahih al-Bukhari)
Ibn `Abbas said, âHow can you ask the people of the Scriptures about their Books while you have Allahâs Book (the Qurâan) which is the most recent of the Books revealed by Allah, and you read it in its pure undistorted form?â ÙÙÙÙÙÙ ØªÙØ³ÙØ£ÙÙÙÙÙÙ Ø£ÙÙÙÙÙ Ø§ÙÙÙÙØªÙØ§Ø¨Ù Ø¹ÙÙÙ ÙÙØªÙØ¨ÙÙÙÙÙ ÙÙØ¹ÙÙÙØ¯ÙÙÙÙÙ ÙÙØªÙØ§Ø¨Ù Ø§ÙÙÙÙÙÙ Ø£ÙÙÙØ±ÙØ¨Ù Ø§ÙÙÙÙØªÙØ¨Ù Ø¹ÙÙÙØ¯ÙØ§ Ø¨ÙØ§ÙÙÙÙÙÙØ ØªÙÙÙØ±ÙØ¡ÙÙÙÙÙÙ ÙÙØÙØ¶Ù
Grade:

Hadith #7523 - Sahih al-Bukhari (Sahih al-Bukhari)
`Abdullah bin `Abbas said, âO the group of Muslims! How can you ask the people of the Scriptures about anything while your Book which Allah has revealed to your Prophet contains the most recent news from Allah and is pure and not distorted? Allah has told you that the people of the Scriptures have changed some of Allahâs Books and distorted it and wrote something with their own hands and said, âThis is from Allah, so as to have a minor gain for it. Wonât the knowledge that has come to yo
Grade:

Hadith #7524 - Sahih al-Bukhari (Sahih al-Bukhari)
Sa`id bin Jubair reported from Ibn `Abbas (regarding the explanation of the Verse: âDo not move your tongue concerning (the Qurâan) to make haste therewith) . He said, âThe Prophet (ï·º) used to undergo great difficulty in receiving the Divine Inspiration and used to move his lips.â Ibn `Abbas said (to Sa`id), âI move them (my lips) as Allahâs Messenger (ï·º) used to move his lips.â And Sa`id said (to me), âI move my lips as I saw Ibn `Abbas moving his lips,â and then he moved
Grade:

Hadith #7525 - Sahih al-Bukhari (Sahih al-Bukhari)
regarding the explanation of the Verse:â â(O Muhammad!) Neither say your prayer aloud, nor say it in a low tone.â (17.110) This Verse was revealed while Allahâs Messenger (ï·º) was hiding himself at Mecca. At that time, when he led his companions in prayer, he used to raise his voice while reciting the Qurâan; and if the pagans heard him, they would abuse the Qurâan, its Revealer, and the one who brought it. So Allah said to His Prophet: âNeither say your prayer aloud. i.e., your r
Grade:

Hadith #7526 - Sahih al-Bukhari (Sahih al-Bukhari)
The Verse:â â(O Muhammad!) Neither say your prayer aloud nor say it in a low tone.â (17.110) was revealed in connection with the invocations. ÙÙØ²ÙÙÙØªÙ ÙÙØ°ÙÙÙ Ø§ÙØ¢ÙÙØ©Ù ââ{âÙÙÙØ§Ù ØªÙØ¬ÙÙÙØ±Ù Ø¨ÙØµÙÙØ§ÙØªÙÙÙ ÙÙÙØ§Ù ØªÙØ®ÙØ§ÙÙØªÙ Ø¨ÙÙÙØ§â}â ÙÙÙ Ø§ÙØ¯ÙÙØ¹ÙØ§Ø¡Ùâ.â
Grade:

Hadith #7527 - Sahih al-Bukhari (Sahih al-Bukhari)
Abu Huraira said, âAllahâs Messenger (ï·º) said, âWhoever does not recite Qurâan in a nice voice is not from us,â and others said extra,â (that means) to recite it aloud.â ÙÙÙÙØ³Ù ÙÙÙÙÙØ§ ÙÙÙÙ ÙÙÙÙ ÙÙØªÙØºÙÙÙÙ Ø¨ÙØ§ÙÙÙÙØ±ÙØ¢ÙÙ ââ
Grade:

Hadith #7528 - Sahih al-Bukhari (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âNot to wish to be the like of except the like of two men: a man whom Allah has given the Qurâan and he recites it during the hours of the night and the hours of the day, in which case one may say, âIf I were given the same as this man has been given, I would do the same as he is doing.â The other is a man whom Allah has given wealth and he spends it in the right way, in which case one may say, âIf I were given the same as he has been given, I would do t
Grade:

Hadith #7529 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) said, âNot to wish to be the like of except the like of two (persons): a man whom Allah has given the knowledge of the Qurâan and he recites it during the hours of the night and the hours of the day; and a man whom Allah has given wealth and he spends it (in Allahâs Cause) during the hours of the night and during the hours of the day.â ÙØ§Ù ØÙØ³ÙØ¯Ù Ø¥ÙÙØ§ÙÙ ÙÙÙ Ø§Ø«ÙÙÙØªÙÙÙÙÙ Ø±ÙØ¬ÙÙÙ Ø¢ØªÙØ§ÙÙ Ø§ÙÙÙÙÙÙ Ø§ÙÙÙÙØ±ÙØ¢ÙÙ ÙÙÙÙÙÙ
Grade:

Hadith #7530 - Sahih al-Bukhari (Sahih al-Bukhari)
Our Prophet has informed us our Lordâs Message that whoever of us is martyred, will go to Paradise. ÙÙÙÙ ÙÙØªÙÙÙ ÙÙÙÙÙØ§ ØµÙØ§Ø±Ù Ø¥ÙÙÙÙ Ø§ÙÙØ¬ÙÙÙÙØ©Ù ââ
Grade:

Hadith #7531 - Sahih al-Bukhari (Sahih al-Bukhari)
Whoever tells you that the Prophet (ï·º) concealed something of the Divine Inspiration, do not believe him, for Allah said: âO Apostle Muhammad! Proclaim (the Message) which has been sent down to you from your Lord, and if you do it not, then you have not conveyed His Message.â (5.67) ÙÙÙÙ ØÙØ¯ÙÙØ«ÙÙÙ Ø£ÙÙÙÙ Ø§ÙÙÙÙØ¨ÙÙÙÙ ØµÙÙ Ø§ÙÙÙ Ø¹ÙÙÙ ÙØ³ÙÙ ÙÙØªÙÙÙ Ø´ÙÙÙØ¦ÙØ§ ÙÙÙÙ Ø§ÙÙÙÙØÙÙÙØ ÙÙÙØ§Ù ØªÙØµÙØ¯ÙÙÙÙÙÙØ Ø¥ÙÙÙÙ Ø§ÙÙÙÙÙ
Grade:

Hadith #7532 - Sahih al-Bukhari (Sahih al-Bukhari)
A man said, âO Allahâs Messenger (ï·º)! Which sin is the biggest in Allahâs Sight?â The Prophet (ï·º) said, âTo set up rivals unto Allah though He Alone created you.â That man said, âWhat is next?â The Prophet (ï·º) said, âTo kill your son lest he should share your food with you.â The man said, âWhat is next?â The Prophet said, âTo commit illegal sexual intercourse with the wife of your neighbor.â Then Allah revealed in confirmation of that: âAnd those who invoke no
Grade:

Hadith #7533 - Sahih al-Bukhari (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âYour stay (in this world) in comparison to the stay of the nations preceding you, is like the period between `Asr prayer and the sun set (in comparison to a whole day). The people of the Torah were given the Torah and they acted on it till midday and then they were unable to carry on. And they were given (a reward equal to) one Qirat each. Then the people of the Gospel were given the Gospel and they acted on it till `Asr Prayer and then they were unable to carr
Grade:

Hadith #7534 - Sahih al-Bukhari (Sahih al-Bukhari)
A man asked the Prophet (ï·º) âWhat deeds are the best?â The Prophet (ï·º) said: â(1) To perform the (daily compulsory) prayers at their (early) stated fixed times, (2) to be good and dutiful to oneâs own parents, (3) and to participate in Jihad in Allahâs Cause.â Ø§ÙØµÙÙÙØ§ÙØ©Ù ÙÙÙÙÙÙØªÙÙÙØ§Ø ÙÙØ¨ÙØ±ÙÙ Ø§ÙÙÙÙØ§ÙÙØ¯ÙÙÙÙÙØ Ø«ÙÙÙÙ Ø§ÙÙØ¬ÙÙÙØ§Ø¯Ù ÙÙÙ Ø³ÙØ¨ÙÙÙÙ Ø§ÙÙÙÙÙÙ ââ
Grade:

Hadith #7535 - Sahih al-Bukhari (Sahih al-Bukhari)
`Amr bin Taghlib said, âSome property was given to the Prophet (ï·º) and he gave it to some people and withheld it from some others. Then he came to know that they (the latter) were dissatisfied. So the Prophet said, âI give to one man and leave (do not give) another, and the one to whom I do not give is dearer to me than the one to whom I give. I give to some people because of the impatience and discontent present in their hearts, and leave other people because of the content and goodness A
Grade:

Hadith #7536 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) said, âMy Lord says, âIf My slave comes nearer to me for a span, I go nearer to him for a cubit; and if he comes nearer to Me for a cubit, I go nearer to him for the span of outstretched arms; and if he comes to Me walking, I go to him running.â â Ø¥ÙØ°ÙØ§ ØªÙÙÙØ±ÙÙØ¨Ù Ø§ÙÙØ¹ÙØ¨ÙØ¯Ù Ø¥ÙÙÙÙÙÙ Ø´ÙØ¨ÙØ±ÙØ§ ØªÙÙÙØ±ÙÙØ¨ÙØªÙ Ø¥ÙÙÙÙÙÙÙ Ø°ÙØ±ÙØ§Ø¹ÙØ§Ø ÙÙØ¥ÙØ°ÙØ§ ØªÙÙÙØ±ÙÙØ¨Ù ÙÙÙÙÙÙ Ø°ÙØ±ÙØ§Ø¹ÙØ§ ØªÙÙÙØ±ÙÙØ¨ÙØªÙ Ù
Grade:

Hadith #7537 - Sahih al-Bukhari (Sahih al-Bukhari)
Perhaps the Prophet (ï·º) mentioned the following (as Allahâs Saying): âIf My slave comes nearer to Me for a span, I go nearer to him for a cubit; and if he comes nearer to Me for a cubit; I go nearer to him for the span of outstretched arms. (See Hadith No. 502) Ø¥ÙØ°ÙØ§ ØªÙÙÙØ±ÙÙØ¨Ù Ø§ÙÙØ¹ÙØ¨ÙØ¯Ù ÙÙÙÙÙÙ Ø´ÙØ¨ÙØ±ÙØ§ ØªÙÙÙØ±ÙÙØ¨ÙØªÙ ÙÙÙÙÙÙ Ø°ÙØ±ÙØ§Ø¹ÙØ§ ÙÙØ¥ÙØ°ÙØ§ ØªÙÙÙØ±ÙÙØ¨Ù ÙÙÙÙÙÙ Ø°ÙØ±ÙØ§Ø¹ÙØ§ ØªÙÙÙØ±ÙÙØ¨ÙØªÙ ÙÙÙÙÙÙ Ø¨
Grade:

Hadith #7538 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) said that your Lord said, âEvery (sinful) deed can be expiated; and the fast is for Me, so I will give the reward for it; and the smell which comes out of the mouth of a fasting person, is better in Allahâs Sight than the smell of musk.â (See Hadith No. 584) ÙÙÙÙÙÙÙ Ø¹ÙÙÙÙÙ ÙÙÙÙÙØ§Ø±ÙØ©ÙØ ÙÙØ§ÙØµÙÙÙÙÙÙ ÙÙÙ ÙÙØ£ÙÙÙØ§ Ø£ÙØ¬ÙØ²ÙÙ Ø¨ÙÙÙØ ÙÙÙÙØ®ÙÙÙÙÙÙ ÙÙÙÙ Ø§ÙØµÙÙØ§Ø¦ÙÙÙ Ø£ÙØ·ÙÙÙØ¨Ù Ø¹ÙÙÙØ¯Ù Ø§ÙÙÙÙÙ
Grade:

Hadith #7539 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) said that his Lord said: âIt does not befit a slave that he should say that he is better than Jonah (Yunus) bin Matta. ÙØ§Ù ÙÙÙÙØ¨ÙØºÙÙ ÙÙØ¹ÙØ¨ÙØ¯Ù Ø£ÙÙÙ ÙÙÙÙÙÙÙ Ø¥ÙÙÙÙÙÙ Ø®ÙÙÙØ±Ù ÙÙÙÙ ÙÙÙÙÙØ³Ù Ø¨ÙÙÙ ÙÙØªÙÙÙ ââââ.â ÙÙÙÙØ³ÙØ¨ÙÙÙ Ø¥ÙÙÙÙ Ø£ÙØ¨ÙÙÙÙâ.â
Grade:

Hadith #7540 - Sahih al-Bukhari (Sahih al-Bukhari)
Muâawiya bin Qurra reported that `Abdullah bin Al-Maghaffal Al-Muzani said, âI saw Allahâs Messenger (ï·º) on the day of the Conquest of Mecca, riding his she-camel and reciting Surat-al-Fath (48) or part of Surat-al-Fath. He recited it in a vibrating and pleasant voice. Then Muâawiya recited as `Abdullah bin Mughaffal had done and said, âWere I not afraid that the people would crowd around me, I would surely recite in a vibrating pleasant voice as Ibn Mughaffal did, imitating the Prop
Grade:

Hadith #7541 - Sahih al-Bukhari (Sahih al-Bukhari)
Abu Sufyan bin Harb told me that Heraclius called for his translator and then asked for the letter of the Prophet (ï·º), and the former read it (thus): âIn the Name of Allah, the Most Gracious, the Merciful. (This letter is) from Muhammad bin âAbdullah, to Heraclius. ââ¦O people of the Scripture (Jews and Christians): Come to a word that is just between us and you that we worship none but Allahâ¦â (V.3:64) ÙÙÙÙØ§ÙÙ Ø§Ø¨ÙÙÙ Ø¹ÙØ¨ÙÙØ§Ø³Ù Ø£ÙØ®ÙØ¨ÙØ±ÙÙÙÙ Ø£ÙØ¨ÙÙ Ø³Ù
Grade:

Hadith #7542 - Sahih al-Bukhari (Sahih al-Bukhari)
The people of the Scripture used to read the Torah in Hebrew and explain it to the Muslims in Arabic. Then Allahâs Messenger (ï·º) said, âDo not believe the people of the Scripture, and do not disbelieve them, but say, âWe believe in Allah and whatever has been revealedâ¦â (3.84) ÙØ§Ù ØªÙØµÙØ¯ÙÙÙÙÙØ§ Ø£ÙÙÙÙÙ Ø§ÙÙÙÙØªÙØ§Ø¨ÙØ ÙÙÙØ§Ù ØªÙÙÙØ°ÙÙØ¨ÙÙÙÙÙÙ ÙÙââ{âÙÙÙÙÙÙØ§ Ø¢ÙÙÙÙÙØ§ Ø¨ÙØ§ÙÙÙÙÙÙ ÙÙÙÙØ§ Ø£ÙÙÙØ²ÙÙÙâ}â Ø§ÙØ¢
Grade:

Hadith #7543 - Sahih al-Bukhari (Sahih al-Bukhari)
A Jew and Jewess were brought to the Prophet (ï·º) on a charge of committing an illegal sexual intercourse. The Prophet (ï·º) asked the Jews, âWhat do you (usually) do with them?â They said, âWe blacken their faces and disgrace them.â He said, âBring here the Torah and recite it, if you are truthful.â They (fetched it and) came and asked a one-eyed man to recite. He went on reciting till he reached a portion on which he put his hand. The Prophet (ï·º) said, âLift up your hand!â H
Grade:

Hadith #7544 - Sahih al-Bukhari (Sahih al-Bukhari)
that he heard the Prophet (ï·º) saying, âAllah does not listen to anything as He listens to the recitation of the Qurâan by a Prophet who recites it in attractive audible sweet sounding voice.â ÙÙØ§ Ø£ÙØ°ÙÙÙ Ø§ÙÙÙÙÙÙ ÙÙØ´ÙÙÙØ¡Ù ÙÙØ§ Ø£ÙØ°ÙÙÙ ÙÙÙÙØ¨ÙÙÙÙ ØÙØ³ÙÙÙ Ø§ÙØµÙÙÙÙØªÙ Ø¨ÙØ§ÙÙÙÙØ±ÙØ¢ÙÙ ÙÙØ¬ÙÙÙØ±Ù Ø¨ÙÙÙ ââ
Grade:

Hadith #7545 - Sahih al-Bukhari (Sahih al-Bukhari)
(when the slanderers said what they said about her): I went to my bed knowing at that time that I was innocent and that Allah would reveal my innocence, but by Allah, I never thought that Allah would reveal in my favor a revelation which would be recited, for I considered myself too unimportant to be talked about by Allah in the Divine Revelation that was to be recited. So Allah revealed the ten Verses (of Surat-an-Nur). âThose who brought a false chargeâ¦â¦..â (24.11-20) ÙÙØ§Ø¶ÙØ·ÙØ¬Ù
Grade:

Hadith #7546 - Sahih al-Bukhari (Sahih al-Bukhari)
I heard the Prophet (ï·º) reciting Surat at-Tin waz Zaitun (By the Fig and the Olive) in the `Ishaâ prayer and I have never heard anybody with a better voice or recitation than his. ÙÙÙÙØ§ Ø³ÙÙÙØ¹ÙØªÙ Ø£ÙØÙØ¯ÙØ§ Ø£ÙØÙØ³ÙÙÙ ØµÙÙÙØªÙØ§ Ø£ÙÙÙ ÙÙØ±ÙØ§Ø¡ÙØ©Ù ÙÙÙÙÙÙâ.â
Grade:

Hadith #7547 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) was hiding himself in Mecca and used to recite the (Qurâan) in a loud voice. When the pagans heard him they would abuse the Qurâan and the one who brought it, so Allah said to His Prophet: âNeither say your prayer aloud, nor say it in a low tone.â (17.110) ÙÙØ±ÙÙÙØ¹Ù ØµÙÙÙØªÙÙÙØ ÙÙØ¥ÙØ°ÙØ§ Ø³ÙÙÙØ¹Ù Ø§ÙÙÙÙØ´ÙØ±ÙÙÙÙÙÙ Ø³ÙØ¨ÙÙÙØ§ Ø§ÙÙÙÙØ±ÙØ¢ÙÙ ÙÙÙÙÙÙ Ø¬ÙØ§Ø¡Ù Ø¨ÙÙÙØ ÙÙÙÙØ§ÙÙ Ø§ÙÙÙÙÙÙ Ø¹ÙØ²ÙÙ ÙÙØ¬ÙÙÙ
Grade:

Hadith #7548 - Sahih al-Bukhari (Sahih al-Bukhari)
that Abu Sa`id Al-Khudri said to him, âI see that you like sheep and the desert, so when you are looking after your sheep or when you are in the desert and want to pronounce the Adhan, raise your voice, for no Jinn, human being or any other things hear the Mu`adh-dhinâs voice but will be a witness for him on the Day of Resurrection.â Abu Sa`id added, âI heard this from Allahâs Messenger (ï·º).â Ø¥ÙÙÙÙÙ Ø£ÙØ±ÙØ§ÙÙ ØªÙØÙØ¨ÙÙ Ø§ÙÙØºÙÙÙÙÙ ÙÙØ§ÙÙØ¨ÙØ§Ø¯ÙÙÙØ©Ù
Grade:

Hadith #7549 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) used to recite the Qurâan with his head in my lap while I used to be in my periods (having menses). ÙÙÙÙØ±ÙØ£Ù Ø§ÙÙÙÙØ±ÙØ¢ÙÙ ÙÙØ±ÙØ£ÙØ³ÙÙÙ ÙÙÙ ØÙØ¬ÙØ±ÙÙ ÙÙØ£ÙÙÙØ§ ØÙØ§Ø¦ÙØ¶Ùâ.â
Grade:

Hadith #7550 - Sahih al-Bukhari (Sahih al-Bukhari)
I heard Hisham bin Hakim reciting Surat-al-Furqan during the lifetime of Allahâs Messenger (ï·º), I listened to his recitation and noticed that he was reciting in a way that Allahâs Messenger (ï·º) had not taught me. I was about to jump over him while He was still in prayer, but I waited patiently and when he finished his prayer, I put my sheet round his neck (and pulled him) and said, âWho has taught you this Sura which I have heard you reciting?â Hisham said, âAllahâs Messenger (ï·
Grade:

Hadith #7551 - Sahih al-Bukhari (Sahih al-Bukhari)
I said, âO Allahâs Messenger (ï·º)! Why should a doer (people) try to do good deeds?â The Prophet (ï·º) said, âEverybody will find easy to do such deeds as will lead him to his destined place for which he has been created.â ÙÙÙÙÙ ÙÙÙÙØ³ÙÙØ±Ù ÙÙÙÙØ§ Ø®ÙÙÙÙÙ ÙÙÙÙ ââ
Grade:

Hadith #7552 - Sahih al-Bukhari (Sahih al-Bukhari)
While the Prophet (ï·º) was in a funeral procession, he took a stick and started scraping the earth with it and said, âThere is none of you but has his place assigned either in Hell or in Paradise.â They (the people) said, âShall we not depend upon that (and give up doing any deeds)?â He said, â Carry on doing (good deeds) for everybody will find it easy to do such deeds as will lead him to his destined place for which he has been created .â (And then the Prophet (ï·º) recited the Ve
Grade:

Hadith #7553 - Sahih al-Bukhari (Sahih al-Bukhari)
I heard Allahâs Messenger (ï·º) saying, âBefore Allah created the creations, He wrote a Book (wherein He has written): My Mercy has preceded my Anger.â and that (Book) is written with Him over the Throne.â ÙÙÙÙÙØ§ ÙÙØ¶ÙÙ Ø§ÙÙÙÙÙÙ Ø§ÙÙØ®ÙÙÙÙÙ ÙÙØªÙØ¨Ù ÙÙØªÙØ§Ø¨ÙØ§ Ø¹ÙÙÙØ¯ÙÙÙ ØºÙÙÙØ¨ÙØªÙ Ù Ø£ÙÙÙ ÙÙØ§ÙÙ Ø³ÙØ¨ÙÙÙØªÙ Ù Ø±ÙØÙÙÙØªÙÙ ØºÙØ¶ÙØ¨ÙÙâ.â ÙÙÙÙÙÙ Ø¹ÙÙÙØ¯ÙÙÙ ÙÙÙÙÙÙ Ø§ÙÙØ¹ÙØ±ÙØ´Ù ââ
Grade:

Hadith #7554 - Sahih al-Bukhari (Sahih al-Bukhari)
I heard Allahâs Messenger (ï·º) saying: âBefore Allah created the creations, He wrote a Book (wherein He has written): âMy Mercy has preceded my Anger.â And that is written with Him over the Throne.â (see Hadith 3194) Ø¥ÙÙÙÙ Ø§ÙÙÙÙÙÙ ÙÙØªÙØ¨Ù ÙÙØªÙØ§Ø¨ÙØ§ ÙÙØ¨ÙÙÙ Ø£ÙÙÙ ÙÙØ®ÙÙÙÙÙ Ø§ÙÙØ®ÙÙÙÙÙ Ø¥ÙÙÙÙ Ø±ÙØÙÙÙØªÙÙ Ø³ÙØ¨ÙÙÙØªÙ ØºÙØ¶ÙØ¨ÙÙâ.â ÙÙÙÙÙÙ ÙÙÙÙØªÙÙØ¨Ù Ø¹ÙÙÙØ¯ÙÙÙ ÙÙÙÙÙÙ Ø§ÙÙØ¹ÙØ±ÙØ´Ù ââ
Grade:

Hadith #7555 - Sahih al-Bukhari (Sahih al-Bukhari)
There were good relations and brotherhood between this tribe of Jurm and the Ash`ariyyin. Once, while we were sitting with Abu Musa Al-Ash`ari, there was brought to him a meal which contained chicken meat, and there was sitting beside him, a man from the tribe of Bani Taimul-lah who looked like one of the Mawali. Abu Musa invited the man to eat but the man said, âI have seen chicken eating some dirty things, and I have taken an oath not to eat chicken.â Abu Musa said to him, âCome along, l
Grade:

Hadith #7556 - Sahih al-Bukhari (Sahih al-Bukhari)
The delegates of `Abdul Qais came to Allahâs Messenger (ï·º) and said, âThe pagans of the tribe of Mudar intervene between you and us therefore we cannot come to you except in the Holy months. So please order us to do something good (Religious deeds) by which we may enter Paradise (by acting on them) and we may inform our people whom we have left behind to observe it.â The Prophet (ï·º) said, âI order you to do four things and forbid you from four things: I order you to believe in Allah.
Grade:

Hadith #7557 - Sahih al-Bukhari (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âThe painter of these pictures will be punished on the Day of Resurrection, and it will be said to them, Make alive what you have created.â â Ø¥ÙÙÙÙ Ø£ÙØµÙØÙØ§Ø¨Ù ÙÙØ°ÙÙÙ Ø§ÙØµÙÙÙÙØ±Ù ÙÙØ¹ÙØ°ÙÙØ¨ÙÙÙÙ ÙÙÙÙÙÙ Ø§ÙÙÙÙÙÙØ§ÙÙØ©ÙØ ÙÙÙÙÙÙØ§ÙÙ ÙÙÙÙÙÙ Ø£ÙØÙÙÙÙØ§ ÙÙØ§ Ø®ÙÙÙÙÙØªÙÙÙ ââ
Grade:

Hadith #7558 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) said, âThe painters of these pictures will be punished on the Day of Resurrection, and it will be said to them, âMake alive what you have created.â Ø¥ÙÙÙÙ Ø£ÙØµÙØÙØ§Ø¨Ù ÙÙØ°ÙÙÙ Ø§ÙØµÙÙÙÙØ±Ù ÙÙØ¹ÙØ°ÙÙØ¨ÙÙÙÙ ÙÙÙÙÙÙ Ø§ÙÙÙÙÙÙØ§ÙÙØ©ÙØ ÙÙÙÙÙÙØ§ÙÙ ÙÙÙÙÙÙ Ø£ÙØÙÙÙÙØ§ ÙÙØ§ Ø®ÙÙÙÙÙØªÙÙÙ ââ
Grade:

Hadith #7559 - Sahih al-Bukhari (Sahih al-Bukhari)
I heard the Prophet (ï·º) saying, âAllah said, âWho are most unjust than those who try to create something like My creation? I challenge them to create even a smallest ant, a wheat grain or a barley grain.â â ÙÙÙÙÙÙ Ø£ÙØ¸ÙÙÙÙÙ ÙÙÙÙÙÙÙ Ø°ÙÙÙØ¨Ù ÙÙØ®ÙÙÙÙÙ ÙÙØ®ÙÙÙÙÙÙØ ÙÙÙÙÙÙØ®ÙÙÙÙÙÙØ§ Ø°ÙØ±ÙÙØ©ÙØ Ø£ÙÙÙ ÙÙÙÙØ®ÙÙÙÙÙÙØ§ ØÙØ¨ÙÙØ©Ù Ø£ÙÙÙ Ø´ÙØ¹ÙÙØ±ÙØ©Ù ââ
Grade:

Hadith #7560 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) said, âThe example of a believer who recites the Qurâan is that of a citron (a citrus fruit) which is good in taste and good in smell. And the believer who does not recite the Qurâan is like a date which has a good taste but no smell. And the example of an impious person who recites the Qurâan is that of Ar-Rihana (an aromatic plant) which smells good but is bitter in taste. And the example of an impious person who does not recite the Qurâan is that of a colocynth whi
Grade:

Hadith #7561 - Sahih al-Bukhari (Sahih al-Bukhari)
Some people asked the Prophet (ï·º) regarding the soothsayers. He said, âThey are nothing.â They said, âO Allahâs Messenger (ï·º)! Some of their talks come true.â The Prophet (ï·º) said, âThat word which happens to be true is what a Jinn snatches away by stealth (from the Heaven) and pours it in the ears of his friend (the foreteller) with a sound like the cackling of a hen. The soothsayers then mix with that word, one hundred lies.â Ø¥ÙÙÙÙÙÙÙÙ ÙÙÙÙØ³ÙÙØ§ Ø¨ÙØ´ÙÙÙ
Grade:

Hadith #7562 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) said, âThere will emerge from the East some people who will recite the Qurâan but it will not exceed their throats and who will go out of (renounce) the religion (Islam) as an arrow passes through the game, and they will never come back to it unless the arrow, comes back to the middle of the bow (by itself) (i.e., impossible). The people asked, âWhat will their signs be?â He said, âTheir sign will be the habit of shaving (of their beards and their heads). (Fath-ul-Bar
Grade:

Hadith #7563 - Sahih al-Bukhari (Sahih al-Bukhari)
The Prophet (ï·º) said, â(There are) two words which are dear to the Beneficent (Allah) and very light (easy) for the tongue (to say), but very heavy in weight in the balance. They are: âSubhan Allah wa-bi hamdihiâ and âSubhan Allah Al-`Azim.â (see Hadith 6682). ÙÙÙÙÙÙØªÙØ§ÙÙ ØÙØ¨ÙÙØ¨ÙØªÙØ§ÙÙ Ø¥ÙÙÙÙ Ø§ÙØ±ÙÙØÙÙÙÙÙØ Ø®ÙÙÙÙÙÙØªÙØ§ÙÙ Ø¹ÙÙÙÙ Ø§ÙÙÙÙØ³ÙØ§ÙÙØ Ø«ÙÙÙÙÙÙØªÙØ§ÙÙ ÙÙÙ Ø§ÙÙÙÙÙØ²ÙØ§ÙÙ Ø³ÙØ¨ÙØÙØ§ÙÙ Ø§ÙÙÙÙ
Grade: